Whole-exome sequencing reveals a novel frameshift and a recurrent nonsense SPG11 variant causing rare familial amyotrophic lateral sclerosis type 5 in two consanguineous Pakistani families - Riaz Ahmad; Muhammad Naeem; Henry Houlden (Molecular Biology Reports, 2026)
Background Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease that affects both upper and lower motor neurons, disturbing communication between the brain and muscles. So far, few reports have been published for the SPG11 -associated ALS, and this is the first documented case from Pakistan. Methods We report a rare subtype of ALS with an autosomal recessive mode of inheritance with juvenile onset before 25 years of age in the five affected individuals from two unrelated families. Whole-exome sequencing was performed to identify disease-causing variants, and selected variants were further prioritized based on predicted pathogenicity and similarity to clinical phenotypes. Results Two homozygous variants within the SPG11 gene were identified as pathogenic according to the ACMG and ClinGen Sequence Variant Interpretation (SVI) Working Group recommendations: a novel truncation (NM_025137.4:c.6738dup, p.Glu2247Ter) variant as validated by Sanger sequencing and a recurrent nonsense (NM_025137.4: c.782C>A, p.Ser261Ter) variant (rs765477482) previously reported in a family affected with autosomal recessive hereditary spastic paraplegia (ARHSP). In silico prediction tools further confirmed their pathogenicity. Conclusion Five patients with juvenile-onset ALS born to consanguineous parents were found to have homozygous SPG11 gene variants. Our findings describe the overlapping phenotypes of SPG11 -related autosomal recessive juvenile ALS and ARHSP, suggesting that these disorders show a clear overlapping phenotype with common genetic defects. In clinical practice, it is challenging to distinguish between these two disorders. Additional Mendelian cases should be included to clarify further and investigate whether these represent two diverse diseases caused by variants in a single gene.

Correction: Molecular characterization and cuticular stomatal anatomy of Punica Granatum L. cultivars study in Dohuk governorate - Dalal Y. Kh. Sinjare; Shamiran S. Abdulrahman; Nizek S. Khalid; Rizgar Y. Ismail; Muhammad Yasir Naeem; Zeliha Selamoglu; Gani Issayev; Aveen M. N. Ahmed (Molecular Biology Reports, 2026)

Clinico-genetic heterogeneity in Pakistani families affected with muscular dystrophies - Riaz Ahmad; Muhammad Almas Hashmi; Asad Ullah; Ubaid Ur Rehman; Muhammad Naeem; Henry Houlden (Molecular Biology Reports, 2026)
Background Muscular dystrophies are a group of inherited neuromuscular disorders characterized by degenerative and progressive muscle weakness. Duchenne muscular dystrophy (DMD), Becker muscular dystrophy (BMD) and merosin-deficient congenital muscular dystrophy type 1 (MDC1A) are frequent forms caused by DMD (NM_004006.3) and LAMA2 (NM_000426.4) mutations, respectively. Methods and results Our study used whole exome sequencing to explore the molecular genetics of muscular dystrophies in six unrelated Pakistani families. We found four novel variants in the LAMA2 ; c.7470_7473del; p.(Lys2490AsnfsTer56) in family A, c.7807del; p.(Ala2603HisfsTer4) in family C, c.8651T > C; p.(Met2884Thr) in family D and c.4127T > A; p.(Leu1376Ter) in family E associated with MDC1A in these families. Furthermore, two already cited DMD variants were identified: c.10,801 C > T; p.(Gln872Ter) in family B and hemizygous genomic deletion in DMD (NM_004006.3):g.32438241_32809611del (corresponding to deletion of exons 7–29; GRCh38), which was identified (in family F) associated with BMD and DMD, respectively. Conclusions We present the first report of MDC1A-associated phenotypes caused by the LAMA2 gene in the Pakistani population, while DMD -related cases have already been documented in the literature and public databases. Clinical and molecular diagnosis of these six affected families will be valuable in therapeutic interventions and prenatal diagnosis of neuromuscular dystrophies in the familial and Pakistani populations. Our study emphasizes the effectiveness of next generation sequencing technology over traditional diagnostic methods such as muscle biopsies.

Polymeric Based Bioinspired Microneedle Patch for the Treatment of Androgenetic Alopecia (AGA) - Muhammad Irfan Siddique; Shaher Bano; Muhammad Sarfraz; Arslan Ghazanfar; Talha Jawaid; Tahir Ali Chohan; Muhammad Naeem; Abida Khan (Journal of Pharmaceutical Innovation, 2026)

Research knowledge in wolfberry (Lycium spp.) diseases: pathogen diversity, diagnostics, and integrated management under climate change - Olaide Ayodele Oladeji; Muhammad Naeem; Hafeez ur Rehman; Moses Akintayo Aborisade (Crop Protection, 2026)

Seasonal variation and source apportionment of heavy metals in the Jhelum river: Implications for water security - Muhammad Faisal; Feng Wu; Muhammad Waseem Boota; Shan-e-hyder Soomro; Muhammad Naeem; Yuzhong Zhang (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Stability of linear delay differential systems via Laplace transformation - Muhammad Naeem; Yang Kuang; Jiaxu Li (Mathematical Biosciences, 2026)

Retraction notice to “Effect of soil texture and zinc oxide nanoparticles on growth and accumulation of cadmium by wheat; a life cycle study” [Environ. Res. 216 (2023)114397] - Muhammad Usman; Muhammad Zia-ur-Rehman; Muhammad Rizwan; Tahir Abbas; Muhammad Ashar Ayub; Asif Naeem; Hesham F. Alharby; Nadiyah M. Alabdallah; Basmah M. Alharbi; Muhammad Javid Qamar; Shafaqat Ali (Environmental Research, 2026)

Assessing the legacy effects of COVID-19 lockdowns on insect pollinator biodiversity - Muhammad Naeem; Ting Shen; Maryam Riasat; Nawaz Haider Bashir; Tahir Farooq; Zhumei Li; Huanhuan Chen; Canping Pan (Biological Conservation, 2026)

Elevated DNA 5-hydroxymethylation promotes chondrocyte differentiation via TET-mediated epigenetic downregulation of hTERT in human mesenchymal stem cells - Naeem Ullah; Fazal Jalil; Muhammad Jaseem Khan; Muhammad Umair; Waseem Iqbal; Aamir Ali Khan (Histochemistry and Cell Biology, 2026)

Enhancing resource productivity and system sustainability on the Qinghai-Tibetan Plateau: a type-temporal-spatial coupling approach for forage-livestock balance - Jing Zhang; Nurlan Serekpayev; Muhammad Usman; Naeem Ahmad; Muhammad Bilal Hafeez; Qingping Zhou; Fujiang Hou; Zhibiao Nan (Plant and Soil, 2026)

Report of Mucopolysaccharidosis Type VI Disorder in Pakistani Patients Presenting Two Novel ARSB Variants - Bibi Zubaida; Hajira Batool; Huma Arshad Cheema; Muhammad Naeem (Biochemical Genetics, 2026)

Daturaolone from Datura metel L. Inhibits acetylcholinesterase and monoamine oxidase B - Bilal Khan; Marryum; Abdur Rauf; Ayesha Tahir; Umer Rashid; Hira Naeem; Muhammad Saeed Jan; Muhammad Shafique; Saima Naz; Alessandra Gianoncelli; Giovanni Ribaudo (Natural Product Research, 2026)

A time adaptive weighting framework for enhanced vegetation health index based drought monitoring - Muhammad Waseem; Ali Hasan Jaffry; Mudassar Iqbal; Muhammad Ajmal; Jiaqing Xiao; Tao Yang; Pengfei Shi; Awais Naeem Sarwar (Remote Sensing Applications: Society and Environment, 2026)

Energy-efficient pulsed photocatalysis with engineered biochar-ferrite nanocomposites for the reductive degradation of chlortoluron in water - Muhammad Imran; Behzad Murtaza; Muhammad Asif Naeem; Zia Ul Haq Khan; Jibran Iqbal; Muhammad Shahid; Long Li; Changseok Han (Journal of Environmental Management, 2026)

A multi-dimensional accounting framework to resolve the grassland-livestock paradox on the Qinghai-Tibetan Plateau - Jing Zhang; Naeem Ahmad; Muhammad Bilal Hafeez; Muhammad Usman; Qingping Zhou; Fujiang Hou; Zhibiao Nan (Global and Planetary Change, 2026)

Comparative experimental study on tower base load characteristics of a parked large-scale wind turbine under tornadoes and straight-line winds - Shiqin Zeng; Haiquan Jing; Xuhui He; Ashraf A. El Damatty; Baole Li; Dongqin Zhang; Muhammad Naeem (Engineering Structures, 2026)

Pressmud Alleviates Cadmium Stress in Wheat by Enhancing Soil Microbial Activity, Nutrient Uptake and Limiting Cd Accumulation - Basit Haider; Muhammad Imran; Fuad Ameen; Hadeeqa Arshad; Azhar Hussain; Ruijia Liu; Asif Naeem (Water, Air, & Soil Pollution, 2026)

Evaluation of Heavy Metal Tolerant Plant Growth Promoting Pseudomonas Strains for Improving the Growth of Eggplant (Solanum Melongena L.) under Lead (Pb) Stress - Uzma Ambreen; Muhammad Shabaan; Muhammad Junaid Sarwar; Mehreen Malik; Saira Sulaman; Hafiz Naeem Asghar; Usman Zulfiqar; Hossam S. El-Beltagi; Gamal Awad El-Shaboury; Arzu Bakhshaliyeva; Abdulrahman Alasmari (Water, Air, & Soil Pollution, 2026)

Cytotoxic and computational profiling of 2-mercaptobenzimidazole Mannich derivatives: structure activity relationship and carbonic anhydrase binding assessment - Muhammad Naeem; Arooj Mohsin Alvi; Muhammad Mehmmod Moin Ul Haq; Najia Shabbir; Shumaila Mehdi; Areen Khalid; Saqib Khan; Hafiz Muhammad Ahmad; Najm Ul Hassan Khan; Muhammad Nouman Arif; Hafiz Aamir Ali Kharl (Inflammopharmacology, 2026)

Metagenomic surveillance identifies a high-risk antibiotic resistance profile in community wastewater: a pilot study from Pakistan - Ishaq Khan; Ihtisham Naeem; Shujait Ali; Mahnoor Gulbin; Arshad Iqbal; Muhammad Shafiq (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Correction: Phytic acid content variation among wheat grain lines and its impact on nutritional quality and growth - Aurangzeb; Nodia Shujaat; Yaseen Ahmad; Muhammad Ikram; Summaira Shaheen; Muhammad Ishaq; Tahir Hameed; Saddam Hussain; Muhammad Romman; Naeem Khan (Vegetos, 2026)

Entomocidal effect of green synthesized titanium dioxide nanoparticles using Aloe vera Extract against Bemisia tabaci (Homoptera: Aleyrodidae) - Muhammad Shahid; Unsar Naeem-Ullah; Waheed S. Khan; Shafqat Saeed; Kashif Razzaq (International Journal of Tropical Insect Science, 2026)

Comparative in vitro pathogenicity of different oil-based formulations of Metarhizium anisopliae against three different aphid species - Ahmad Nawaz; Anam Ejaz; Tariq Mustafa; Usman Naeem; Amna Irshad; Muhammad Dildar Gogi; Muhammad Tayyib; Muhammad Naveed; Amjad Abbas; Muhammad Jalal Arif (International Journal of Tropical Insect Science, 2026)

Erratum to “Charge transfer and redox synergetic in MoSe2-V2O5 heterojunctions: high-performance bifunctional electrocatalyst for efficient overall water splitting” [Fuel 428 (2027) 140571] - Ambreen Bashir; Muhammad Rafaqat; Chang-Feng Yan; Md A. Wahab; Muhammad Sufyan Naeem; Abdual Waheed Rabbni; Tauseef Munawar; Faisal Iqbal (Fuel, 2026)

Corrigendum to “Charge transfer and redox synergetic in MoSe2-V2O5 heterojunctions: high-performance bifunctional electrocatalyst for efficient overall water splitting” [Fuel 428 (2027) 140571] - Ambreen Bashir; Muhammad Rafaqat; Chang-Feng Yan; Md A. Wahab; Muhammad Sufyan Naeem; Abdul Waheed Rabbani; Tauseef Munawar; Faisal Iqbal (Fuel, 2026)

Integrating Nanotechnology and Bioremediation for Efficient Heavy Metals Removal in Aquatic Ecosystems: A Comprehensive Review - Nadia Yasin; Syed Makhdoom Hussain; Shafaqat Ali; Ameer Fawad Zahoor; Abdulrahman Alasmari; Muhammad Munir; Muhammad Asrar; Muhammad Mudassar Shahzad; Adan Naeem (Water, Air, & Soil Pollution, 2026)

Pressmud Enhances Soil Microbial Activity, Root Endophyte Populations, Nutrient Uptake, and Wheat Growth in an Antibiotic-Contaminated Soil - Waqar Ul Abbas; Muhammad Imran; Muhammad Akhtar; Basit Haider; Hadeeqa Arshad; Asif Naeem (Journal of Soil Science and Plant Nutrition, 2026)

Clinical evaluation of adjunctive magnesium therapy in patients receiving antidepressants for depression—open label, nonrandomized clinical trial - Afifa Siddique; Uzma Naeem; Muhammad Masood Khokhar; Mushayada Irshad; Tayaba Farooq; Sughra Kanwal (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Impact of CODMn gradients on element cycling in a membrane-aeration combined with bacteria–algae symbiosis system for mariculture wastewater treatment - Yingzhen Wei; Muhammad Naeem Ramzan; Wen Yang; Zhongming Zheng (Journal of Environmental Chemical Engineering, 2026)

Melatonin with Reduced Nitrogen Enhances Rice Productivity and Lowers Nitrous Oxide Emissions by Stimulating Carbon Assimilation - Daji Li; Muhammad Naeem Sattar; Abdul Ghafoor (Journal of Soil Science and Plant Nutrition, 2026)

Genome-Wide Identification and In Silico Characterization of the ALKBH Gene Family in Rice (Oryza sativa L.) Under Abiotic Stress Conditions - Shabana Iqbal; Muhammad Naeem; Zeeshan Ali; Muhammad Saqib (Journal of Crop Health, 2026)

Identification and Computational Analysis of a Novel Pathogenic DKC1 Variant Underlying X-Linked Dyskeratosis Congenita - Namra Asghar; Wardah Sajjad; Muhammad Naeem (Biochemical Genetics, 2026)

Application of advanced oxidation processes for remediation of rubber industry wastewater: a comprehensive review - Zafran Ullah; Zhen-Yu Tian; Collin G. Joseph; Sabine Neusatz Guilhen; Siow Hwa Teo; Jualang Azlan Gansau; Rosalam Sarbatly; Kartini Alias; Pretibaa Subhramaniyun; Muhammad Naeem Khan; Muhammad Shahid Iqbal (Environmental Science and Pollution Research, 2026)

Bioactive phenolic allelochemicals from mulberry leaf litter through bioassay-guided fractionation and their bioherbicidal activity - Shagufta Perveen; Muhammad Naeem Mushtaq; Muhammad Yousaf; Raihan Ismil (Natural Product Research, 2026)

Boundary-Consistent Ordinal Regression for wheat yield prediction using UAV-based multispectral time-series data - Muhammad Salman Akhtar; Zuhair Zafar; Zahid Mahmood; Muhammad Kashif Naeem; Kanat Yermekbayev; Muhammad Moazam Fraz (Computers and Electronics in Agriculture, 2026)

State-of-the-art adsorbent materials for Bisphenol A removal from water: A systematic evaluation of mechanisms, performance, and environmental sustainability - Muhammad Sajid; Mohammed Altahir Suliman; Mazen K. Nazal; I. Ihsanullah; Naeem Ur Rehman (Journal of Water Process Engineering, 2026)

A novel spatiotemporal and machine learning framework for sustainable groundwater monitoring and management - Sheraz Maqbool; Muhammad Imran Khan; Aamir Raza; Mumtaz Ali; Naeem Saddique; Qaisar Saddique (Groundwater for Sustainable Development, 2026)

Pangenome-assisted characterization of TaBAM genes and association of TaBAM16-1B with NDVI in wheat - Maira Anam; Zulqurnain Khan; Muhammad Ali Sher; Muhammad Sajjad; Muhammad Kashif Naeem; Zijin Zhang; Sania Javeed; Fatima Javeria; Jing Chen; Shoaib Ur Rehman (Theoretical and Applied Genetics, 2026)

From Sequence to Solution: Computational Design of a Multi-Epitope Vaccine Candidate Against Francisella tularensis - Muhammad Suleman; Allah Rakha Yaseen; Ayman Naeem; Fuad M. Alzahrani; Khalid J. Alzahrani; Khalaf F. Alsharif; Misbah Khan (Probiotics and Antimicrobial Proteins, 2026)

Protective potential of linalool against cyclophosphamide-induced interstitial cystitis: mechanistic insights from experimental and computational approaches - Irfan Anjum; Asfia Arooje; Saima; Fawad Naeem; Muhammad Naveed Mushtaq; Kashif Barkat; Zaka Ur Rehman; Syed Damin Abbas Hamdani; Shah Jahan; Mohammed Dauelbait; Amir Bouallegue; Esmael M. Alyami; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Unveiling Pakistan’s hydro-climatic shifts: trends and change-points in soil moisture and potential evapotranspiration across Pakistan’s climatic zones - Darakshan Naeem; Abdullah Taib; Muhammad Awais; Rizwan Aziz; Muhammad Zaman (Meteorology and Atmospheric Physics, 2026)

Molecular detection of Toxoplasma gondii in Amblyomma gervaisi ticks infesting monitor lizards (Varanus bengalensis) - Muhammad Naeem; Muhammad Ammar Ameen; Hafiza Misbah Munir; Huma Fatima; Shakir Ullah; Hira Muqaddas; Kasim Sakran Abass; Adil Khan; Furhan Iqbal (Experimental and Applied Acarology, 2026)

Unraveling the synergistic effects of Bacillus cereus and different concentrations of silicon nanoparticles on wheat under rain-fed conditions of Pakistan - Muhammad Umer; Kahkashan Perveen; Faheema Khan; Jayanthi Barasarathi; Naeem Khan; Nageen Bostan; Summiya Faisal; Zainab Asif; Noshin Ilyas (Environmental Geochemistry and Health, 2026)

Myricetin as a potential therapeutic agent against Pseudomonas aeruginosa : inhibition of biofilm formation, quorum sensing, and virulence factor production - Sallah A. Al Hashedi; Saif M. Dmour; Hamad Sarheed Galut; Ayman Daifallah Ismail Alsheikh; Mohammad H. Abukhalil; Sham Ma’aitah; Najeeb S. Al-Zoreky; Khaled M.A. Ramadan; Muhammad Naeem Sattar; Zafar Iqbal; Adil Alshoaibi; Sultan A. M. Saghir (Biofouling, 2026)

A weighted ensemble DL framework for granular RPV inventory and energy yield analysis in Pakistan - Muhammad Kamran Lodhi; Yumin Tan; Yang Li; Faisal Mumtaz; Shahid Naeem (Remote Sensing Applications: Society and Environment, 2026)

Novel design of Fe0-and AC-doped hydroxyapatite-alginate composites for efficient arsenic clean-up: Mechanistic insights from batch and column tests - Behzad Murtaza; Farwah Shamshir; Muhammad Imran; Muhammad Shahid; Kifayat Ullah; Muhammad Nadeem; M. Asif Naeem; Noor Samad Shah; Jianxu Wang; Ajmal Khan; Changseok Han (Journal of Environmental Management, 2026)

Individual and combined decontamination effect of aqueous ozone and plant extracts on fungi and aflatoxins in brown rice - Iqra Naeem; Amir Ismail; Yun Yun Gong; Muhammad Riaz; Muhammad Arif Shahzad; Aneela Hameed; Mubashir Aziz; Asif Mahmood; Waheed Al Masry; Muhammad Latif; Sher Ali; Carlos A.F. Oliveira (Food Control, 2026)

Valorization of pongamia pinnata (sukhchain) seed oil for sustainable biodiesel production via Na2O/MgFe2O4 catalyst: kinetics, thermodynamic and cost estimation analysis - Ihtisham Wali Khan; Muhammad Shahid; Muhammad Farooq; Abdul Naeem; Yinhai Su; Najm Us Saqib; Fouzia Perveen; Imran Ullah (Biomass and Bioenergy, 2026)

Remediation of Pb2+ Ions by Green Route Modified Carbon Nanotubes - Saba Zafar; Abdul Amir; Saira Arif; Fozia Bibi; Ammara Aftab; Muhammad Naeem Ahmed; Muhammad Waseem (Water, Air, & Soil Pollution, 2026)

Fecal microbiota transplantation in inflammatory bowel disease: a systematic review and meta-analysis of randomized controlled trials (2020–2025) - Sania Ikram; Muneeb Ullah; Juho Lee; Nurhasni Hasan; Jin-Wook Yoo; Raees Khan; Muhammad Naeem (Inflammopharmacology, 2026)

Retraction Note: Study of variability, combining ability, genetics and association of different yield related traits in rice (Oryza sativa L.) genotypes - Zeeshan Ali; Muhammad Naeem; Iqra Rafiq; Rao Muhammad Ikram; M. Irfan Akram; Ehab I. Taha; Mounir M. Bekhit; Ozhan Simsek; Tolga Izgu; Temoor Ahmed; Javed Iqbal; Rashid Iqbal (Genetic Resources and Crop Evolution, 2026)

The virulence regulator Rv3425 mediates stress adaptation and promotes intracellular survival of Mycobacterium tuberculosis avirulent strain - Wei Zhu; Aikebaier Reheman; Guanghui Dang; Yifan Wang; Huaiyuan Cai; Xuan Yang; Mingjue Liu; Muhammad Ahsan Naeem; Xi Chen (Archives of Microbiology, 2026)

Mechanistic and Synergistic Evaluation of Amodiaquine–Isometamidium Combination Against Trypanosoma evansi: Integrated In Silico–In-Vitro Insights - Waqas Ahmad; Naeem Rasool; Mehmood Ahmad; Muhammad Yasin Tipu; Tehreem Fayyaz; Usama Bin Naeem; Sadaf Aroosa; Rana Muhammad Zahid Mushtaq (Acta Parasitologica, 2026)

Agriculture, industry, and economic growth as determinants of carbon emissions in climate hotspots: evidence from dynamic causal analysis - Amir Mustafa; Naeem Ahmed; Munib Ahmed; Muhammad Adnan Bashir (Environment, Development and Sustainability, 2026)

Multifunctional Curcumin Nanoparticles: Oncolytic, Radical Scavenging, Regenerative, Hepatoprotective, and Bactericidal Effects - Huzaifa Hanif; Shahzad Hussain; Umer Rashid; Tafail Akbar Mughal; Muhammad Naeem Ahmad; Muhammad Waseem (Cell Biochemistry and Biophysics, 2026)

Molecular characterization and genetic diversity of cotton whitefly Bemisia tabaci infesting cotton crops - Qamar Saeed; Muhammad Sagheer; Ummad ud din Umar; Muhammad Taimoor Shakeel; Mahmoud Moustafa; Mohammed Al-Shahrani; Uthman Algopishi; Muhammad Naeem; Mahmoud Ahmed Amer (International Journal of Tropical Insect Science, 2026)

YOLOv8n-PFA: a parallel fusion attention network for enhanced target detection in challenging environments - Muhammad Rashid; Junfeng Wang; Faheem Ahmed; Naeem Ahmed; Syed Agha Hassnain Mohsan; Eatedal Alabdulkreem; Samih M. Mostafa (Frontiers in Marine Science, 2026)
Introduction Underwater target detection plays a crucial role in marine environmental monitoring and ocean exploration. However, accurate detection remains challenging due to low illumination, blurred small objects, and complex background interference. Although convolutional neural network-based detectors have improved detection performance, many existing approaches are computationally expensive, limiting their deployment on resource-constrained underwater platforms. Methods To address these challenges, we propose YOLOv8n-PFA, a lightweight and high-precision underwater object detection framework. The proposed method introduces a novel Parallel Fusion Attention (PFA) module that models channel and spatial attention in parallel using residual connections to enhance discriminative features while suppressing background noise. The Wise Intersection over Union (WIoUv3) loss is incorporated to stabilize training and improve localization accuracy. Additionally, depth-wise convolutions (DWConv) are strategically applied to reduce model parameters and computational complexity. To further validate generalization capability, the PFA module is also integrated into YOLOv11n. Results Experimental results show that YOLOv8n-PFA achieves 84.2% mean Average Precision (mAP) on the URPC2020 dataset with 2.68 M parameters and 7.7 GFLOPs, and 84.8% mAP on the RUOD dataset with 2.98 M parameters and 7.9 GFLOPs. When integrated into YOLOv11n, the model achieves 84.7% mAP on URPC2020 and 85.3% on RUOD with only 2.76 M parameters and 6.5 GFLOPs. Across both datasets, the proposed approach improves mAP by 2.8-4.1% over baseline models while maintaining a lightweight architecture. Discussion The results demonstrate that the proposed framework provides an effective and computationally efficient solution for real-time underwater target detection in challenging marine environments. The consistent performance gains across different YOLO generations further confirm the scalability and robustness of the proposed PFA module.

Biofloc technology: a comprehensive review of its implications for enhancing aquaculture production - Nadia Yasin; Syed Makhdoom Hussain; Bedur Faleh Albalawi; Muhammad Amjad; Adan Naeem; Eman Naeem; Zainab Akram; Mubeena Akbar (Aquaculture International, 2026)

Closed-loop processing of in-situ modified wood: Biopolymer-structure-property relationships - Tanveer Farid; Kashif Abbass; Lev A. Trusov; Boris P. Gorshunov; Evgeny A. Gorbachev; Saghir Hussain; Muhammad Naeem Ashiq; Yike Li; Muhammad Imran Asghar; Shukui Li; Hongyi Liu; Jing Yu; et al. (Carbohydrate Polymers, 2026)

Evaluation of Genetic Diversity, Yield, and Its Associated Traits in Rice (Oryza Sativa L.) Genotypes - Zeeshan Ali; Muhammad Naeem; Iqra Rafiq; Abdul Rehman; Shabir Ahmad; Khairiah Mubarak Alwutayd; Fatmah Ahmed Safhi; Javed Iqbal; Rashid Iqbal (Plant Molecular Biology Reporter, 2026)

Iodine availability in soil and accumulation by maize in limed and humic acid–amended soil fertilized with iodide and iodate - Asif Naeem; Muhammad Faizan Ilyas; Karl H. Mühling (Plant and Soil, 2026)

Chitosan-mediated elicitation enhanced production of secondary metabolites and antioxidant assays in callus culture of Ocimum bacilicum L. (Purple Basil) - Gouhar Zaman; Samah Saleh Al-Shybany; Muhammad Naeem Bajwa; Muhammad Salman Khan; Muhammad Nadeem; Muhammad Zia; Christophe Hano; Bilal Haider Abbasi (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Performance Assessment of Diverse Spelt Wheat (Triticum spelta L.) Genotypes Across Three Years Seasons in Central Europe - Jaffar Iqbal; Naeem Ahmad; Muhammad Roman; Lukáš Hlisnikovský; Jiří Hermuth; Michal Hejcman (International Journal of Plant Production, 2026)
Spelt wheat ( Triticum spelta L.), known as an ancient cereal, is gaining popularity again due to its exceptional dietary value, adaptability to climate change, and low resource inputs. However, limited information is available about the diverse spelt lines agronomic and nutritional performance under fluctuating environments in central Europe. To determine agronomic and grain nutritional characteristics of 46 spelt wheat genotypes from the Czech Republic, Germany, and Switzerland, a 3-year field study (2021–2023) was carried-out at the Crop Research Institute, Czech University of Life Sciences, Prague. Our results showed highest genotypic variability among measured traits. Agronomic traits such as plant height, spike length, 1000 grain weight and grain yield were highest in genotype 69Z6.205, followed by 69Z6.204. Nutritional quality traits such as crude protein and starch content were greatest in genotypes 69Z6.205 (20.7% and 63.3%). Moreover, Zeleny sedimentation values were noted higher in 69Z6.205 genotype, compared to genotypes under study. Regarding years comparison, 2023 significantly improved the agronomic and quality traits followed by 2021 and 2022. The correlation and principal component analysis demonstrated that the grain yield, harvest index and quality factors (starch and Zeleny sedimentation value) are strongly associated with each other, thus indicating integrated adaptability potential to promote productivity and quality. The principal findings of the mantel correlation test are that the interannual climatic variability was significant contributor, shows trade-offs in total biomass production and partitioning efficiency to grain components, thereby revealing insights into traits performance over temporal scale. Overall, certain genotypes (particularly, 69Z6.205, 69Z6.204, 69Z6.148 and 69Z6.153) produced high yield and had good nutritional value, these lines could be considered for future breeding projects because of the nutrient-enhanced and climate-resilient characteristics. These findings suggest that spelt wheat has agronomic and nutritional potential as a viable substitute for bread wheat in central European agroecosystems.

Computationally guided synthesis and biological profiling of chalcones as antioxidant and anti-inflammatory activities - Hafiz Aamir Ali Kharl; Muhammad Naeem; Shakira Ghazanfar; Arifa Mehreen; Hasnain Haider; Sumel Ashique; Sabina Yasmin; Fatimah M. Al-Salem; Md Yousuf Ansari (Inflammopharmacology, 2026)

Sublethal effects of azadirachtin on life table parameters of Musca domestica (Diptera: Muscidae): implications for population dynamics in Pakistan - Naeem Iqbal; Nauman Sadiq; Hafiz Azhar Ali Khan; Allah Ditta Abid; Muhammad Sohail Shahzad; Muhammad Nadir Naqqash; Adnan Akhter (International Journal of Tropical Insect Science, 2026)

High Adsorption Potential of Co-Pyrolyzed Biochars for Acid Blue 93 in Wastewater - Dania Majeed; Muhammad Bilal Shakoor; Muhammad Awais; Naeem Akhtar Abbasi (Water, Air, & Soil Pollution, 2026)

Overexpression of rapeseed BnaLhcb5.3 mediates cellular metabolism and antioxidant defense under chromium stress - Iram Batool; Tongjun Qin; Ahsan Ayyaz; Fakhir Hannan; Muhammad Javed; Weiqi Chen; Zafar Ullah Zafar; Muhammad Shahbaz Naeem; Muhammad Ahsan Farooq; Weijun Zhou (Physiology and Molecular Biology of Plants, 2026)

Unveiling Hidden Threats: Molecular Detection and Genetic Diversity of Hepatozoon spp. and Toxoplasma Gondii in Wild Rodents of Saudi Arabia and Their Ectoparasites - Maryam Ijaz; Samia Q. Alghamdi; Abdullah D Alanazi; Mubashra Salim; Muhammad Naeem; Muhammad Ali; Shabana Mukhtiar; Kasim Sakran Abass; Hira Muqaddas; Adil Khan; Furhan Iqbal (Acta Parasitologica, 2026)

Mitigating cadmium toxicity in rice through tandem application of zinc oxide nanoparticles and Serendipita indica as revealed by multi-omics and NMT-based ion flux analysis - Muhammad Faheem Adil; Muhammd Naeem; Shafaque Sehar; Fanrui Zhou; Syed Muhammad Hassan Askri; Yunqi Liu; Zhong-Hua Chen; Wenwu Zhou; Imran Haider Shamsi (Journal of Hazardous Materials, 2026)

Influence of externally added organic or inorganic acids on evolution of property of hydrochar from hydrothermal carbonization of potato peel - Muhammad Mahboob Naeem; Sobia Kousar; Yuchen Jiang; Mengjiao Fan; Inkoua Stelgen; Shu Zhang; Xun Hu (Biomass and Bioenergy, 2026)

Thiamine and Indole-3-acetic Acid Mediated Detoxification of Arsenic in Maize to Improve Grain Proximate Components, Yield, and Nutrient Ingredients - Muhammad Atif; Shagufta Perveen; Farah Saeed; Abida Parveen; Sara Zafar; Naeem Iqbal (Water, Air, & Soil Pollution, 2026)

A comprehensive insight on the bioactive phytochemicals and pharmacological propensities of Ficus benghalensis L.: a reservoir for modern drug discovery - Sulaman Yaqub; Muhammad Islam; Hamid Saeed; Abrar Ahmad; Khurram Aamir; Rida Naeem; Meerab Tanveer (Phytochemistry Reviews, 2026)

Laboratory and greenhouse endophytic colonization of tomato by three entomopathogenic fungal isolates for the management of Tetranychus urticae and field efficacy trials - Waqas Wakil; Maria C. Boukouvala; Nickolas G. Kavallieratos; Aqsa Naeem; Syed Adnan Haider; Muhammad Usman Ghazanfar; Pasco B. Avery (Crop Protection, 2025)

Simulating and predicting lake dynamics by fusing HBV modeling, machine learning approach and remote sensing data - Muhammad Naeem; Yongqiang Zhang; Ning Ma; Zixuan Tang; Ping Miao; Xiaoqiang Tian; Congcong Li; Qi Huang; Zhenwu Xu; Longhao wang; Zhen Huang (Journal of Hydrology, 2025)

Solid phase microextraction of chlorpyrifos residues in food samples using polyacrylamide@MOF/MXene composite - Sumaira Sabir; Nadeem Raza; Muhammad Hayat; Suryyia Manzoor; Faryal Aftab; Lilia Basilio de Caland; Muhammad Imran Khan; Ahmed Yar; Faisal K. Algethami; Mostafa E. Salem; Anis Ahmad Chaudhary; Muhammad Naeem Ashiq (Food Chemistry, 2025)

Synergistic Arsenic Adsorption by Nano Zero-Valent Iron and Biochar: Batch and Column Scale Performance - Muhammad Asif Naeem; Muhammad Imran; Muhammad Amjad; Ghulam Mustafa Shah; Ghulam Abbas; Behzad Murtaza; Muhammad Shafique Khalid; Hafiz Faiq Bakhat; Samina Khalid; Muhammad Imtiaz Rashid (Water, Air, & Soil Pollution, 2025)

The weight reducing effects of naltrexone-bupropion among obese psychiatric and non-psychiatric patients: a systematic review - Hafsah Alim Ur Rahman; Muhammad Ahmed Ali Fahim; Unaiza Naeem; Syed Hassan Ahmed; Muhammad Youshay Jawad; Hareem Arshad; Anil Kalyoncu; Mujeeb U. Shad; Ahmad Hameed (Psychopharmacology, 2025)

QARS1 associated developmental epileptic encephalopathy: first report of a rare homozygous missense variant from Pakistan causing nonepileptic phenotype in a family of seven patients and a comprehensive review of the literature - Riaz Ahmad; Muhammad Naeem; Henry Houlden (Molecular Biology Reports, 2025)
Background Pathogenic variants in QARS1 (MIM:603727; Glutaminyl-TRNA Synthetase 1), which encodes Glutaminyl-tRNA synthetase 1, have been associated with rare progressive microcephaly with seizures and cerebral and cerebellar atrophy (MSCCA MIM:615760). Only a handful of MSCCA patients have been reported in the literature mostly associated with compound heterozygous QARS1 variants. In the current study, we aimed molecular characterization of a large consanguineous Pakistani family affected with microcephaly, severe intellectual and developmental disability. Methods We isolated genomic DNA from blood samples collected from the two affected and three normal individuals of the family. We employed whole exome sequencing, homozygosity mapping, Sanger sequencing and in silico protein modelling tools to characterize the pathogenic variant causing the disease phenotype. Moreover, we collected data of 26 MSCCA patients previously reported in the literature. Results The phenotype in the affected individuals of the family was characterized by microcephaly, severe intellectual and developmental disability, but no epilepsy. We found a rare QARS1 variant NM_005051.3:c.1133G > A, p.(Arg378His) in homozygous state in the family. This variant was recently cited in a patient of Turkish ethnicity, the only MSCCA patient reported with nonepileptic phenotype. This variant lying in the catalytic domain of glutaminyl-tRNA synthetase 1 showed deleterious structure and functional impacts on the protein predicted by in silico tools. The variant was classified as ‘likely pathogenic’ following ACMG guidelines. Conclusions We present first report of QARS1 associated developmental encephalopathy from Pakistan. Our study adds to the restricted clinical and mutational database of this rare disorder supporting the growing evidence that homozygous missense QARS1 genotypes may lead to the milder phenotype. The reports of more patients with molecular studies will enhance the understanding of the genotype-phenotype correlations.

Molecular characterization and cuticular stomatal anatomy of Punica Granatum L. cultivars study in Dohuk governorate - Dalal Y. Kh. Sinjare; Shamiran S. Abdulrahman; Nizek S. Khalid; Rizgar Y. Ismail; Muhammad Yasir Naeem; Zeliha Selamoglu; Gani Issayev; Aveen M. N. Ahmed (Molecular Biology Reports, 2025)

Molecular and computational analysis of a novel pathogenic variant in emopamil-binding protein (EBP) involved in cholesterol biosynthetic pathway causing a rare male EBP disorder with neurologic defects (MEND syndrome) - Hadiba Bibi; Riaz Ahmad; Fatima Rahman; Shazia Maqbool; Muhammad Naeem; Stephanie Efthymiou; Henry Houlden (Molecular Biology Reports, 2025)
Background Male EBP disorder with neurologic defects (MEND syndrome) is an extremely rare disorder with a prevalence of less than 1/1,000,000 individuals worldwide. It is inherited as an X-linked recessive disorder caused by impaired sterol biosynthesis due to nonmosaic hypomorphic EBP variants. MEND syndrome is characterized by variable clinical manifestations including intellectual disability, short stature, scoliosis, digital abnormalities, cataracts, and dermatologic abnormalities. The goal of this study was to investigate the disease-causing variants in a family of two patients affected with MEND syndrome. Methods The genomic DNA of the two patients with MEND syndrome was subjected to whole exome sequencing to identify disease-causing variants. Segregation of the identified variant was tested through Sanger sequencing. Several in-silico tools were used to evaluate the pathogenicity of the variant. Protein’s 3D structure analysis systems were used to predict the impact of the identified variant on the binding and function of the mutated EBP protein including AlphaFold, PyMOL, AutoDock, ChimeraX and Discovery Studio. Results A novel pathogenic missense EBP variant NM_006579.3:c.556T > C (Trp186Arg) was found segregating in the affected family. In-silico analysis and molecular docking results supported the pathogenicity of the identified variant. Conclusion Our study expands the mutation spectrum of EBP and adds to the restricted reports of MEND patients. It strengthens the body of evidence that supports the role of EBP in the MEND syndrome phenotype. To our knowledge, this is the first report of this disorder from Pakistan.

Report of a novel missense TDP1 variant in a Pakistani family affected with an extremely rare disorder congenital spinocerebellar ataxia with axonal neuropathy type 1 (SCAN1) - Riaz Ahmad; Filza Sayyad; Muhammad Naeem; Henry Houlden (Molecular Biology Reports, 2025)
Background Spinocerebellar ataxia with axonal neuropathy type 1 (OMIM: 607250) is an extremely rare autosomal recessive disorder caused by a mutation in the tyrosyl-DNA phosphodiesterase 1 ( TDP1) gene. Only a single missense variant (p.His493Arg) in this gene has been reported. This variant was found in three Arab families with a possible common founder effect. Methods and Results We report a female patient born to a consanguineous Pakistani family segregating autosomal recessive spinocerebellar ataxia with axonal neuropathy type 1. The patient presents additional clinical features distinct from previously reported Arab families including congenital onset of the disease. We performed whole exome sequencing with the patient’s DNA and identified a novel missense variant (NC_000014.9:g.89991982C > T; p.His478Tyr) in exon 13 of the TDP1 gene. Sanger sequencing was performed to verify the autosomal recessive segregation of the p.His478Tyr variant in the family. Conclusion The current study expands both the clinical and mutation spectrum of the TDP1 associated spinocerebellar ataxia with axonal neuropathy type 1 and increases the body of evidence that supports the pathogenic role of TDP1 in cerebellar ataxias with peripheral neuropathy.

Exome sequencing in a Pakistani male infertility cohort: perspective on molecular diagnosis, genetic heterogeneity, and diagnostic yield - Dapeng Zhou; Ambrin Fatima; Afrasiab Ahmed; Tehseen Ullah Khan Afridi; Haq Nawaz Khan; Mussarat Ashraf; Muhammad Naeem; Syed Babar Jamal; Ishtiaq Hassan; Erica E. Davis; Feng Zhang; Rehana Rehman; et al. (Molecular Genetics and Genomics, 2025)

Sustainable Modeling and Optimization of Green-Synthesized ZnO Nanoparticles and Humic-Citric Amendments: Enhancing Growth, Nutrient Uptake, and Flowering of Solidago in Saline Soils - Khaled M.A. Ramadan; Hisham Mohamed; Muhammad Munir; Samah M. Youssef; Hossam S. El-Beltagi; Hani S. Saudy; Sallah A. Al Hashedi; Muhammad Naeem Sattar; Ahmed S. Abdelbaky; Ibrahim A. A. Mohamed; Mohamed M. El-Mogy; Wael M. Semida; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Manure-enriched Acidic Phosphate Fertilizer Improves Paddy Yield Over the Conventional Phosphate Fertilizers on a Calcisol - Ayesha Siddique; Muhammad Akhtar; Muhammad Saleem; Tahir Hussain Awan; Asif Naeem (Journal of Soil Science and Plant Nutrition, 2025)

Deep Learning Ensemble and Multi-Criteria GIS for High-Fidelity Rooftop Solar Potential Mapping - Muhammad Kamran Lodhi; Yumin Tan; Yang Li; Muhammad Nouman Khan; Shahid Naeem (Journal of Geovisualization and Spatial Analysis, 2025)
Accurately mapping urban rooftop solar potential is essential for cities like Amsterdam that are pursuing net-zero emissions. This study presents an innovative framework that combines high-resolution geospatial data with an advanced deep learning ensemble to identify existing solar panels and untapped suitable rooftop areas. The predictions from a meticulously trained ensemble of deep learning models were integrated using both simple and performance-weighted majority voting. The weighted ensemble achieved an accuracy of 0.95, an F1 score of 0.91, and a Matthews correlation coefficient of 0.88, outperforming individual models. Rooftop suitability was assessed using a multi-criteria approach, which incorporated a high-resolution digital surface model (DSM) to derive slope, aspect, and solar irradiation. A novel solar irradiation model was developed that enhanced the precision of yield estimates by adjusting atmospheric transmissivity and diffuse fraction based on monthly cloud cover data from Amsterdam. This framework provides district-wise spatiotemporal solar irradiation and photovoltaic yield estimates. Based on our model estimates, current installations have a potential of 140 GWh annually, while there is a significant untapped potential of 1276 GWh on suitable rooftops. These detailed insights can help urban planners optimize solar energy deployment and support the city’s carbon neutrality goal by 2050. Graphical Abstract

Dissecting Genetic Variability and Combining Ability for Salt Tolerance in Rice Based on Morpho-Physiological Traits - Zeeshan Ali; Muhammad Naeem; Iqra Rafiq (Journal of Crop Health, 2025)

Retraction Note: Pharmacological support to anti-arthritic prospective of physostigmine: a new approach - Haseeb Ahsan; Ihtisham Haider; Muhammad Naveed Mushtaq; Muhammad Naeem Qaisar; Farwa Naqvi; Awais Asif (Inflammopharmacology, 2025)

Optimizing aquaculture sustainability: Microalgae-based co-culture systems for aquaculture wastewater treatment and pollution reduction - Javaeria Maqsood Gill; Syed Makhdoom Hussain; Shafaqat Ali; Ameer Fawad Zahoor; Abdulrahman Alasmari; Muhammad Munir; Eman Naeem; Muhammad Amjad; Zeeshan Yousaf; Muhammad Faisal (Algal Research, 2025)

Bacterial community of the shrimp (Litopenaeus vannamei) gut and its relationship with water quality in a recirculating aquaculture system (RAS) - Arslan Emmanuel; Bilal Raza; Muhammad Naeem Ramzan; Zhongming Zheng (Aquaculture International, 2025)

Identification of novel VPS4 inhibitors using multi-tiered structure based virtual screening - Abdus Samad; Mussa Yussuf Khamis; Peng Jin; Muhammad Naeem Toor; Yinglan Yu; Lei Luo; Hao Shao (Molecular Diversity, 2025)

Fluorescence spectroscopy as a tool for differentiating methicillin resistance in clinical isolates of Staphylococcus aureus - Rabia Anjum; Sana Imtiaz; Tahseen Rafaqat; Naeem Akhtar; Muhammad Saleem; Muhammad Umar (Journal of Fluorescence, 2025)

FinTech, environmental innovation, and social capital drive environmental and economic development in Asia - Yun Li; Muhammad Naeem Shahid; Muhammad Umar Islam; Muhammad Ishtiaq; Falak Sher (Environment, Development and Sustainability, 2025)

Aspergillus spp and aflatoxins in Pakistani rice: A case study on the decontamination effect of accelerated aging and improved storage practices - Iqra Naeem; Amir Ismail; Yun Yun Gong; Muhammad Riaz; Aneela Hameed; Mubashir Aziz; Asif Mahmood; Waheed Al Masry; Muhammad Latif; Sher Ali; Carlos Augusto Fernandes de Oliveira (Toxicon, 2025)

Water level forecasting in coastal cities using a hybrid deep learning approach - Abdur Rahman; M. Hafidz Omar; Tahir Mahmood; Nasir Abbas; Muhammad Riaz; Naeem Ramzan (Science of The Total Environment, 2025)

Zinc-based nanoparticles improved the growth, chlorophyll, osmoregulation and ions relations of sunflower under combined shade and drought stress - Maria Tariq; Aasma Tufail; Muhammad Bilal Hafeez; Mafia Shoukat; Naeem Ahmad; Shahid Iqbal; Maqsood ul Hussan; Tayyaba Tariq; Muhammad Kamran; Muhammad Ahsan; Fahd Rasul; Noreen Zahra (Biocatalysis and Agricultural Biotechnology, 2025)

Efficacy and safety of cyclosporine in colitis: An updated meta-analysis of randomized control trials (1998 to 2024) - Aqsa Mehreen; Faiza Batool; Uzma Azeem Awan; Shaista Aslam; Adnan Haider; Muneeb Ullah; Jin-Wook Yoo; Rida Fatima Saeed; Muhammad Naeem (Inflammopharmacology, 2025)

Risk assessment of synthetic insecticides and botanicals to Western honey bee, Apis mellifera (Hymenoptera: Apidae) - Sami Ullah; Naeem Iqbal; Muhammad Sohail Shahzad; Hafiz Azhar Ali Khan; Khalid Rafiq; Allah Ditta Abid; Mudssar Ali; Shafqat Saeed (International Journal of Tropical Insect Science, 2025)

Unraveling the potential of zinc oxide nanoparticles on alleviating arsenic toxicity in wheat (Triticum aestivum L.) varieties: a comparative assessment of histology and phenomics - Eimaan Aamer; Muhammad Saeed; Faroha Liaqat; Muhammad Ramzan Khan; Muhammad Kashif Naeem; Ghazala Mustafa; Riffat Naseem Malik (Physiology and Molecular Biology of Plants, 2025)

Epigenetic horizons in aquaculture: unlocking sustainable fish production - Khalid Hussain; Syed Makhdoom Hussain; Shafaqat Ali; Ameer Fawad Zahoor; Ebru Yilmaz; Abdulrahman Alasmari; Muhammad Munir; Muhammad Zubair-ul-Hassan Arsalan; Adan Naeem (Fish Physiology and Biochemistry, 2025)

Effectiveness of curcumin for anticancer activity by surface functionalized nickel and manganese ferrites - Huzaifa Hanif; Shahzad Hussain; Muhammad Naeem Ahmed; Muhammad Waseem (Natural Product Research, 2025)

Bridging sustainable finance, AI, and clean technology amid economic shocks: How are they connected in median and extreme conditions? - Sinda Hadhri; Faisal Nazir Zargar; Muhammad Abubakr Naeem; Faten Chibani (Journal of Environmental Management, 2025)

Corrigendum to “Production of manganese telluride-based manganese oxide nano-composite works as a catalyst for effective oxygen evolution reaction” [363 (2024) 130919] - Zainab M. Almarhoon; Karam Jabbour; Sumaira Manzoor; Syed Imran Abbas Shah; Muhammad Faheem Ashiq; Muhammad Yousaf Ur Rehman; Muhammad Fahad Ehsan; Muhammad Najam-ul-Haq; Muhammad Naeem Ashiq (Fuel, 2025)

Retraction Note: Assessment of antiarthritic potential of Asparagus dumosus using formaldehyde and CFA-induced arthritic models in rats via modulation of oxidative stress biomarkers and mRNA expression of IL-1b, IL-6, RANKL, OPG, TNF-α and COX-2 - Nimra Nazar; Malik Hassan Mehmood; Rida Siddique; Muhammad Naeem Faisal (Inflammopharmacology, 2025)

Efficacy and safety of colchicine post myocardial infarction: a systematic review, meta-analysis and meta-regression analysis of randomized clinical trials - Farhan Naeem; Shehroze Tabassum; Muhammad Burhan; Elsayed Balbaa; Ahmed Ibrahim; Shrouk Ramadan; Usama Qamar; Fatima Saeed; Mohamed Abuelazm; Dmitry Abramov; Timir K. Paul; Yasar Sattar (European Journal of Clinical Pharmacology, 2025)

Identification of a Novel GRM1 Frameshift Variant in Two Pakistani Families Broadens the Genetic Landscape of Ultra-Rare Spinocerebellar Ataxia Type 13 - Riaz Ahmad; Mina Zamani; Eleanor Self; Salah Ud Din Shah; Muhammad Naeem; Henry Houlden (The Cerebellum, 2025)
Autosomal recessive spinocerebellar ataxia 13 (SCAR13) is an extremely rare neurodegenerative disorder characterized by psychomotor delay, ranging from mild to severe intellectual disability with absent or poor speech development, nystagmus and stance ataxia. If ambulation is achieved, affected subjects often exhibit gait ataxia. Additionally, epilepsy and polyneuropathy have been reported in some patients. SCAR13 is caused by pathogenic variants in the GRM1 gene, which is predominantly expressed in the cerebellum, with lower levels in the other parts of the brain. To date, only seven reports of this rare ataxia have been published globally. Our study aimed to investigate clinical and mutation spectrum of GRM1 -associated SCAR13 disorder in nine patients of two consanguineous Pakistani families (designated here to as NP35 and NP36). We performed whole exome sequencing in the probands of the two families followed by Sanger sequencing to test variant segregation. We identified a novel GRM1 frameshift variant (NM_001278064.2):c.3525_3529del; p.(Asn1176IlefsTer71) in both families as a cause of SCAR13. It was classified as a variant of uncertain significance (PM2: pathogenic moderate 2 and PVS1: pathogenic very strong 1) according to the ACMG guidelines. The novel variant exhibited clinical heterogeneity in the two families. Moreover, scoliosis was observed in all four patients of the family NP35, a feature previously documented in only one patient worldwide. Our study expands the limited mutation spectrum of the GRM1 -associated SCAR13. Next-generation sequencing plays a pivotal role in the elucidation of inherited neurological disorders and in a better understanding of the convergent phenotypes.

Trends in extracting protein from microalgae Spirulina platensis , using innovative extraction techniques: mechanisms, potentials, and limitations - Samran Khalid; Kashmala Chaudhary; Humera Aziz; Sara Amin; Hassan Mehmood Sipra; Sadia Ansar; Husnain Rasheed; Muhammad Naeem; Helen Onyeaka (Critical Reviews in Food Science and Nutrition, 2025)

Organic solvent assisted hydrothermal processing of cooked rice to get insights into the evolution of chemical structure of hydrochar - Sobia Kousar; Kanwal Javed; Bushra Begum; Muhammad Mahboob Naeem; Shu Zhang; Xun Hu (Waste Management, 2025)

Molecular detection, epidemiology and phylogenetic evaluation of Babesia ovis in apparently healthy goats - Asia Taqddus; Muhammad Naeem; Hira Muqaddas; Ceylan Ceylan; Onur Ceylan; Ferda Sevinc; Maryam Rahravani; Meysam Moravedji; Alireza Sazmand; Furhan Iqbal (Research in Veterinary Science, 2025)

The role of green finance, energy transition, and digitalization in OECD greenhouse gas emissions - Shahzad Alvi; Imtiaz Ahmad; Shahzada M. Naeem Nawaz; William Connell; Muhammad Khalid Anser; Mehboob Ul Hassan (Journal of Cleaner Production, 2025)

How Does Corporate Governance Deviance Impact Sustainability in Family Firms? A Stakeholder Perspective - Irfan Saleem; Muhammad Naeem; Muhammad Haseeb; Hao Ji; Said Al Fazari (Circular Economy and Sustainability, 2025)

Resistance development, cross-resistance, and inheritance patterns in clothianidin and triazophos resistant strains of Oxycarenus hyalinipennis - Rabia Saeed; Naeem Abbas; Muhammad Akmal; Jam Nazir Ahmad (Crop Protection, 2025)

The compound Bacillus and sea purslane (Sesuvium portulacastrum) enhanced aquaculture wastewater treatment efficiency: Insights from a study on microbial community distributions - Hongmei Yuan; Junxian Li; Haihang Wang; Regan Nicholaus; Muhammad Naeem Ramzan; Wen Yang; Zhongming Zheng; Yangcai Wang (Aquaculture, 2025)

Strigolactone (GR24) regulates fruit ripening in yft3 tomatoes by altering ABA biosynthesis - Muhammad Naeem; Rong Han; Anran Xu; Xuemeng Shan; Lingxia Zhao (Plant Science, 2025)

Elucidating the synergistic activity of biocontrol agents in combating Xanthomonas citri pv. malvacearum and promoting of physio-chemical responses in cotton - Usman Arshad; Yaxing Feng; Muhammd Raheel; Waqas Ashraf; Muhammad Amjad Ali; Iqra Naeem; Kexin Liu (Physiological and Molecular Plant Pathology, 2025)

Evaluating the efficacy of nano-cyclosporine A in mice model of ulcerative colitis: a meta-analysis - Aqsa Mehreen; Faiza Batool; Uzma Azeem Awan; Nadia Shabnam; Adnan Haider; Shaista Aslam; Madiha Ghazanfar; Fakhar Ud-Din; Muhammad Irfan Siddique; Muhammad Naeem; Rida Fatima Saeed (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Transcriptome and Physiological Analyses Unravel Chromium Stress Tolerance Mechanism in Brassica napus L. - Iram Batool; Ahsan Ayyaz; Kangni Zhang; Fakhir Hannan; Yongqi Sun; Tongjun Qin; Habib Ur Rehman Athar; Muhammad Shahbaz Naeem; Muhammad Ahsan Farooq; Weijun Zhou (Journal of Plant Growth Regulation, 2025)

Dual colorimetric sensing of Hg(II) and Fe(III) using sulfanilamide-stabilized silver nanoparticles and evaluating their photodegradation and antibacterial properties - Maria Kanwal; Muhammad Sher; Azhar Abbas; Shoaib Akhtar; Abu Bakar Siddique; Muhammad Naeem ul Hasan; Nasir Assad; Hassan A. Alhazmi; Hatem M.A. Amin (Journal of Water Process Engineering, 2025)

Decolorization of Dye-Loaded Textile Wastewater: Elucidating the Potential of Chlorella sorokiniana Strain HIN-3 and Effect of Effluent Characteristics - Hadeeqa Arshad; Muhammad Imran; Muhammad Ashraf; Asif Naeem; Muhammad Atif Riaz (Water, Air, & Soil Pollution, 2025)

Mitigation Potential of Green-Zinc Oxide Nanoparticles for Nickel (Ni) Stress in Watermelon Plants: Regulation of Cellular Oxidative Stress Metabolism and Reduction in Ni Translocation - Ahlam Khalofah; Muhammad Qaisar Naeem Khan; Hafiz Saqib Hayat (Journal of Soil Science and Plant Nutrition, 2025)

Creating a novel engineered tobacco chassis with downregulated expression of β-1,2-xylosyltransferase - Rong Han; Anran Xu; Yangzhong Wang; Jing Cao; Muhammad Naeem; Weihua Zhao; Lingxia Zhao (Journal of Plant Biochemistry and Biotechnology, 2025)

Exogenous applications of humic acid and salicylic acid differentially affect biomass accumulation and production of rare pharmacologically active withanolides in in vitro cultures of Withania coagulans - Mehnaz Khanum; Muhammad Uzair Javed; Sannia Batool; Gouhar Zaman; Muhammad Naeem Bajwa; Anisa Andleeb; Laurine Garros; Samantha Drouet; Duangjai Tungmunnithum; Christophe Hano; Bilal Haider Abbasi; Nathalie Giglioli-Guivarc’h (Plant Biosystems, 2025)

Occurrence of aflatoxins and effect of preventive practices to inhibit fungal growth and aflatoxin production in leftover flat bread/chapati used as animal feed and stored in Pakistani dairy farms - Mavra Amin; Amir Ismail; Iqra Naeem; Usama Nasir; Muhammad Riaz; Yun Yun Gong; Sher Ali; Michael N. Routledge; Amna Iqbal; Asifa Saif; Carlos Augusto Fernandes Oliveira (Journal of Stored Products Research, 2025)

Cation-induced phase transformation in PVDF for efficient energy harvesting - Dinku Hazarika; Jiaqi Lu; Jiafeng Ni; Chuanrui Chen; Muhammad Naeem Shah; Liangquan Xu; Jianhui Wu; Kaihang Zhang; Jie Li; Xinyu Cai; Rui Wan; Hao Jin; et al. (Chemical Engineering Journal, 2025)

Molecular prevalence and genetic diversity of Toxoplasma gondii in free ranging Asil hen (Gallus gallus domesticus) - Muhammad Naeem; Anees Ur Rehman; Umme Habiba; Zia Ur Rehman; Hira Muqaddas; Amna Aqdas; Turki M. Dawoud; Mohammed Bourhia; Afshan Khan; Adil Khan; Furhan Iqbal (Tropical Animal Health and Production, 2025)

Ecotoxicological investigation of arsenic contamination within the water-soil-fruit-human continuum - Muhammad Shafique Khalid; Nimra Farooq; Muhammad Amjad; Muhammad Shahid; Muhammad Imran; Samina Khalid; Hafiz Faiq Bakht; Ghulam Mustafa Shah; Muhammad Asif Naeem; Ghulam Abbas; Behzad Murtaza (Environmental Geochemistry and Health, 2025)

Is There Any Role of Zinc and Copper in Severity and Progression of Osteoarthritis? A Review - Umaima Cheema; Meeram Noor; Hurain Naeem; Mahnoor Arfan; Abdul-Rehman Azam; Shamikha Cheema; Hafiz Muhammad Haris; Muhammad Raza (Biological Trace Element Research, 2025)

Diffused sunlight assisted green synthesis of silver nanoparticles using Cotoneaster nummularia polar extract for antimicrobial and wound healing applications - Nasir Assad; Muhammad Naeem-ul-Hassan; Muhammad Ajaz Hussain; Azhar Abbas; Muhammad Sher; Gulzar Muhammad; Yasir Assad; Muhammad Farid-ul-Haq (Natural Product Research, 2025)

Exploration of natural colourant of ( Solanum melongena L.) brinjal plant residues for fabric dyeing: a novel approach towards textile processing - Fatima Batool; Naeem Iqbal; Shahid Adeel; Muhammad Azeem; Sahar Mumtaz; Muhammad Hussaan (Natural Product Research, 2025)

Starvation from within: How heavy metals compete with essential nutrients, disrupt metabolism, and impair plant growth - Abdul Wakeel Umar; Muhammad Naeem; Hamad Hussain; Naveed Ahmad; Ming Xu (Plant Science, 2025)

Can central bank green communication reduce carbon emissions of high-energy-consuming firms? - Xu Zhang; Xiao Zhou; Muhammad Abubakr Naeem; Abdul Rauf (Journal of Environmental Management, 2025)

Machine learning-optimized trimetallic MOF integrated nanofibers for precise detection of p-Nitrophenol in agricultural soil - Ayesha Yousaf; Zhihua Zhao; Naeem Akhtar; Muhammad Aizaz; Maham Shahzadi (Chemical Engineering Journal, 2025)

Removal of structurally different textile dyes from water by adsorption onto biomass of non-viable Chlorella sorokiniana strain HIN-3: Kinetics and adsorption isotherms - Hadeeqa Arshad; Muhammad Imran; Muhammad Ashraf; Asif Naeem; Muhammad Atif Riaz (Journal of Applied Phycology, 2025)

Performance and Microbial Community Analysis of Integrated Bioremediation Systems with Photosynthetic Bacteria in Treating Mariculture Tailwater - Muhammad Naeem Ramzan; Ding Shen; Yingzhen Wei; Arslan Emmanuel; Wen Yang; Jinyong Zhu; Yangcai Wang; Zhongming Zheng (Journal of Ocean University of China, 2025)

Nano-revolution in aquaculture: quantum dot innovations for sustainable fisheries - Ulfat Batool; Syed Makhdoom Hussain; Shafaqat Ali; Azhar Rasul; Muhammad Mudassar Shahzad; Adan Naeem; Nisar Ahmad; Muhammad Munir; Abdul Ghafoor; Mohammad Ali Alshehri (Aquaculture International, 2025)

Application of gamma spectrum analysis techniques for natural radioactivity measurements using NaI(Tl) detector - Namra Naeem; Muhammad Sohail; Rizwan Ahmed; Shoaib Masood (Environmental Monitoring and Assessment, 2025)

Effect of soil types and moisture contents on the pupation behavior and adult emergence of Oriental fruit fly, Bactrocera dorsalis (Hendel) (Diptera: Tephritidae) - Muhammad Bilal; Muhammad Mamoon-ur-Rashid; Shabana Wazir; Muhammad Naeem; Asif Ishaq; Rana Muhammad Kaleem Ullah; Abdulrahman Saad Aldawood (International Journal of Tropical Insect Science, 2025)

Correction to: Use of methanolic plant extracts against maize weevil (Sitophilus zeamais) (Curculionidae: Coleoptera) - Muhammad Mamoon-Ur-Rashid; Riaz-ud Din; Muhammad Naeem; Mohamed Farouk Elsadek; Khalid S. Al-Numair; Mohamed S. Sheteiwy; Muhammad Muzammal; Muhammad Yasin (International Journal of Tropical Insect Science, 2025)

A review: Improving aquaculture rearing water quality by removal of nutrients using microalgae, challenges and future prospects - Bilal Raza; Muhammad Naeem Ramzan; Wen Yang (Aquaculture, 2025)

Reviewing the impact of seed-borne mycoflora on mycotoxin accumulation: A threat to lentil genetic resources - Sanam Asif; Momina Nisar; Shakir Ullah; Muhammad Naeem (Toxicon, 2025)

Corrigendum to “Facile synthesis of CuAl2O4/rGO nanocomposite via the hydrothermal method for supercapacitor applications” [Fuel 357(Part A) (2024) 129688] - Shahzaib Khan; Muhammad Usman; Muhammad Abdullah; Muhammad Suleman Waheed; Muhammad Faheem Ashiq; Muhammad Ishfaq Ahmad; Abdulnasser M. Karami; Muhammad Fahad Ehsan; Sumaira Manzoor; Muhammad Naeem Ashiq (Fuel, 2025)

Fish waste biorefinery: A novel approach to promote industrial sustainability - Javaeria Maqsood Gill; Syed Makhdoom Hussain; Shafaqat Ali; Abdul Ghafoor; Muhammad Adrees; Nadia Nazish; Adan Naeem; Eman Naeem; Mohammed Ali Alshehri; Eram Rashid (Bioresource Technology, 2025)

Simultaneous generation of micropores and macropores via synergistic activation of peach wood with K2C2O4 and sodium salts for enlarging pore diameters - Sobia Kousar; Kanwal Javed; Bushra Begum; Muhammad Mahboob Naeem; Shu Zhang; Xun Hu (Biomass and Bioenergy, 2025)

Harnessing the Duo Effect of Plant Growth-Promoting Rhizobacteria and Organic Amendments in the Phytoremediation of Cadmium: a Review - Muhammad Junaid Sarwar; Muhammad Shabaan; Muhaimen Ayyub; Zahir Ahmad Zahir; Hafiz Naeem Asghar; Kashiuf Asif; Aqsa Shareef; Usman Zulfiqar (Journal of Soil Science and Plant Nutrition, 2025)

Isolation and characterization of Aspergillus oryzae from Withania coagulans rhizosphere: metabolite profiling and bioactivity assessment - Sidra Farooq; Asif Mehmood; Nasir Ali; Muhammad Irshad; Anwar Hussain; Naeem Khan (Journal of Plant Biochemistry and Biotechnology, 2025)

RETRACTED ARTICLE: Study of variability, combining ability, genetics and association of different yield related traits in rice (Oryza sativa L.) genotypes - Zeeshan Ali; Muhammad Naeem; Iqra Rafiq; Rao Muhammad Ikram; M. Irfan Akram; Ehab I. Taha; Mounir M. Bekhit; Ozhan Simsek; Tolga Izgu; Temoor Ahmed; Javed Iqbal; Rashid Iqbal (Genetic Resources and Crop Evolution, 2025)

Material selection in the construction industry: a systematic literature review on multi-criteria decision making - Asad Ur Rehman Bajwa; Chandana Siriwardana; Wajiha Shahzad; Muhammad Ahmad Naeem (Environment Systems and Decisions, 2025)
Material choice is critical for ensuring sustainability in the construction industry. Higher carbon embodiment materials contribute towards greenhouse gas emissions and global warming. Decisions on sustainable material selection depend on multiple criteria and variables, thus creating a difficulty to determine the best choice. Multi-Criteria Decision Making (MCDM) techniques have the potential to address this challenge. However, there is limited data that reviews MCDM in choosing building and construction materials. This study aims to review the MCDM methods employed in the sustainable selection of building materials within the construction industry. This systematic literature review (SLR) incorporates meta-analysis and thematic mapping through applying “PRISMA framework” and “ Bibliometrix ”, respectively. This study explored and analysed the records published from 2010 to 2023. This work identified the critical steps for addressing decision problems in building material selection: Establishing criteria, ranking the hierarchy, comparing the selection criteria, and enabling consistency indices. Moreover, one of the most used MCDM methods, i.e. Analytical Hierarchy Process (AHP) was particularly found particularly useful for the selection criteria and weight assignment of variables regarding the waste, recycled, and composite materials. The involvement of several criteria and alternatives raised the complexity of decision problems, leading to the use of Hybrid MCDM. Hybrid MCDM techniques possess the capacity guide informed decisions for the sustainable material selection in the construction industry.

A review of recent advances in green and sustainable technologies for removing 4-nitrophenol from the water and wastewater - Hamza Badamasi; Zain Naeem; Giorgio Antoniolli; Avvaru Praveen Kumar; Abdul Ademola Olaleye; Ismail Shina Sadiq; Naseer Inuwa Durimin-iya; Muhammad Salman Khan (Sustainable Chemistry and Pharmacy, 2025)

Influences of rainfall characteristics on water saving and stormwater control performances of rainwater harvesting systems - Shahbaz Ali; Yan-Fang Sang; Moyuan Yang; Muhammad Naeem (Journal of Environmental Management, 2025)

Corrigendum to “Uniformly dispersed flowery EuZrSe3 derived from the europium-based metal–organic framework for energy storage devices” [Fuel 336 (2023) 127066] - Abdul Ghafoor Abid; Soumaya Gouadria; Sumaira Manzoor; Khadijah Mohammed Saleh Katubi; Karam Jabbour; Muhammad Abdullah; Mehar Un Nisa; Salma Aman; Mohammed Sultan Al-Buriahi; Muhammad Naeem Ashiq (Fuel, 2025)

Chemically modified filter paper with Jaman fruit extract for visual sensing of milk freshness - Muhammad Naeem Shabbir; Adeel Ahmad; Muhammad Aslam; Ayaz Hassan; Hidayat Ullah; Muhammad Akram; Hafiza Fatima Qayum; Fatima Naeem (Food Chemistry, 2025)

Impacts of microplastic accumulation in aquatic environment: Physiological, eco-toxicological, immunological, and neurotoxic effects - Eram Rashid; Syed Makhdoom Hussain; Shafaqat Ali; Muhammad Munir; Abdul Ghafoor; Ebru Yilmaz; Mohammed Ali Alshehri; Danish Riaz; Adan Naeem; Eman Naeem (Aquatic Toxicology, 2025)

First report of Hepatozoon and Lankesterella spp. infections in wild rodents from Pakistan, and their potential impact on blood parameters and oxidative stress markers in vital organs - Maryam Ijaz; Asmat Ullah Khan; Muhammad Ali; Shakir Ullah; Muhammad Naeem; Samir Ibenmoussa; Turki M. Dawoud; Adil Khan; Mourad Ben Said; Furhan Iqbal (Veterinary Research Communications, 2025)

Non-effervescent Polymeric Floating Tablets of Clarithromycin and Pantoprazole: Preparation and In-Vitro Evaluation for Improved Gastric Drug Retention - Fahad Ashraf; Kifayat Ullah Shah; Muhammad Danish Saeed; Faiqa Falak Naz; Fahad Y. Sabei; Tahseen Ahmed; Syed Shafqat Ali Shah; Amir Badshah; Naeem Ur Rehman; Kausar Ali Mahsud (Journal of Pharmaceutical Innovation, 2025)

Major and trace elements geochemistry of Ziarat laterite deposits, Ziarat District, western Pakistan. Implications for source rock materials and ore genesis - Muhammad Ayoub Khan; Andrew C. Kerr; Abdullah; Hikmat Ullah Kakar; Muhammad Tariq; Abdul Naeem (Carbonates and Evaporites, 2025)

Nitrogen and phosphorus-related functional genes enhance nutrient removal in the integrated aquaculture wastewater bioremediation system in the presence of photosynthetic bacteria - Muhammad Naeem Ramzan; Ding Shen; Yingzhen Wei; Arslan Emmanuel; Regan Nicholaus; Wen Yang; Zhongming Zheng (Aquaculture International, 2025)

Monitoring and biochemical characterization of resistance against commonly used insecticides in cotton jassid, Amrasca biguttula (Ishida) from Punjab, Pakistan - Sikandar Hussain; Shoaib Freed; Afifa Naeem; Muhammad Sheraz Shah; Muhammad Zeeshan Nazar; Muhammad Waqas Sumra (International Journal of Tropical Insect Science, 2025)

Nutraceutical Impact of Pumpkin Seed Oil on Expression Levels of EZH-2 and KRT-14 Genes against DSS-induced Inflammatory Bowel Disease in the Rat Model - Asma Mukhtar; Imran Mukhtar; Humaira Muzaffar; Muhammad Naeem Faisal; Kashif ur rehman khan; Laaraib Nawaz; Muhammad Umar Ijaz; Sana Maryam; Muhammad Umair; Haseeb Anwar; Farid S. Ataya; Gaber El-Saber Batiha; et al. (Cell Biochemistry and Biophysics, 2025)
Inflammatory bowel disease is a collection of intestinal disorders that cause inflammation in the digestive tract. Prolonged inflammation in the gastrointestinal tract is a major risk factor for colorectal cancer. The objective of this study was to fucus on gene expression levels of ( KRT-14 ; associated with epithelial cell integrity) and enhancer of zeste homolog-1 ( EZH-2; involved in cellular proliferation) in a IBD rat model in order to rule out impact of nutraceuticals (pumpkin seed oil; PSO) as a complementary approach to conventional treatments of IBD. In the current study, IBD was induced using dextran sodium sulfate (DSS). Following acclimatization, rats were separated into three groups: the negative control, the positive control, and the treatment group. The DSS (1 ml/kg bw) was given to the positive control and treatment groups. Negative control was given only a normal diet. Pumpkin seed oil (PSO) was given orally as a treatment (0.5 ml/kg bw). Blood and colon tissue were obtained on the 5 th , 10 th , 14 th, and 18 th days. Physical parameters, hematology, biochemical assays, gene expression, and histopathology were carried out. After statistical analyses, macroscopic parameters showed significant differences. Biochemical analyses revealed a significant ( P ≤ 0.05) decrease in serum potassium concentrations, total cholesterol, triglycerides, total proteins, total oxidants status, and C-reactive proteins in PSO treated group as compared with positive control. Gene expression levels of KRT-14 and EZH2 were significantly ( P ≤ 0.05) upregulated in PSO treated group as compared to positive control group. Histopathology revealed that pumpkin seed oil preserved the structural integrity of colon.

Use of methanolic plant extracts against maize weevil (Sitophilus zeamais) (Curculionidae: Coleoptera) - Muhammad Mamoon-ur-Rashid; Riaz-ud Din; Muhammad Naeem; Mohamed Farouk Elsadek; Khalid S. Al-Numair; Mohamed S. Sheteiwy; Iram Ijaz; Muhammad Muzammal; Muhammad Yasin (International Journal of Tropical Insect Science, 2025)

Dual-strategy approach for Rhynchophorus ferrugineus control: Endophytic Beauveria bassiana and Bacillus thuringiensis topical application - Muhammad Yasin; Waqas Wakil; Nickolas G. Kavallieratos; Nikoleta Eleftheriadou; Aqsa Naeem; Mirza Abdul Qayyum; Muhammad Asrar; Saleh S. Alhewairini; David Shapiro-Ilan (Crop Protection, 2025)

Photocatalysis mediated removal of diclofenac potassium and energy storage efficiency of bismuth doped cerium tungstate - Ayesha Javaid; Muhammad Imran; Farah Kanwal; Shoomaila Latif; Muhammad Naeem Khan (Journal of Water Process Engineering, 2025)

Both climate and anthropogenic impacts on recent lake area change in the Erdos Plateau - Muhammad Naeem; Yongqiang Zhang; Vahid Nourani; Xiaoqiang Tian; Ping Miao (Journal of Environmental Management, 2025)

Nonstationarity assessment in extreme temperatures and its association with antecedent soil moisture levels across diverse climate zones in Pakistan - Darakshan Naeem; Rizwan Aziz; Mahnoosh Moghaddasi; Ismail Yucel; Muhammad Awais (Theoretical and Applied Climatology, 2025)

Accuracy assessment of potential alternatives to observed precipitation for extremes over complex topography - Muhammad Amjad; Naeem Shahzad; Wajeeh Ul Hassan (Theoretical and Applied Climatology, 2025)

Phytic acid content variation among wheat grain lines and its impact on nutritional quality and growth - Aurangzeb; Nodia Shujaat; Yaseen Ahmad; Muhammad Ikram; Summaira Shaheen; Muhammad Ishaq; Tahir Hameed; Saddam Hussain; Muhammad Romman; Naeem Khan (Vegetos, 2024)

A comprehensive review on advanced trends in treatment technologies for removal of Bisphenol A from aquatic media - Sangeen Waleed; Muhammad Haroon; Naeem Ullah; Mustafa Tuzen; Imran Khan Rind; Ahmet Sarı (Environmental Monitoring and Assessment, 2024)

Effect of differential exposure of UV-C and melatonin stress on the therapeutic potential of bioactive compounds in Moringa oleifera - Muhammad Naeem Bajwa; Gouhar Zaman; Muhammad Asad Ullah; Muhammad Uzair Javed; Anisa Andleeb; Christophe Hano; Bilal Haider Abbasi (South African Journal of Botany, 2024)

Unlocking plant resilience: Advanced epigenetic strategies against heavy metal and metalloid stress - Babar Iqbal; Naveed Ahmad; Guanlin Li; Arshad Jalal; Ali Raza Khan; Xiaojun Zheng; Muhammad Naeem; Daolin Du (Plant Science, 2024)

Machine learning integration with response surface methodology to enhance the removal efficacy of arsenate (V) through sulfur-functionalized mxene coated QPPO/PVA AEM - Nimra Saher Zain; Ibrahim A. Shaaban; Farhan Zafar; Hafiz Muhammad Asif; Muhammad Tariq; Muhammad Ali Khan; Naeem Akhtar; Hafsa Kainat; Mohammad A. Assiri (Journal of Environmental Management, 2024)

Corrigendum to “Coral like gadolinium doped hematite nanostructure as stable and robust electrocatalyst for oxygen evolution water splitting” [Fuel 338 (2023) 127313] - Mehar Un Nisa; Soumaya Gouadria; Sara Houda; Karam Jabbour; Sumaira Manzoor; Salma Aman; Muhammad Najam-Ul-Haq; Muhammad Naeem Ashiq (Fuel, 2024)

Machine learning trained poly (3,4-ethylenedioxythiophene) functionalized carbon matrix suspended Cu nanoparticles for precise monitoring of nitrite from pickled vegetables - Waseem Abbas; Farhan Zafar; Manal F. Abou Taleb; Mavra Ameen; Abdul Sami; Muhammad Ehsan Mazhar; Naeem Akhtar; Muhammad Waseem Fazal; Mohamed M. Ibrahim; Zeinhom M. El-Bahy (Food Chemistry, 2024)

Wood biochar induced metal tolerance in Maize (Zea mays L.) plants under heavy metal stress - Atiqa Zahra; Sadaf Kayani; Asim Shahzad; Tijen Demiral Sert; Hasan Ozcelik; Mingzhou Qin; Muhammad Naeem; Motsim Billah (Environmental Research, 2024)

SNP Markers Associated with Some Root, Stolon, and Tuber Traits in Tetraploid Potatoes (Solanum tuberosum L.) Grown Under Diverse Growing Systems - Muhammad Farhan Yousaf; Ufuk Demirel; Muhammad Naeem; Eric Kuopuobe Naawe; Mehmet Emin Caliskan (Potato Research, 2024)
Numerous loci, environmental factors, and their interactions have an impact on the phenotypic diversity of several significant traits in plants. One approach put forth in recent years for genetic research and finding quantitative trait loci (QTLs) responsible for the specific trait is association mapping. The purpose of the current study was to pinpoint the genetic underpins of significant underground traits in potato. A panel of 192 diverse tetraploid potato genotypes from different countries were grown under different growing conditions (i.e., aeroponics and pot) to study root, stolon and tuber traits. Significant differences ( P ≤ 0.01) were found between the genotypes for all examined traits, and the heritability (H 2 ) of the traits ranged from 0.74 to 0.94. Genotyping was carried out using the SolCAP 25K array. 21,226 polymorphic SNPs were used for association mapping of underground traits. A GWASpoly R package was implemented for the marker-trait associations, and 78 genomic regions were found associated with the traits under investigation.. The history of potato breeding was reflected in LD patterns. The identified SNPs have their putative gene functions related to the root and stolon architecture and tuber growth (i.e., WRKY transcription factor, MAPK, the GTP cyclohydrolase 1 (i.e., GTPCHI ), Glutathionyl-hydroquinone reductase, and pyrophosphate—fructose 6-phosphate 1-phosphotransferase subunit alpha ( PFPase ). The results of the present study provides a framework that could be helpful for future potato breeding programs to increase tuber production and reduce the challenges of feeding the world's population in the years to come.

Revolutionizing cancer care strategies: immunotherapy, gene therapy, and molecular targeted therapy - Aasma Zafar; Muhammad Jawad Khan; Junaid Abu; Aisha Naeem (Molecular Biology Reports, 2024)
Despite the availability of technological advances in traditional anti-cancer therapies, there is a need for more precise and targeted cancer treatment strategies. The wide-ranging shortfalls of conventional anticancer therapies such as systematic toxicity, compromised life quality, and limited to severe side effects are major areas of concern of conventional cancer treatment approaches. Owing to the expansion of knowledge and technological advancements in the field of cancer biology, more innovative and safe anti-cancerous approaches such as immune therapy, gene therapy and targeted therapy are rapidly evolving with the aim to address the limitations of conventional therapies. The concept of immunotherapy began with the capability of coley toxins to stimulate toll-like receptors of immune cells to provoke an immune response against cancers. With an in-depth understating of the molecular mechanisms of carcinogenesis and their relationship to disease prognosis, molecular targeted therapy approaches, that inhibit or stimulate specific cancer-promoting or cancer-inhibitory molecules respectively, have offered promising outcomes. In this review, we evaluate the achievement and challenges of these technically advanced therapies with the aim of presenting the overall progress and perspective of each approach.

The comparative transcriptome analysis of two green super rice genotypes with varying tolerance to salt stress - Nageen Zahra; Muhammad Uzair; Imdad Ullah Zaid; Kotb A. Attia; Safeena Inam; Sajid Fiaz; Rizk M. Abdallah; Muhammad Kashif Naeem; Umer Farooq; Nazia Rehman; Ghulam Muhammad Ali; Jianlong Xu; et al. (Molecular Biology Reports, 2024)

A homozygous missense variant in YTHDC2 induces azoospermia in two siblings - Shixiong Tian; Muhammad Faheem; Humayoon Shafique Satti; Jianqiu Xiao; Feng Zhang; Tahir Naeem Khan; Chunyu Liu (Molecular Genetics and Genomics, 2024)

Exome sequencing in four families with neurodevelopmental disorders: genotype–phenotype correlation and identification of novel disease-causing variants in VPS13B and RELN - Tehseen Ullah Khan Afridi; Ambrin Fatima; Humayoon Shafique Satti; Zaineb Akram; Imran Khan Yousafzai; Wajahat Bin Naeem; Nasreen Fatima; Asmat Ali; Zafar Iqbal; Ayaz Khan; Muhammad Shahzad; Chunyu Liu; et al. (Molecular Genetics and Genomics, 2024)

Synergistic Application of Bacterial Consortium and Organic Amendments Improves the Growth and Seed Quality of Mash Bean (Vigna Mungo L.) - Kashiuf Asif; Muhammad Shabaan; Waqas Mahmood; Hafiz Naeem Asghar; Zahir Ahmad Zahir; Usman Zulfiqar; Sadam Hussain; Walid Soufan (Journal of Soil Science and Plant Nutrition, 2024)

Effect of Plant Growth Regulators On Water Relations, Proximate Composition, and Ascorbate/glutathione Cycle of Late-sown Wheat Under Saline Conditions - Muhammad Bilal Hafeez; Abdul Ghaffar; Noreen Zahra; Naeem Ahmad; Ali Raza; Rui Wang; Jun Li (Journal of Crop Health, 2024)

Efficacy and safety of ticagrelor monotherapy following a brief DAPT vs. prolonged 12-month DAPT in ACS patients post-PCI: a meta-analysis of RCTs - Usama Qamar; Farhan Naeem; Muhammad Talha Maqsood; Maleeka Zamurad Khan; Zeeshan Imtiaz; Fatima Saeed; Neelesh Gupta; Fnu Zafarullah Brohi; Celestine Mkpozi; Yasar Sattar (European Journal of Clinical Pharmacology, 2024)

Spatial modeling of soil erosion potential in the Panjkora Basin, Eastern Hindu Kush: integrated RUSLE and geospatial approaches - Shakeel Mahmood; Nayab Naeem; Muhammad Irfan Ahamad; Zara Tariq; Jinxi Song (Environment, Development and Sustainability, 2024)

Towards safer mining environments: an in-depth review of predictive models for accidents - Kausar Sultan Shah; Hafeez Ur Rehman; Niaz Muhammad Shahani; Barkat Ullah; Naeem Abbas; Muhammad Junaid; Mohd Hazizan bin Mohd Hashim (Arabian Journal of Geosciences, 2024)

Multifaceted roles of zinc nanoparticles in alleviating heavy metal toxicity in plants: a comprehensive review and future perspectives - Muhammad Umair Hassan; Huang Guoqin; Naeem Ahmad; Tahir Abbas Khan; Muhammad Nawaz; Adnan Noor Shah; Adnan Rasheed; Tahani A. Y. Asseri; Sezai Ercisli (Environmental Science and Pollution Research, 2024)

Looking into the thermostable archaeal l-asparaginases - Ayesha Sania; Muhammad Sajed; Naeem Rashid (Biologia, 2024)

Toxicity of different nitrogenous fertilizers on Aedes aegypti larvae (Linnaeus) (Diptera: Culicidae) - Sikander Ali; Unsar Naeem-Ullah; Naeem Iqbal; Hafiz Azhar Ali Khan; Allah Ditta Abid; Muhammad Sohail Shahzad; Shafqat Saeed; Muhammad Usman; Muhammad Nadir Naqqash (International Journal of Tropical Insect Science, 2024)

Greenly synthesized zinc oxide nanoparticles: An efficient, cost-effective catalyst for dehydrogenation of formic acid and with improved antioxidant and phyto-toxic properties - Sami Ullah; Muhammad Shaban; Abu Bakar Siddique; Anam Zulfiqar; Naveed Shahzad Lali; Muhammad Naeem-ul-Hassan; Muhammad Imran Irfan; Muhammad Sher; Muhammad Fayyaz ur Rehman; Ali Hanbashi; Fahad Y. Sabei; Hatem M.A. Amin; et al. (Journal of Environmental Chemical Engineering, 2024)

Anatomical and Ionomics Investigation of Bread Wheat (Triticum aestivum L.) to Decipher Tolerance Mechanisms Under Arsenic Stress - Muhammad Anas; Muhammad Saeed; Kashif Naeem; Munib Ahmed Shafique; Umar Masood Quraishi (Journal of Plant Growth Regulation, 2024)

Gingerol nanoparticles attenuate complete Freund adjuvant-induced arthritis in rats via targeting the RANKL/OPG signaling pathway - Rida Siddique; Faqir Muhammad; Muhammad Naeem Faisal; Bushra Akhtar; Ammara Saleem; Shaneel Kousar; Ali Sharif; Muhammad Saeed; Safwan Muhammad (Inflammopharmacology, 2024)

Nuclear integration of MYB36 and APX-1 genes impart heat tolerance in wheat - Hina Firdous; Arfan Ali; Muhammad Mubashar Zafar; Faiz Ahmad Joyia; Muhammad Hamza; Abdul Razzaq; Muhammad Uzair; Sezai Ercisli; Waqas Shafqat Chattha; Mahmoud F. Seleiman; Naeem Khan; Xuefei Jiang (Functional & Integrative Genomics, 2024)

Chromium uptake and its impact on antioxidant level, photosynthetic machinery, and related gene expression in Brassica napus cultivars - Iram Batool; Ahsan Ayyaz; Kangni Zhang; Fakhir Hannan; Yongqi Sun; Tongjun Qin; Habib Ur Rehman Athar; Muhammad Shahbaz Naeem; Weijun Zhou; Muhammad Ahsan Farooq (Environmental Science and Pollution Research, 2024)

Alleviated cadmium toxicity in wheat (Triticum aestivum L.) by the coactive role of zinc oxide nanoparticles and plant growth promoting rhizobacteria on TaEIL1 gene expression, biochemical and physiological changes - Adiba Khan Sehrish; Shoaib Ahmad; Muhammad Nafees; Zahid Mahmood; Shafaqat Ali; Wenchao Du; Muhammad Kashif Naeem; Hongyan Guo (Chemosphere, 2024)

CRISPR/Cas-mediated genome editing for efficient tomato breeding: past achievements and future directions - Muhammad Naeem; Wajid Zaman; Saddam Saqib; Asim Shahzad; Saeed ur Rahman; Naveed Ahmad (South African Journal of Botany, 2024)

Metabolites-induced co-evolutionary warfare between plants, viruses, and their associated vectors: So close yet so far away - Naveed Ahmad; Hamad Hussain; Muhammad Naeem; Saeed ur Rahman; Khalid Ali Khan; Babar Iqbal; Abdul Wakeel Umar (Plant Science, 2024)

Control efficacy of isolates of Aspergillus nidulans and Aspergillus fumigatus against three destructive insect pests of stored grain - Hafiz Azhar Ali Khan; Tiyyabah Khan; Naeem Iqbal; Waheed Anwar; Muhammad Ali (Journal of Stored Products Research, 2024)

Sorghum's potential unleashed: A comprehensive exploration of bio-energy production strategies and innovations - Muaz Ameen; Athar Mahmood; Ahmad Naeem Shahzad; Muhammad Anjum Zia; Muhammad Mansoor Javaid (Bioresource Technology Reports, 2024)

Ecofriendly Approach for the Determination of Selected Aldehydes by Fluorescence Quenching of L-Tryptophan - Muhammad Naeem Khan; Syeda Qandeel Wajid Kazmi (Journal of Fluorescence, 2024)

Tailoring structural and optical properties of Cu(II)-induced MgAl2O4 nanoparticles and their response to toxic dyes under solar illumination - Muhammad Javed; Naeem Akbar; Ayaz Arif Khan; Asad Masood; Naeem Ahmed; Muhammad Junaid Khan; Nisar Ahmed; Said Nasir Khisro; Muhammed Ali Shaikh Abdul Hameed (Environmental Science and Pollution Research, 2024)

Quantification and polymeric characterization of microplastics in composts and their accumulation in lettuce - Aamna Naeem; Muhammad Ansar Farooq; Muhammad Shafiq; Muhammad Arshad; Aamir Alaud Din; Abdulrahman Ali Alazba (Chemosphere, 2024)

Exploring the efficacy of plant growth promoters in nutrient acquisition and antioxidant defense responses of late sown wheat under saline conditions - Muhammad Bilal Hafeez; Abdul Ghaffar; Noreen Zahra; Naeem Ahmad; Wahidah H. Al-Qahtani; Pankaj Sharma; Azamal Husen; Jun Li (South African Journal of Botany, 2024)

Solid mineral development and Chinese economic growth: Role of technological advancement - Weihan Du; Yi Wei; Muhammad Abubakr Naeem (Resources Policy, 2024)

Revisiting the nexus between financialization and natural Resource efficiency through the lens of financial development and green industrial optimization - Javaria Hameed; Chunhui Huo; Gadah Albasher; Muhammad Abubakr Naeem (Journal of Cleaner Production, 2024)

Unveiling drastic influence of cross-interactions in hydrothermal carbonization of spirulina with cellulose, lignin or poplar on nature of hydrochar and activated carbon - Stelgen Inkoua; Chao Li; Muhammad Rashid; Muhammad Mahboob Naeem; Shu Zhang; Wenran Gao; Mortaza Gholizadeh; Xun Hu (Journal of Environmental Management, 2024)

Integrative approach to the biochemical, and toxicological fingerprinting of Polygonum glabrum.: A computational and experimental synergy for a medicinal food plant - Sumera Hanif; Muhammad Faisal Nadeem; Haji M. Shoaib Khan; Muhammad Naeem; Anjum Khursheed; Abdulwahab Alamri; Mhdia Elhadi Osman; Adel Alghamdi; Nasrin E. Khalifa; Marcello Locatelli; Syafiq Asnawi Zainal Abidin (Food Bioscience, 2024)

Maleated Hydroxyethyl Cellulose for the Efficient Removal of Cd(II) Ions from an Aqueous Solution: Isothermal, Kinetic and Regeneration Studies - Fatima Khan; Abu Bakar Siddique; Muhammad Imran Irfan; Muhammad Naeem ul Hassan; Muhammad Sher; Hassan A. Alhazmi; Abdulrahman N. Qramish; Hatem M. A. Amin; Rahman Qadir; Azhar Abbas (Water, Air, & Soil Pollution, 2024)

Silicon oxide nanoparticle mitigated the vanadium toxicity in Cucumber (Cucumis sativus L.) - Muhammad Mohsin Altaf; Sahrish Ashraf; Muhammad Qaisar Naeem Khan; Sibgha Noreen; Muhammad Anwar; Rafa Almeer; Rattandeep Singh; Atique ur Rehman (South African Journal of Botany, 2024)

Aflatoxins in the rice production chain: A review on prevalence, detection, and decontamination strategies - Iqra Naeem; Amir Ismail; Muhammad Riaz; Mubashir Aziz; Kashif Akram; Muhammad A. Shahzad; Mavra Ameen; Sher Ali; Carlos A.F. Oliveira (Food Research International, 2024)

Enhancing productivity and profitability of quinoa through optimization of plant spacing and weeding regimes - Muhammad Kashif Hanif; Irfan Afzal; Muhammad Kashif Munir; Abdul Khaliq; Hafiz Naeem Asghar (Field Crops Research, 2024)

Fintech and environmental efficiency: The dual role of foreign direct investment in G20 nations - Myne Uddin; Abu Bakkar Siddik; Zhao Yuhuan; Muhammad Abubakr Naeem (Journal of Environmental Management, 2024)

Photocatalytic and biological efficacy of Carissa macrocarpa fruit extract-mediated one-pot synthesized ternary metal oxide dual S-scheme heterojunction - Abu Bakar Siddique; Muhammad Ashraf Shaheen; Azhar Abbas; Yasir Zaman; Akbar Ali; Muhammad Naeem-ul-Hassan; Javed Iqbal (Journal of Environmental Chemical Engineering, 2024)

Sunlight-assisted green synthesis of gold nanocubes using horsetail leaf extract: A highly selective colorimetric sensor for Pb2+, photocatalytic and antimicrobial agent - Abdul Waheed Khan; Naveed Shahzad Lali; Fahad Y. Sabei; Muhammad Imran Irfan; Muhammad Naeem-ul-Hassan; Muhammad Sher; Awaji Y. Safhi; Abdullah Alsalhi; Ahmed H. Albariqi; Faroq Kamli; Hatem M.A. Amin; Azhar Abbas (Journal of Environmental Chemical Engineering, 2024)

Phyllospheric Microorganisms and Bean Characteristics Influence Quality of Ten Genotypes of Coffea Arabica - Butian Wang; Xuedong Shi; Mengnan Shi; Meijun Qi; Zhenwei Zhang; Na Yang; Muhammad Dawood; Ahmad Naeem Shahzad; Yu Ge (Journal of Soil Science and Plant Nutrition, 2024)

Exogenous Application of Plant Growth Regulators Improves Economic Returns, Grain Yield and Quality Attributes of Late-Sown Wheat under Saline Conditions - Muhammad Bilal Hafeez; Abdul Ghaffar; Noreen Zahra; Naeem Ahmad; Hira Shair; Muhammad Farooq; Jun Li (International Journal of Plant Production, 2024)

Multiple Transgenic Strategies Positively Regulate Cold-Induced Sweetening in Low Temperature Stored Potato Tubers - Nida Toufiq; Olawale Samuel Adeyinka; Anwar Khan; Shazia Shafique; Nusrat Jahan; Muhammad Umar Bhatti; Rida Khalid; Ayman Naeem; Qamar Abbas; Sobiya Shafique; Bushra Tabassum (Potato Research, 2024)

Untapped potential of food waste derived biochar for the removal of heavy metals from wastewater - Asma Moureen; Muhammad Waqas; Naeem Khan; Fariha Jabeen; Cosimo Magazzino; Nargis Jamila; Dilek Beyazli (Chemosphere, 2024)

Optimal environment control and fruits delivery tracking system using blockchain for greenhouse - Atif Rizwan; Anam Nawaz Khan; Muhammad Ibrahim; Rashid Ahmad; Naeem Iqbal; Do Hyeun Kim (Computers and Electronics in Agriculture, 2024)

Production of manganese telluride-based manganese oxide nano-composite works as a catalyst for effective oxygen evolution reaction - Zainab M. Almarhoon; Karam Jabbour; Sumaira Manzoor; Syed Imran Abbas Shah; Muhammad Faheem Ashiq; Muhammad Yousaf Ur Rehman; Muhammad Fahad Ehsan; Muhammad Najam-ul-Haq; Muhammad Naeem Ashiq (Fuel, 2024)

Explaining urban communities’ adaptation strategies for climate change risk: novel evidence from Rawalpindi, Pakistan - Naeem Ahmed; Muhammad Luqman (Natural Hazards, 2024)

Trapping the genetic variation for yield and yield related attributes in bread wheat under water deficit stress - Hafiz Ghulam Muhu-Din Ahmed; Muhammad Naeem; Yawen Zeng; Aziz Ullah; Ghulam Sabir Hussain; Muhammad Irfan Akram; Amjad Saeed; Noor Fatima; Ibtasam Moeez; Hayssam M. Ali; Nagy S. Radwan; Sezai Ercisli; et al. (Euphytica, 2024)

Assessment of heavy metals level in chicken with indeterminate analysis in localities of Lahore, Pakistan - Naveed Ahmad; Usama Afzal; Ramna Zafar; Muhammad Arslan; Saira Riaz; Shahzad Naseem; Muhammad Naeem; Adeena Fatima; Mubashar Ali; Muhammad Aslam (Environmental Monitoring and Assessment, 2024)

Toxicological profile and potential health concerns through metals and trace elements exposure in brick kiln workers from Lahore, Pakistan - Talha Saeed; Naeem Akhtar Abbasi; Muhammad Talha Zahid; Noor Fatima; Kaleem Ullah; Muhammad Fahim Khokhar (Environmental Geochemistry and Health, 2024)

Digitalization for sustainable buildings: Technologies, applications, potential, and challenges - Muhammad Asif; Ghinwa Naeem; Muhammad Khalid (Journal of Cleaner Production, 2024)

Highly selective and effective oxidation of 5-hydroxymethylfurfural by Co-Ni based electrodeposited bimetallic oxide nanostructures - Ghazala Nawaz; Mahnoor Fatima; Zahoor Ahmad; Khurram Saleem Joya; Mohammed Ali Assiri; Syed Imran Abbas Shah; Farhat Yasmeen; Muhammad Naeem Khan (Fuel, 2024)

Contaminant transport from solid waste dumps: Implications for environmental degradation with a focus on capital territory regions - Muhammad Naeem; Zaki ul Zaman Asam (Environmental Research, 2024)

Assessment of historical and projected changes in extreme temperatures of Balochistan, Pakistan using extreme value theory - Darakshan Naeem; Rizwan Aziz; Muhammad Awais; Sajid Rashid Ahmad (Environmental Monitoring and Assessment, 2024)

Toxicological assessment of dietary exposure of polyethylene microplastics on growth, nutrient digestibility, carcass and gut histology of Nile Tilapia (Oreochromis niloticus) fingerlings - Muhammad Mahmood; Syed Makhdoom Hussain; Pallab K. Sarker; Shafaqat Ali; Muhammad Saleem Arif; Nadia Nazish; Danish Riaz; Nisar Ahmad; Bilal Ahamad Paray; Adan Naeem (Ecotoxicology, 2024)

Leading report of molecular prevalence of tick borne Anaplasma marginale and Theileria ovis in yaks (Bos grunniens) from Pakistan - Muqaddas Nawaz; Rehmat Ullah; Zia Ur Rehman; Muhammad Naeem; Afshan Khan; Mohammed Bourhia; Muhammad Mudassir Sohail; Takbir Ali; Adil Khan; Tanveer Hussain; Furhan Iqbal (Archives of Microbiology, 2024)

Retraction Note: Trends of electronic waste pollution and its impact on the global environment and ecosystem - Rida Akram; Natasha; Shah Fahad; Muhammad Zaffar Hashmi; Abdul Wahid; Muhammad Adnan; Muhammad Mubeen; Naeem Khan; Muhammad Ishaq Asif Rehmani; Muhammadd Awais; Mazhar Abbas; Khurram Shahzad; et al. (Environmental Science and Pollution Research, 2024)

Removal of reactive dyes from textile industrial effluent using electrocoagulation in different parametric conditions of aluminum electrodes - Abdul Mannan Zafar; Asma Naeem; Muhammad Athar Minhas; Muhammad Jamal Hasan; Sania Rafique; Amir Ikhlaq (Total Environment Advances, 2024)

Shining in or fading out: Do precious metals sparkle for cryptocurrencies? - Afsheen Abrar; Muhammad Abubakr Naeem; Sitara Karim; Brian M. Lucey; Samuel A. Vigne (Resources Policy, 2024)

Molecular prevalence of vector borne bacterial pathogens in the blood samples of wild rodent species trapped from Saudi Arabia - Abdul Ghafar; Samia Q. Alghamdi; Abdullah D. Alanazi; Syed Muhammad Zukhruf Qousain; Maryam Ijaz; Muhammad Naeem; Muhammad Ali; Hira Muqaddas; Adil Khan; Furhan Iqbal (Comparative Immunology, Microbiology and Infectious Diseases, 2024)

Optimization and cost analysis evaluation studies of the biodiesel production from waste cooking oil using Na–Si/Ce-500 heterogeneous catalyst - Mshari A Alotaibi; Abdul Naeem; Ihtisham Wali Khan; Muhammad Farooq; Israf Ud Din; Maizat S. Saharun (Biomass and Bioenergy, 2024)

Soil Carbon Mineralization and Aggregate Distribution in Various Tillage Practices of Rice–Wheat Cropping System: A Field and Laboratory Study - Naeem Ahmad; Ahmad Latif Virk; Muhammad Bilal Hafeez; Zheng-Rong Kan; Zujiao Shi; Rui Wang; Hafiz Muhammad Waleed Iqbal; Muhammad Ishaq Asif Rehmani; Xiaoli Wang; Rattan Lal; Jun Li (Journal of Soil Science and Plant Nutrition, 2024)

Silicon-nanoparticles loaded biochar for soil arsenic immobilization and alleviation of phytotoxicity in barley: Implications for human health risk - Muhammad Asif Naeem; Abrar Shabbir; Muhammad Imran; Sajjad Ahmad; Muhammad Shahid; Behzad Murtaza; Muhammad Amjad; Waqas-ud-Din Khan (Environmental Science and Pollution Research, 2024)

Retraction Note: Evaluating toxicity of copper(II) oxide nanoparticles (CuO-NPs) through waterborne exposure to tilapia (Oreochromis mossambicus) by tissue accumulation, oxidative stress, histopathology, and genotoxicity - Khurram Shahzad; Muhammad Naeem Khan; Farhat Jabeen; Nasreen Kosour; Abdul Shakoor Chaudhry; Muhammad Sohail (Environmental Science and Pollution Research, 2024)

Carbon trade-off and energy budgeting under conventional and conservation tillage in a rice-wheat double cropping system - Naeem Ahmad; Ahmad Latif Virk; Abdul-Sattar Nizami; Rattan Lal; Scott X. Chang; Muhammad Bilal Hafeez; Xingyu Guo; Rui Wang; Xiaoli Wang; Hafiz Muhammad Waleed Iqbal; Gadah Albasher; Jun Li (Journal of Environmental Management, 2024)

Facile synthesis of CuAl2O4/rGO nanocomposite via the hydrothermal method for supercapacitor applications - Shahzaib Khan; Muhammad Usman; Muhammad Abdullah; Muhammad Suleman Waheed; Muhammad Faheem Ashiq; Muhammad Ishfaq Ahmad; Abdulnasser M. Karami; Muhammad Fahad Ehsan; Sumaira Manzoor; Muhammad Naeem Ashiq (Fuel, 2024)

Retraction Note: Ameliorative effect of two structurally divergent hydrazide derivatives against DSS-induced colitis by targeting Nrf2 and NF-κB signaling in mice - Ashrafullah Khan; Adnan Khan; Bushra Shal; Abdul Aziz; Sajjad Ahmad; Muhammad Usman Amin; Muhammad Naeem Ahmed; Zia‑ur‑Rehman; Salman Khan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Development and Characterization of Glimepiride-Loaded Polymeric Nanoparticles: Formulation Design and Evaluation - Zaiba Irfan; Muhammad Imran Khan; Muhammad Farhan Sohail; Muhammad Furqan Akhtar; Muhammad Naeem Qaisar; Muhammad Kashif Javed; Fareeha Anwar; Badarqa-tul-Ayesha; Majid Anwar; Aslam Khan; Faizan Akram (Journal of Pharmaceutical Innovation, 2024)

Determination of Salinity Tolerance in Pigmented Rice Genotypes at Seedling Stage - Zeeshan Ali; Muhammad Naeem; Hafiz Ghulam Muhu-Din Ahmed (Journal of Crop Health, 2024)

RETRACTED ARTICLE: Assessment of antiarthritic potential of Asparagus dumosus using formaldehyde and CFA-induced arthritic models in rats via modulation of oxidative stress biomarkers and mRNA expression of IL-1b, IL-6, RANKL, OPG, TNF-α and COX-2 - Nimra Nazar; Malik Hassan Mehmood; Rida Siddique; Muhammad Naeem Faisal (Inflammopharmacology, 2024)

Cancer Stem Cells Niche Regulation Within the Tumor Microenvironment - Zainab Siddiqui; Zaffar Equbal; Naoshad Muhammad; Darksha Usmani; Satya N. Sankhwar; S. Nishat Fatima Rizvi; Abdul Naeem (Current Tissue Microenvironment Reports, 2024)

Beyond contamination: Enhancing plant tolerance to arsenic through phytobial remediation - Saeed ur Rahman; Xinxin Liu; Muhammad Khalid; Asad Rehman; Junfeng Cao; Sadaf-Ilyas Kayani; Muhammad Naeem; Naveed Ahmad; Abid Ali Khan; Muhammad Aamir Manzoor; Chang Zhao; Haoxin Tan; et al. (South African Journal of Botany, 2024)

Mitigating chromium toxicity in rice (Oryza sativa L.) via ABA and 6-BAP: Unveiling synergistic benefits on morphophysiological traits and ASA-GSH cycle - Khairiah Mubarak Alwutayd; Suliman Mohammed Suliman Alghanem; Rahaf Alwutayd; Sameera A. Alghamdi; Nadiyah M. Alabdallah; Rahmah N. Al-Qthanin; Wajiha Sarfraz; Noreen Khalid; Nayab Naeem; Baber Ali; Muhammad Hamzah Saleem; Sadia Javed; et al. (Science of The Total Environment, 2024)

Unveiling the dynamic impact of energy generation on economic sustainability in Canada: A roadmap towards sustainable development - Mohammad Subhan; Muhammad Irfan; Xuen Pan; Gayas Ahmad; Mohd Hammad Naeem; M.N. Zamir (Journal of Cleaner Production, 2024)

Spherical Fe2O3 nanoparticles inhibit the production of aflatoxins (B1 and B2) and regulate total soluble solids and titratable acidity of peach fruit - Mahnoor Akbar; Naeem Ali; Muhammad Imran; Arshad Hussain; Syed Waqas Hassan; Urooj Haroon; Asif Kamal; Farhana; Hassan Javed Chaudhary; Muhammad Farooq Hussain Munis (International Journal of Food Microbiology, 2024)

Scalable synthesis of MOF-derived Nd2O3@C and V2O5@C nanohybrid: Efficient electrocatalyst for OER in alkaline medium - Tauseef Munawar; Ambreen Bashir; Muhammad Shahid Nadeem; Faisal Mukhtar; Sumaira Manzoor; Muhammad Naeem Ashiq; Shoukat Alim Khan; Muammer Koc; Faisal Iqbal (Fuel, 2024)

Comparative taxonomy and evolutionary significance of foliar epidermis in Jasminum L. (Oleaceae) based on light and scanning electron microscopy - Naeem Akhtar; Muhammad Q. Hayat; Umer Habib; Muhammad A. Khan; Saad I. Malik; Hina Hafeez; Adil Hussain; Azhar Hussain; Daniel Potter (Flora, 2024)

Green synthesized silver nanoparticles: Characterization, phytostimulatory impacts, and degradation potential for organic pollutants - Ghania Abbas; Fozia Batool; Ambreen Ahmed; Shabana Wagi; Humaira Yasmeen Gondal; Farah Maqsood; Ehab A. Abdelrahman; Hafiza Komal Naeem; Samia Kanwal; Muhammad Mustaqeem; Allah Ditta (Biocatalysis and Agricultural Biotechnology, 2024)

Characterization of water-deficit tolerance in Upland cotton (Gossypium hirsutum L.) assessing morphological, biochemical, molecular and yield attributes - Muhammad Saeed; Muhammad Naeem; Alia Javed; Shagufta Perveen; Iqra Sajjad; Muhammad Zaid Yousaf; M. Shahid Munir Chohan; Muhammad Riaz; Sana Ullah; Xianliang Song (Acta Physiologiae Plantarum, 2024)

Green synthesis of cobalt ferrite and Mn doped cobalt ferrite nanoparticles: Anticancer, antidiabetic and antibacterial studies - Sabahat Fiaz; Muhammad Naeem Ahmed; Ihsan ul Haq; Syed Wadood Ali Shah; Muhammad Waseem (Journal of Trace Elements in Medicine and Biology, 2023)

Influence of Oxyranylmethanol as a Catalytic Cross-linking Agent over Physiochemical Properties and Pb (II) Adsorption Performance of Resorcinol Formaldehyde Aerogels: a Comparative Study - Faheem Akhter; Abdul Rauf Jamali; Jawad Ahmed; Haris Jawad Arain; Muhammad Junaid Ahsan; Muhammad Naeem Akhtar (Water, Air, & Soil Pollution, 2023)

Physiological and Metabolic Changes in Maize Seedlings in Response to Bisphenol A Stress - Haziq Hussain; Rehan Naeem; Baharullah Khattak; Zia ur Rehman; Niamat Khan; Muhammad Kamran Qureshi; Farah Deeba; Iftikhar Ali; Muhammad Daud Khan (Journal of Soil Science and Plant Nutrition, 2023)

Phosphorous (P)-Solubilizing Rhizobacteria Improve P Availability to Mung Bean via Enhanced Soil Phosphatase Activity and Improve Its Growth - Rabia Khalid; Aqsa Khalid; Muhammad Shabaan; Hafiz Naeem Asghar; Zahir Ahmad Zahir (Journal of Soil Science and Plant Nutrition, 2023)

Engineering of Chlamydomonas reinhardtii chloroplast for mucosal immunotherapeutic against Newcastle disease virus - Sania Naeem; Naila Shahid; Mohsin Ahmad Khan; Saira Azam; Muhammad Saad Bhutta; Ayesha Latif; Aneela Yasmeen; Tahir Rehman Sami Ullah; Abdul Qayyum Rao; Kausar Malik (Journal of Applied Phycology, 2023)

Comparison of As removal efficiency and health risks from aqueous solution using as-synthesized Fe0 and Cu0: modelling, kinetics and reusability - Behzad Murtaza; Asad Ali; Muhammad Imran; Abdullah A. Al-Kahtani; Zeid A. ALOthman; Natasha Natasha; Muhammad Shahid; Noor S. Shah; Muhammad Asif Naeem; Sajjad Ahmad; Ghulam Murtaza (Environmental Geochemistry and Health, 2023)

Influence of Phosphate Solubilizing Bacteria on the Growth of mustard Grown Under Drought Stress Conditions - Farhat Suhail; Aftab Afzal; Laraib Naseer; Aneela Pervaiz; Muhammad Ikram; Summaira Shaheen; Yasir Islam; Naeem Khan (Agricultural Research, 2023)

Pseudomonas fluorescens and L-tryptophan application triggered the phytoremediation potential of sunflower (Heliantus annuus L.) in lead-contaminated soil - Muhammad Tauseef Jaffar; Zain Mushtaq; Abdul Waheed; Hafiz Naeem Asghar; Jianguo Zhang; Jiale Han (Environmental Science and Pollution Research, 2023)

Exogenous melatonin mitigates the adverse effects of drought stress in strawberry by upregulating the antioxidant defense system - Muhammad Qaisar Naeem Khan; Nevzat Sevgin; Humaira Rizwana; Nida Arif (South African Journal of Botany, 2023)

Expression analysis of transcription factor (CBF/DREB) gene and biochemical response of Cannabis sativa to cadmium toxicity and foliar application of molybdenum - Nasir Ali; Fazal Hadi; Muhammad Ali; Asif Mehmood; Mahmoud F. Seleiman; Naeem Khan (South African Journal of Botany, 2023)

Retraction Note: Inhibition of NF-κB signaling and HSP70/HSP90 proteins by newly synthesized hydrazide derivatives in arthritis model - Ashraf Ullah Khan; Amna Khan; Adnan Khan; Bushra Shal; Abdul Aziz; Muhammad Naeem Ahmed; Salman Ul Islam; Hussain Ali; Adeeb Shehzad; Salman Khan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Adsorption potential of orange rind–based nanosorbents for the removal of cadmium(II) and chromium(VI) from contaminated water - Samia Kanwal; Hafiza Komal Naeem; Fozia Batool; Awais Mirza; Ehab A. Abdelrahman; Gulnaz Sharif; Farah Maqsood; Muhammad Mustaqeem; Allah Ditta (Environmental Science and Pollution Research, 2023)

Molecular regulation of antioxidants and secondary metabolites act in conjunction to defend plants against pathogenic infection - Muhammad Usman Akbar; Muhammad Aqeel; Muhammad Shahzad Shah; Ghulam Jeelani; Naeem Iqbal; Ammara Latif; Rehab O. Elnour; Mohamed Hashem; Omar Mahmoud Alzoubi; Talaat Habeeb; Muhammad Qasim; Ali Noman (South African Journal of Botany, 2023)

Asymmetric efficiency in petroleum markets before and during COVID-19 - Muhammad Abubakr Naeem; Saqib Farid; Imran Yousaf; Sang Hoon Kang (Resources Policy, 2023)

Assessment of application of ZnO nanoparticles on physiological profile, root architecture and antioxidant potential of Solanum lycopersicum - Fazal ur Rehman; Najeeba Paree Paker; Mohsin Khan; Nida Zainab; Naeem Ali; Muhammad Farooq Hussain Munis; Muhammad Iftikhar; Hassan Javed Chaudhary (Biocatalysis and Agricultural Biotechnology, 2023)

Multiplex Cas9-based excision of CLCuV betasatellite and DNA-A revealed reduction of viral load with asymptomatic cotton plants - Sana Shakoor; Abdul Qayyum Rao; Sara Ajmal; Aneela Yasmeen; Muhammad Azmat Ullah Khan; Sahar Sadaqat; Naeem Mahmood Ashraf; Felix Wolter; Michael Pacher; Tayyab Husnain (Planta, 2023)

Geology, mineralogy, and geochemistry of Naweoba and Bagh Cyprus-type VMS deposits of the Late Cretaceous Zhob Valley Ophiolites, Pakistan: implications for genesis - Muhammad Ayoub Khan; Thomas Ulrich; Muhammad Ishaq Kakar; Mohamed Metwaly; Abdul Naeem; Shazia Fareed (Arabian Journal of Geosciences, 2023)

Redundant nerve roots indicate higher degree of stenosis in lumbar spine stenotic patients - Karim Rizwan Nathani; Muhammad Danish Barakzai; Hamid Hussain Rai; Komal Naeem; Fatima Mubarak; Haissan Iftikhar; Saad Akhtar Khan; Syed Ather Enam (Acta Neurologica Belgica, 2023)

Arsenic fractionation and speciation in different textured soils supplied with farmyard manure and accumulation by sunflower under alkaline calcareous conditions - Muhammad Awais Piracha; Muhammad Ashraf; Sher Muhammad Shahzad; Sajid Masood; Naeem Akhtar; Rizwana Kausar; Awais Shakoor (Environmental Science and Pollution Research, 2023)

The deteriorating effects of cadmium accumulation on the yield and quality of maize crops - Naila Shah; Muhammad Irshad; Anwar Hussain; Asif Mehmood; Waheed Murad; Muhammad Qadir; Muhammad Awais; Mohib Shah; Naeem Khan (South African Journal of Botany, 2023)

Synthesis, chracterization, and analytical application of silver dopamine magnetic nanomaterial - Rahat Nawaz; Zarayb Hussan; Fahad Ali; Naeem Akhtar; Batool Fatima; Muhammad Najam ul Haq; Awais Bokhari; Salman Raza Naqvi; Mohamed Ouladsmane; Saadat Majeed (Fuel, 2023)

An Application of Rock Phosphate Increased Soil Cadmium Contamination and Hampered the Morphophysiological Growth of Brassica campestris L - Muhammad Usman Khadim; Ghulam Murtaza; Zia Ur Rahman Farooqi; Tajammal Hussain; Naeem Mahmood; Saddam Hussain (Journal of Soil Science and Plant Nutrition, 2023)

Beyond green and red: unlocking the genetic orchestration of tomato fruit color and pigmentation - Muhammad Naeem; Weihua Zhao; Naveed Ahmad; Lingxia Zhao (Functional & Integrative Genomics, 2023)

Food waste: causes and economic losses estimation at household level in Pakistan - Samina Khalid; Aman Ullah Malik; Muhammad Irfan Ullah; Muhammad Shafique Khalid; Hafiz Muhammad Rashad Javeed; Muhammad Asif Naeem; Aqsa Naseer (Environmental Science and Pollution Research, 2023)

Zinc oxide nanoparticles: A unique saline stress mitigator with the potential to increase future crop production - Mahmoud F. Seleiman; Awais Ahmad; Martin L. Battaglia; Hafiz Muhammad Bilal; Bushra A. Alhammad; Naeem Khan (South African Journal of Botany, 2023)

Chitosan decorated zirconium metal-organic framework for collaborative adsorption and photocatalytic degradation of methylene blue and methyl orange - Abdul Naeem; Tooba Saeed; Murtaza Sayed; Bashir Ahmad; Tahira Mahmood; Muhammad Farooq; Fouzia Perveen (Process Safety and Environmental Protection, 2023)

MDM2- an indispensable player in tumorigenesis - Aasma Zafar; Muhammad Jawad Khan; Aisha Naeem (Molecular Biology Reports, 2023)
Murine double minute 2 (MDM2) is a well-recognized molecule for its oncogenic potential. Since its identification, various cancer-promoting roles of MDM2 such as growth stimulation, sustained angiogenesis, metabolic reprogramming, apoptosis evasion, metastasis, and immunosuppression have been established. Alterations in the expression levels of MDM2 occur in multiple types of cancers resulting in uncontrolled proliferation. The cellular processes are modulated by MDM2 through transcription, post-translational modifications, protein degradation, binding to cofactors, and subcellular localization. In this review, we discuss the precise role of deregulated MDM2 levels in modulating cellular functions to promote cancer growth. Moreover, we also briefly discuss the role of MDM2 in inducing resistance against anti-cancerous therapies thus limiting the benefits of cancerous treatment.

Isolation of Endophytic Fungi from Halophytic Plants and their Identification and Screening for Auxin Production and Other Plant Growth Promoting Traits - Muhammad Ikram; Niaz Ali; Gul Jan; Farzana Gul Jan; Rainaz Pervez; Muhammad Romman; Rimsha Zainab; Humaira Yasmin; Naeem Khan (Journal of Plant Growth Regulation, 2023)

Anti-arthritic effects of geranium essential oil loaded chitosan nanoparticles in Freund’s complete adjuvant induced arthritic rats through down-regulation of inflammatory cytokines - Rana Dawood Naseer; Faqir Muhammad; Bilal Aslam; Muhammad Naeem Faisal (Inflammopharmacology, 2023)

Diversity in Elemental Content in Selected Artemisia L. (Asteraceae) Species from Gilgit-Baltistan Region of Pakistan Based on Inductively Coupled Plasma Atomic Emission Spectrophotometry (ICP-AES) - Adil Hussain; Muhammad Sajid; Daniel Potter; Hassam Rasheed; Mujtaba Hassan; Naeem Akhtar; Bashir Ahmad; Syed Ali Imran Bokhari (Biological Trace Element Research, 2023)

Multifunctional catalyst-assisted sustainable reformation of lignocellulosic biomass into environmentally friendly biofuel and value-added chemicals - Muhammad Naeem; Muhammad Imran; Shoomaila Latif; Adnan Ashraf; Nazim Hussain; Grzegorz Boczkaj; Wojciech Smułek; Teofil Jesionowski; Muhammad Bilal (Chemosphere, 2023)

Occurrence and molecular characteristics of pedilanthus leaf curl virus complex from the new hosts fenugreek and night jessamine in Pakistan - Muhammad Naeem Sattar; Fasiha Qurashi; Zafar Iqbal; Hossam S. EL-Beltagi; Muhammad Khurshid (Physiological and Molecular Plant Pathology, 2023)

Bio-fabrication of zinc oxide nanoparticles from Picea smithiana and their potential antimicrobial activities against Xanthomonas campestris pv. Vesicatoria and Ralstonia solanacearum causing bacterial leaf spot and bacterial wilt in tomato - Fazal ur Rehman; Najeeba Paree Paker; Mohsin Khan; Muhammad Naeem; Muhammad Farooq Hussain Munis; Shafiq ur Rehman; Hassan Javed Chaudhary (World Journal of Microbiology and Biotechnology, 2023)

Segmentation of digital rock images using texture analysis and deep network - Shahzad Manzoor; Tehreem Qasim; Naeem Bhatti; Muhammad Zia (Arabian Journal of Geosciences, 2023)

Examining the role of ICT, transportation energy consumption, and urbanization in CO2 emissions in Asia: a threshold analysis - Zakia Batool; Naeem Ahmed; Muhammad Luqman (Environmental Science and Pollution Research, 2023)

Co-application of organic amendments and Cd-tolerant rhizobacteria for suppression of cadmium uptake and regulation of antioxidants in tomato - Muhammad Junaid Sarwar; Zahir Ahmad Zahir; Hafiz Naeem Asghar; Muhammad Shabaan; Muhaimen Ayyub (Chemosphere, 2023)

Climate change adaptation strategies for sustainable water management in the Indus basin of Pakistan - Muhammad Muzammil; Azlan Zahid; Umar Farooq; Naeem Saddique; Lutz Breuer (Science of The Total Environment, 2023)

Multibody constrained dynamics of deepwater Y-method installation system - Naeem Ullah; Menglan Duan; Mac Darlington Uche Onuoha; Asad Syed; Muhammad Sajid; Guomin Sun; Wenda Li (Ocean Engineering, 2023)

Development of Mn-MOF/CuO composites as platform for efficient electrocatalytic OER - Bushra Shabbir; Nidhal Drissi; Karam Jabbour; Abdelaziz Gassoumi; F.F. Alharbi; Sumaira Manzoor; Muhammad Faheem Ashiq; H.A. Alburaih; Muhammad Fahad Ehsan; Muhammad Naeem Ashiq (Fuel, 2023)

Unraveling the functional characterization of a jasmonate-induced flavonoid biosynthetic CYP45082G24 gene in Carthamus tinctorius - Yufei Wang; Zhiling Li; Naveed Ahmad; Xiaoxiao Sheng; Babar Iqbal; Muhammad Naeem; Nan Wang; Fengwei Li; Na Yao; Xiuming Liu (Functional & Integrative Genomics, 2023)

An assessment of rural household vulnerability and resilience in natural hazards: evidence from flood prone areas - Shah Fahad; Mohammad Shakhawat Hossain; Nguyen Thi Lan Huong; Abdelmohsen A. Nassani; Mohamed Haffar; Muhammad Rashid Naeem (Environment, Development and Sustainability, 2023)

Interactive effect of salicylic acid and triacontanol to improve lead stress tolerance in maize (Zea mays L.) - Javed Iqbal; Shagufta Perveen; Abida Parveen; Muhammad Saeed; Sara Zafar; Naeem Iqbal (Arabian Journal of Geosciences, 2023)

Coral like gadolinium doped hematite nanostructure as stable and robust electrocatalyst for oxygen evolution water splitting - Mehar Un Nisa; Soumaya Gouadria; Sara Houda; Karam Jabbour; Sumaira Manzoor; Salma Aman; Muhammad Najam-Ul-Haq; Muhammad Naeem Ashiq (Fuel, 2023)

Chitosan Polymerized Silica Composite as a Potential Silicon Source: Modulation on Antioxidant Enzymes, Ionic Homeostasis, and Grain Quality in Maize Plants Under Na+ Stress - Waqas-ud-Din Khan; Faiza Sharif; Muhammad Asif Naeem; Muhammad Ansar Farooq; Zafar Siddiq; Muhammad Imran (Journal of Plant Growth Regulation, 2023)

Uniformly dispersed flowery EuZrSe3 derived from the europium-based metal–organic framework for energy storage devices - Abdul Ghafoor Abid; Soumaya Gouadria; Sumaira Manzoor; Khadijah Mohammed Saleh Katubi; Karam Jabbour; Muhammad Abdullah; Mehar Un Nisa; Salma Aman; Mohammed Sultan Al-Buriahi; Muhammad Naeem Ashiq (Fuel, 2023)

Development of CuO/CuS/MnO2 ternary nanocomposite for visible light-induced photocatalytic degradation of methylene blue - Muhammad Abdullah; Peter John; Muhammad Naeem Ashiq; Sumaira Manzoor; Muhammad Ishfaq Ghori; Mehar Un Nisa; Abdul Ghafoor Abid; Kashif Younas Butt; Saeed Ahmed (Nanotechnology for Environmental Engineering, 2023)

Staphylococcus Sciuri SAT-17 Facilitated in Vitro Regenerated Sugarcane Plantlets Cultivation in Saline Soil by Harmonizing Oxidative Signaling, Photosynthetic Efficiency and Nutrients Uptake Patterns - Raheel Parvez Abbasi; Muhammad Sohail Akram; Khadija Rafiq; Saadia Basheer; Naeem Iqbal (Journal of Soil Science and Plant Nutrition, 2023)

A comprehensive review on phytochemistry, bioactivity and medicinal value of bioactive compounds of pomegranate (Punica granatum) - Muhammad Modassar Ali Nawaz Ranjha; Bakhtawar Shafique; Lufeng Wang; Shafeeqa Irfan; Muhammad Naeem Safdar; Mian Anjum Murtaza; Muhammad Nadeem; Shahid Mahmood; Ghulam Mueen-ud-Din; Hafiz Rehan Nadeem (Advances in Traditional Medicine, 2023)

Characterization of Azadirachta indica synthesized silver nanoparticles and its toxicity against Dusky cotton bug, Oxycarenus hyalinipennis Costa (Hemiptera:Lygaeidae) - Muhammad Javaid; Unsar Naeem-Ullah; Waheed S. Khan; Shafqat Saeed; Mirza Abdul Qayyum; Muhammad Arslan Khan (International Journal of Tropical Insect Science, 2023)

Explaining the adsorption mechanism of the herbicide 2,4-D and the drug ketoprofen onto wheat husks Fagopyrum esculentum treated with H2SO4 - Chen Yanan; Jawad Ali; Lotfi Sellaoui; Fatma Dhaouadi; Muhammad Naeem; Dison S.P. Franco; Jordana Georgin; Alessandro Erto; Michael Badawi (Chemosphere, 2023)

Recent progress in calcium looping integrated with chemical looping combustion (CaL-CLC) using bifunctional CaO/CuO composites for CO2 capture: A state-of-the-art review - Jian Chen; Lunbo Duan; Yuxin Ma; Yuxin Jiang; Anqi Huang; Hongyu Zhu; Hongyu Jiao; Mingdi Li; Yanbin Hu; Hui Zhou; Yongqing Xu; Felix Donat; et al. (Fuel, 2023)

Defective nickel zirconium oxide mesoporous bifunctional electrocatalyst for oxygen evolution reaction and overall water splitting - Maira Sadaqat; Sumaira Manzoor; Salma Aman; Laraib Nisar; Muhammad Najam-Ul-Haq; Afzal Shah; Ahmed M. Shawky; H. Elhosiny Ali; Muhammad Naeem Ashiq; T.A. Taha (Fuel, 2023)

Investigation of K2CO3-modified CaO sorbents for CO2 capture using in-situ X-ray diffraction - Yongqing Xu; Felix Donat; Cong Luo; Jian Chen; Agnieszka Kierzkowska; Muhammad Awais Naeem; Liqi Zhang; Christoph R. Müller (Chemical Engineering Journal, 2023)

Recent advances in the green synthesis of Betti bases and their applications: a review - Ramsha Iftikhar; Muhammad Kamran; Aleesha Iftikhar; Sadia Parveen; Naila Naeem; Nazia Jamil (Molecular Diversity, 2023)

Polymeric Nanogel for Oral Delivery of the Chemotherapeutic Agent: Fabrication and Evaluation Alongside Toxicological Studies and Histopathological Examination - Humaira Sultana; Muhammad Naeem Aamir; Asadullah Madni; Masood ur Rehman; Afifa Shafiq; Jafir Hussain Shirazi; Sidra Hassan; Sumaira (AAPS PharmSciTech, 2023)

Microwave-assisted sustainable exploration of cocklebur leaves (Xanthium strumarium L.) as a novel source of distinct yellow natural colorant for dyeing cotton fabric - Muhammad Hussaan; Ahmad Raza; Noman Habib; Shahid Adeel; Naeem Iqbal; Muhammad Tariq Javed (Environmental Science and Pollution Research, 2023)

Application of silver nanoparticles synthesized through varying biogenic and chemical methods for wastewater treatment and health aspects - Asima Rasheed; Sabir Hussain; Waseem Mushtaq; Muhammad Zubair; Khadija Siddique; Kotb Attia; Naeem Khan; Sajid Fiaz; Farrukh Azeem; Yinglong Chen (Environmental Science and Pollution Research, 2023)

Opportunities and constraints for cleaner production policy in the developing world: a case study of Sindh Region, Pakistan - Love Kumar; Sohail Ali Naqvi; Matthew J. Deitch; Muhammad Jibran Khalid; Komal Naeem; Arjmand Qayyum Amjad; Avinash Kumar; Tesfay Gebretsadkan Gebremicael; Masood Arshad (Environment, Development and Sustainability, 2023)

Implementing a novel deep learning technique for rainfall forecasting via climatic variables: An approach via hierarchical clustering analysis - Shah Fahad; Fang Su; Sufyan Ullah Khan; Muhammad Rashid Naeem; Kailei Wei (Science of The Total Environment, 2023)

One-pot solvothermal synthesis of highly catalytic Janus transition metal phosphides (TMPs) for high performance OER - Zeenat; Zahoor Ahmad; Adnan Maqbool; Muhammad Asif Hussain; Rami Adel Pashameah; Amber Shahzadi; Nosheen Nazar; Shahid Iqbal; Abdullah K. Alanazi; Muhammad Naeem Ashiq; Hala M. Abo-Dief (Fuel, 2023)

Nickel-based nitrodopamine MOF and its derived composites functionalized with multi-walled carbon nanotubes for efficient OER applications - Sonia Kiran; Ghazala Yasmeen; Zahid Shafiq; Amir Abbas; Sumaira Manzoor; Dilshad Hussain; Rami Adel Pashameah; Eman Alzahrani; Abdullah K. Alanazi; Muhammad Naeem Ashiq (Fuel, 2023)

Nitrogen-rich three-dimensional metal-organic framework microrods as an efficient electrocatalyst for oxygen evolution reaction and supercapacitor applications - Muhammad Imran Anwar; Sumaira Manzoor; Limin Ma; Muhammad Asad; Wenhua Zhang; Zahid Shafiq; Muhammad Naeem Ashiq; Guang Yang (Fuel, 2023)

RETRACTED: Effect of soil texture and zinc oxide nanoparticles on growth and accumulation of cadmium by wheat: a life cycle study - Muhammad Usman; Muhammad Zia-ur-Rehman; Muhammad Rizwan; Tahir Abbas; Muhammad Ashar Ayub; Asif Naeem; Hesham F. Alharby; Nadiyah M. Alabdallah; Basmah M. Alharbi; Muhammad Javid Qamar; Shafaqat Ali (Environmental Research, 2023)

Genome mining, antimicrobial and plant growth-promoting potentials of halotolerant Bacillus paralicheniformis ES-1 isolated from salt mine - Sajid Iqbal; Muhammad Qasim; Hazir Rahman; Naeem Khan; Rehan Zafar Paracha; Muhammad Faraz Bhatti; Aneela Javed; Hussnain Ahmed Janjua (Molecular Genetics and Genomics, 2023)

Nickel toxicity pretreatment attenuates salt stress by activating antioxidative system and ion homeostasis in tomato (Solanum lycopersicon L.): an interplay from mild to severe stress - Muhammad Azeem Subhani; Muhammad Amjad; Muhammad Mohsin Iqbal; Behzad Murtaza; Muhammad Imran; Muhammad Asif Naeem; Ghulam Abbas; Mathias Neumann Andersen (Environmental Geochemistry and Health, 2023)

Air quality index prediction via multi-task machine learning technique: spatial analysis for human capital and intensive air quality monitoring stations - Xin Xiang; Shah Fahad; Myat Su Han; Muhammad Rashid Naeem; Shah Room (Air Quality, Atmosphere & Health, 2023)

Expansion of human amniotic epithelial cells using condition cell reprogramming technology - Aisha Naeem; Muhammad Umer Choudhry; Alex Kroemer; Simone Wahnschafft; Wanxing Cui; Chris Albanese (Human Cell, 2022)
Human amniotic epithelial cells (hAECs) are non-immunogenic epithelial cells that can develop into cells of all three germline lineages. However, a refined clinically reliable method is required to optimize the preparation and banking procedures of hAECs for their successful translation into clinical studies. With the goal of establishing standardized clinically applicable hAECs cultured cells, we described the use of a powerful epithelial cell culture technique, termed C onditionally R eprogrammed Cells (CRC) for ex vivo expansion of hAECs. The well-established CRC culture method uses a Rho kinase inhibitor (Y-27632) and J2 mouse fibroblast feeder cells to drive the indefinite proliferation of all known epithelial cell types. In this study, we used an optimized CRC protocol to successfully culture hAECs in a CRC medium supplemented with xenogen-free human serum. We established that hAECs thrive under the CRC conditions for over 5 passages while still expressing pluripotent stem markers (OCT-4, SOX-2 and NANOG) and non-immunogenic markers (CD80, CD86 and HLA-G) suggesting that even late-passage hAECs retain their privileged phenotype. The hAECs-CRC cells were infected with a puromycin-selectable lentivirus expressing luciferase and GFP (green fluorescent protein) and stably selected with puromycin. The hAECs expressing GFP were injected subcutaneously into the flanks of Athymic and C57BL6 mice to check the tolerability and stability of cells against the immune system. Chemiluminescence imaging confirmed the presence and viability of cells at days 2, 5, and 42 without acute inflammation or any tumor formation. Collectively, these data indicate that the CRC approach offers a novel solution to expanding hAECs in humanized conditions for future clinical uses, while retaining their primary phenotype. Graphical abstract

Global energy markets connectedness: evidence from time–frequency domain - Mobeen Ur Rehman; Muhammad Abubakr Naeem; Nasir Ahmad; Xuan Vinh Vo (Environmental Science and Pollution Research, 2022)

An overview of genome-wide association mapping studies in Poaceae species (model crops: wheat and rice) - Muhammad Abu Bakar Zia; Muhammad Farhan Yousaf; Arslan Asim; Muhammad Naeem (Molecular Biology Reports, 2022)

Naturally occurring plant-based anticancerous candidates as prospective ABCG2 inhibitors: an in silico drug discovery study - Mahmoud A. A. Ibrahim; Alaa H. M. Abdelrahman; Esraa A. A. Badr; Nahlah Makki Almansour; Othman R. Alzahrani; Muhammad Naeem Ahmed; Mahmoud E. S. Soliman; Mohamed Ahmed Naeem; Ahmed M. Shawky; Peter A. Sidhom; Gamal A. H. Mekhemer; Mohamed A. M. Atia (Molecular Diversity, 2022)
ATP-binding cassette transporter G2 (ABCG2) is an efflux transporter related to the clinical multidrug resistance (MDR) phenomenon. Identifying ABCG2 inhibitors could help discover extraordinary curative strategies for carcinoma remediation. Hitherto, there is no medication drug inhibiting ABCG2 transporter, notwithstanding that a considerable number of drugs have been submitted to clinical-trial and investigational phases. In the search for unprecedented chemical compounds that could inhibit the ABCG2 transporter, an in silico screening was conducted on the Naturally Occurring Plant-based Anticancer Compound-Activity-Target (NPACT) database containing 1574 compounds. Inhibitor-ABCG2 binding affinities were estimated based on molecular docking and molecular minimization (MM) calculations and compared to a co-crystallized inhibitor (BWQ) acting as a reference inhibitor. Molecular dynamics (MD) simulations pursued by molecular mechanics-generalized Born surface area (MM-GBSA) binding energy estimations were further executed for compounds with MM-GBSA//MM binding energies lower than BWQ (calc. − 60.5 kcal/mol). NPACT00968 and NPACT01545 demonstrated auspicious inhibitory activities according to binding affinities (Δ G binding ) over the 100 ns MD simulations that were nearly one and a half folds compared to BWQ (− 100.4, − 94.7, and − 62.9 kcal/mol, respectively). Throughout the 100 ns MD simulations, structural and energetical analyses unveiled outstanding stability of the ABCG2 transporter when bound with NPACT00968 and NPACT01545. In silico calculations hold a promise for those two inhibitors as drug candidates of ABCG2 transporter and emphasize that further in vitro and in vivo experiments are guaranteed. Graphical abstract

Zinc–Lysine (Zn–Lys) Decipher Cadmium Tolerance by Improved Antioxidants, Nutrient Acquisition, and Diminished Cd Retention in Two Contrasting Wheat Cultivars - Muhammad Hussaan; Kashif Tanwir; Saghir Abbas; Muhammad Tariq Javed; Naeem Iqbal (Journal of Plant Growth Regulation, 2022)

Genetic diversity and population structure assessed through simple sequence repeat markers in Saccharum spp. hybrids from Pakistan and Sri Lanka - Sundas Shahzad; Muhammad Saeed; Shagufta Perveen; Muhammad Azeem; Iqra Sajjad; Shazia Saeed; Muhammad Naeem; Alia Javed; Iqra Sultan; Ukasha Faria; Sana Maryam; Muhammad Zaid Yousaf (Genetic Resources and Crop Evolution, 2022)

Influence of stress relief due to deep excavation on a brick masonry wall: 3D numerical predictions - Mukhtiar Ali Soomro; Dildar Ali Mangnejo; Abdullah Saand; Naeem Mangi; Muhammad Auchar Zardari (European Journal of Environmental and Civil Engineering, 2022)

NGS-driven molecular diagnosis of heterogeneous hereditary neurological disorders reveals novel and known variants in disease-causing genes - Ayaz Khan; Shixiong Tian; Muhammad Tariq; Sheraz Khan; Muhammad Safeer; Naimat Ullah; Nazia Akbar; Iram Javed; Mahnoor Asif; Ilyas Ahmad; Shahid Ullah; Humayoon Shafique Satti; et al. (Molecular Genetics and Genomics, 2022)

Appraisal and risk assessment of polycyclic aromatic hydrocarbons (PAHs), polychlorinated biphenyls (PCBs), and organochlorine pesticides (OCPs) in wastewater irrigated area - Yusra Mahfooz; Abdullah Yasar; Liu Guijian; Qamer Ul Islam; Rizwan Rasheed; Muhammad Afzaal; Hifza Butt; Urooj Naeem (Arabian Journal of Geosciences, 2022)

Coupling biochar with microbial inoculants improves maize growth and nutrients acquisition under phosphorous-limited soil - Hafiz Muhammad Rashad Javeed; Rimsha Naeem; Mazhar Ali; Rafi Qamar; Muhammad Aqeel Sarwar; Fahim Nawaz; Atique-ur-Rehman; Muhammad Shehzad; Amjad Farooq; Haseeb-ur-Rehman; Samina Khalid; Khuram Mubeen; et al. (Acta Physiologiae Plantarum, 2022)

Flooding tolerance in plants: from physiological and molecular perspectives - Nasrullah; Shahid Ali; Muhammad Umar; Lifang Sun; Muhammad Naeem; Humaira Yasmin; Naeem Khan (Brazilian Journal of Botany, 2022)

A Comprehensive Review About Bioactive Peptides: Sources to Future Perspective - Muhammad Naeem; Muhammad Inamullah Malik; Talha Umar; Swaiba Ashraf; Adnan Ahmad (International Journal of Peptide Research and Therapeutics, 2022)

RETRACTED ARTICLE: Ameliorative effect of two structurally divergent hydrazide derivatives against DSS-induced colitis by targeting Nrf2 and NF-κB signaling in mice - Ashrafullah Khan; Adnan Khan; Bushra Shal; Abdul Aziz; Sajjad Ahmad; Muhammad Usman Amin; Muhammad Naeem Ahmed; Zia-ur-Rehman; Salman Khan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2022)

Comparative genetic, biochemical and physiological analysis of sodium and chlorine in wheat - Muhammad Naeem; Arshad Abbas; Sami Ul-Allah; Waqas Malik; Faheem Shehzad Baloch (Molecular Biology Reports, 2022)

Elevated ozone phytotoxicity ameliorations in mung bean {Vigna radiata (L.) Wilczek} by foliar nebulization of silicic acid and ascorbic acid - Eram Shahzadi; Muhammad Nawaz; Muhammad Adrees; Muhammad Jawad Asghar; Naeem Iqbal (Environmental Science and Pollution Research, 2022)

Estimation of some heavy metals contamination in waste newspapers - Hatem Abdel Moniem Ahmed; Ahmed Saad Gouhar; Muhammad Naeem Janjua; Nada Alhafez (Environmental Monitoring and Assessment, 2022)

A plant-type L-asparaginase from Pyrobaculum calidifontis undergoes temperature dependent autocleavage - Muhammad Sajed; Samia Falak; Majida Atta Muhammad; Nasir Ahmad; Naeem Rashid (Biologia, 2022)

Effects of yeast extract on the production of phenylpropanoid metabolites in callus culture of purple basil (Ocimum Basilicum L. var purpurascens) and their in-vitro evaluation for antioxidant potential - Gouhar Zaman; Umar Farooq; Muhammad Naeem Bajwa; Hasnain Jan; Muzamil Shah; Riaz Ahmad; Anisa Andleeb; Samantha Drouet; Christophe Hano; Bilal Haider Abbasi (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Electrical resistivity in the assessment of subsurface lithology and groundwater depth—a case study in Rawalpindi, Pakistan - Faraz ul Haq; Usman Ali Naeem; Ijaz Ahmad; Muhammad Waseem; Mudassar Iqbal (Arabian Journal of Geosciences, 2022)

Influence of biochar on trace element uptake, toxicity and detoxification in plants and associated health risks: A critical review - Natasha Natasha; Muhammad Shahid; Sana Khalid; Irshad Bibi; Muhammad Asif Naeem; Nabeel Khan Niazi; Filip M. G. Tack; James Anthony Ippolito; Jörg Rinklebe (Critical Reviews in Environmental Science and Technology, 2022)

Pcal_2031, a RecA/Rad51 homologue from Pyrobaculum calidifontis, complements the ultraviolet light sensitivity of Escherichia coli - Syed Nasim Abbas; Mehwish Aslam; Amina Maqsood; Hafiza Zumra Fatima; Muhammad Arshad Javed; Naeem Rashid (Biologia, 2022)

Toxicity of selected organophosphate and pyrethroid insecticides against larval and adult stages of Culex quinquefasciatus - Muhammad Zubair; Hafiz Azhar Ali Khan; Waseem Akram; Khurram Zia; Rana Muhammad Naeem Ahsan; Malik Muhammad Shahbaz Sharif; Huma Qamar; Muhammad Kamil Malik (International Journal of Tropical Insect Science, 2022)

Combined efficacy of Cinnamomum zeylanicum and doxorubicin against leukemia through regulation of TRAIL and NF-kappa B pathways in rat model - Sidra Bukhari; Muhammad Hamid Siddique; Anum Naeem; InamUllah Khan; Zain Ali; Asiya Essa; Falak Fazal; Riffat Aysha Anis; Lukas Moran; Aneesa Sultan; Iram Murtaza; Petr Vanhara; et al. (Molecular Biology Reports, 2022)

Acacia jacquemontii ethyl acetate extract reduces hyperglycemia and pro-inflammatory markers while increasing endogenous antioxidant potential in alloxan-induced diabetic rats - Ambreen Mehmood Awan; Wafa Majeed; Faqir Muhammad; Muhammad Naeem Faisal (Environmental Science and Pollution Research, 2022)

Integrated application of plant bioregulator and micronutrients improves crop physiology, productivity and grain biofortification of delayed sown wheat - Naeem Ahmad; Ahmad Latif Virk; Sadam Hussain; Muhammad Bilal Hafeez; Fasih Ullah Haider; Muhammad Ishaq Asif Rehmani; Tauqeer Ahmad Yasir; Ariba Asif (Environmental Science and Pollution Research, 2022)

Geology and petrogenesis of gabbro from the Zhob Ophiolite, Balochistan, Pakistan - Abdul Naeem; Muhammad Ishaq Kakar; Rehanul Haq Siddiqui; Andrew C. Kerr; Muhammad Qasim Jan; Muhammad Ayoub Khan (Arabian Journal of Geosciences, 2022)

Omics: a tool for resilient rice genetic improvement strategies - Muhammad Naeem; Zeeshan Ali; Anzal Khan; Sami-Ul-Allah; Hassan Javed Chaudhary; Javeria Ashraf; Faheem Shahzad Baloch (Molecular Biology Reports, 2022)

Comparative Effect of Various Organic Extracts Coated Urea Fertilizer on the Release Pattern of Ammonium and Nitrate in the Soil at Different Time Intervals - Adeel Ahmad; Muhammad Yaseen; Hafiz Naeem Asghar; Shahzad Maqsood Ahmed Basra (Journal of Soil Science and Plant Nutrition, 2022)

Use of Eudragit RS PO, HPMC K100M, Ethyl Cellulose, and Their Combination for Controlling Nicorandil Release from the Bilayer Tablets with Atorvastatin as an Immediate-Release Layer - Wajiha Iffat; Muhammad Harris Shoaib; Rabia Ismail Yousuf; Faaiza Qazi; Zafar Alam Mahmood; Iyad Naeem Muhammad; Kamran Ahmed; Farrukh Rafiq Ahmed; Muhammad Suleman Imtiaz (Journal of Pharmaceutical Innovation, 2022)

Biocidal activity of green synthesized silver nanoformulation by Azadirachta indica extract a biorational approach against notorious cotton pest whitefly, Bemisia tabaci (Homoptera; Aleyrodidae) - Muhammad Shahid; Unsar Naeem-Ullah; Waheed S. Khan; Shafqat Saeed; Kashif Razzaq (International Journal of Tropical Insect Science, 2022)

Phycoremediation of textile effluents with enhanced efficacy of biodiesel production by algae and potential use of remediated effluent for improving growth of wheat - Muhammad Rashid Waqas; Sajid Mahmood Nadeem; Muhammad Yahya Khan; Zeeshan Ahmad; Liaqat Ali; Hafiz Naeem Asghar; Azeem Khalid (Environmental Science and Pollution Research, 2022)

Genetic diversity in natural population of Notopterus notopterus evaluated through mitochondrial DNA marker ATPase 6/8 regions and cytochrome b gene - Waqas Ahmad; Muhammad Naeem (Molecular Biology Reports, 2022)

Biochar increases salt tolerance and grain yield of quinoa on saline-sodic soil: multivariate comparison of physiological and oxidative stress attributes - Ghulam Abbas; Muhammad Mohsin Abrar; Muhammad Asif Naeem; Manzer H. Siddiqui; Hayssam M. Ali; Yantao Li; Khalil Ahmed; Nan Sun; Minggang Xu (Journal of Soils and Sediments, 2022)

The Interactive Approach of Rhizobacteria and l-tryptophan on Growth, Physiology, Tuber Characteristics, and Iron Concentration of Potato (Solanum tuberosum L.) - Zain Mushtaq; Hafiz Naeem Asghar; Zahir Ahmad Zahir; Muhammad Maqsood (Journal of Plant Growth Regulation, 2022)

Sustainable natural coloring potential of bitter gourd (Momordica charantia L.) residues for cotton dyeing: innovative approach towards textile industry - Fatima Batool; Shahid Adeel; Naeem Iqbal; Muhammad Azeem; Muhammad Hussaan (Environmental Science and Pollution Research, 2022)

Assessment of cadmium and lead tolerance potential of quinoa (Chenopodium quinoa Willd) and its implications for phytoremediation and human health - Muhammad Amjad; Muhammad Mohsin Iqbal; Ghulam Abbas; Abu Bakar Umer Farooq; Muhammad Asif Naeem; Muhammad Imran; Behzad Murtaza; Muhammad Nadeem; Sven-Erik Jacobsen (Environmental Geochemistry and Health, 2022)

Static force-based seismic analysis of reinforced concrete frames having weaker beam-column joints - Naveed Ahmad; Muhammad Rizwan; Qaisar Ali; Akhtar Naeem Khan (European Journal of Environmental and Civil Engineering, 2022)

Baseline toxicity of ten insecticides from organophosphate, pyrethroid and novel mode of action groups against Droschica mangiferae (Homoptera: Margarodidae) collected from citrus orchard in 2017–19 - Muhammad Nawaz Khan; Muhammad Babar Shahzad Afzal; Naima Din; Afifa Naeem; Ansa Banazeer; Malik Abdul Rehman; Hira Tariq; Muhammad Raza Salik; Muhammad Qasim (International Journal of Tropical Insect Science, 2022)

Habitat characterization of Aedes albopictus - Faisal Hafeez; Unsar Naeem-Ullah; Waseem Akram; Muhammad Arshad; Ayesha Iftikhar; Afifa Naeem; Muhammad Jawad Saleem (International Journal of Tropical Insect Science, 2022)

Susceptibility of Helicoverpa armigera Hübner (Lepidoptera: Noctuidae) on detached plant parts of transgenic and non-transgenic cotton - Muhammad Jawad Saleem; Faisal Hafeez; Qurban Ali; Asad Aslam; Muhammad Arshad; Dilbar Hussain; Ayesha Iftikhar; Afifa Naeem; Muhammad Saleem (International Journal of Tropical Insect Science, 2022)

Nickel tolerance and phytoremediation potential of quinoa are modulated under salinity: multivariate comparison of physiological and biochemical attributes - Naila Naheed; Ghulam Abbas; Muhammad Asif Naeem; Munawar Hussain; Rahat Shabbir; Saud Alamri; Manzer H. Siddiqui; Muhammad Zahid Mumtaz (Environmental Geochemistry and Health, 2022)

Information transmission in regional energy stock markets - Suha M. Alawi; Sitara Karim; Abdelrhman Ahmed Meero; Mustafa Raza Rabbani; Muhammad Abubakr Naeem (Environmental Science and Pollution Research, 2022)

Citric Acid (CA)–Modified Biochar Improved Available Phosphorus Concentration and Its Half-Life in a P-Fertilized Calcareous Sandy Soil - Adil Mihoub; Abu El-Eyuoon Abu Zied Amin; Hamid Reza Motaghian; Muhammad Farhan Saeed; Asif Naeem (Journal of Soil Science and Plant Nutrition, 2022)

Correction to: Biochemical characterization of Aedes aegypti (Linnaeus) (Diptera: Culicidae) resistance to deltamethrin, fipronil, and imidacloprid - Muhammad Waqas Sumra; Shoaib Freed; Muhammad Sheraz Shah; Muhammad Zeeshan Nazar; Sikandar Hussain; Afifa Naeem (Environmental Monitoring and Assessment, 2022)

Investigating the effect of Aspergillus niger inoculated press mud (biofertilizer) on the potential of enhancing maize (Zea mays. L) yield, potassium use efficiency and potassium agronomic efficiency - Urooj Naeem; Irfan ul Haq; Muhammad Afzaal; Akram Qazi; Abdullah Yasar; Amtul bari Tabinda; Yusra Mahfooz; Asad Ullah Naz; Humera Awan (Cereal Research Communications, 2022)

Strategies to enhance soluble production of heterologous proteins in Escherichia coli - Samia Falak; Muhammad Sajed; Naeem Rashid (Biologia, 2022)

Hydrological evaluation of 14 satellite-based, gauge-based and reanalysis precipitation products in a data-scarce mountainous catchment - Naeem Saddique; Muhammad Muzammil; Istakhar Jahangir; Abid Sarwar; Ehtesham Ahmed; Rana Ammar Aslam; Christian Bernhofer (Hydrological Sciences Journal, 2022)

Biochemical resistance characterization to chlorpyrifos, acetamiprid, spinosad, and emamectin benzoate in Phenacoccus solenopsis Tinsley (Hemiptera: Pseudococcidae) from Pakistan - Bushra Saddiq; Muhammad Babar Shahzad Afzal; Ashfaq Ahmad Sial; Naeem Abbas; Sarfraz Ali Shad; Asif Sajjad; Sajjad Ali (Phytoparasitica, 2022)

Effects of interspecific competition between Aedes aegypti and Culex quinquefasciatus on their life history traits - Daniyal Ahmad; Muhammad Waqas Sumra; Rizwan Mustafa Shah; Mehboob Alam; Sarfraz Ali Shad; Unsar Naeem-Ullah; Muhammad Binyameen (International Journal of Tropical Insect Science, 2022)

RNA interference-mediated knockdown of odorant-binding protein 2 and MP58 gene causes mortality in Myzus persicae - Iqra Mahmood; Amber Afroz; Muhammad Faheem Malik; Nadia Zeeshan; Muhammad Ramzan Khan; Umer Rashid; Muhammad Azmat Ullah Khan; Naeem Mehmood Ashraf; Sadia Alam (International Journal of Tropical Insect Science, 2022)

Remotely sensed image interpretation for assessment of land use land cover changes and settlement impact on allocated irrigation water in Multan, Pakistan - Maira Naeem; Hafiz Umar Farid; Muhammad Arbaz Madni; Rameez Ahsen; Zahid Mehmood Khan; Aqsa Dilshad; Huzaifa Shahzad (Environmental Monitoring and Assessment, 2022)

Microbial-based separate and simultaneous saccharification and ethanol fermentation of poplar (Populus euramericana) substrate - Fouzia Tabssum; Muhammad Naeem Khan (Environment, Development and Sustainability, 2022)

Transporters and transcription factors gene families involved in improving nitrogen use efficiency (NUE) and assimilation in rice (Oryza sativa L.) - Tahmina Nazish; Mamoona Arshad; Sami Ullah Jan; Ayesha Javaid; Muhammad Hassaan Khan; Muhammad Afzal Naeem; Muhammad Baber; Mohsin Ali (Transgenic Research, 2022)

Ecological risk assessment of heavy metal chromium in a contaminated pastureland area in the Central Punjab, Pakistan: soils vs plants vs ruminants - Fu Chen; Fatima Ghulam Muhammad; Zafar Iqbal Khan; Kafeel Ahmad; Muhammad Nadeem; Shahid Mahmood; Muhammad Umar Farooq Awan; Mudasra Munir; Ifra Saleem Malik; Asma Ashfaq; Razia Sultana; Ayesha Maqsood; et al. (Environmental Science and Pollution Research, 2022)

Evaluation of potential ecological risk and prediction of zinc accumulation and its transfer in soil plants and ruminants: public health implications - Fu Chen; Laraib Saqlain; Jing Ma; Zafar Iqbal Khan; Kafeel Ahmad; Asma Ashfaq; Razia Sultana; Fatima Ghulam Muhammad; Ayesha Maqsood; Majida Naeem; Ifra Saleem Malik; Mudasra Munir; et al. (Environmental Science and Pollution Research, 2022)

Bioaccumulation and transfer of zinc in soil plant and animal system: a health risk assessment for the grazing animals - Fu Chen; Fatima Ghulam Muhammad; Zafar Iqbal Khan; Kafeel Ahmad; Ifra Saleem Malik; Asma Ashfaq; Majida Naeem; Muhammad Nadeem; Jing Ma; Muhammad Umer Farooq Awan; Shahzadi Mahpara; Shahid Mehmood (Environmental Science and Pollution Research, 2022)

Characterization of Exotic, Native and Wild-Type Genotypes of Sugarcane (Saccharum spp. Hybrids) for Internal Nitrogen Use Efficiency Under Different Nitrogen Levels - Muhammad Anas; Krishan K. Verma; Ikram Ul Haq; Muhammad Naeem; Qiang Li; Fen Liao; Yong-Xiu Xing; Yang-Rui Li (Sugar Tech, 2021)

Correction to: Zinc-Solubilizing Bacteria-Mediated Enzymatic and Physiological Regulations Confer Zinc Biofortification in Chickpea (Cicer arietinum L.) - Sadia Batool; Hafz Naeem Asghar; Muhammad Asif Shehzad; Sanaullah Yasin; Muhammad Sohaib; Fahim Nawaz; Gulzar Akhtar; Khuram Mubeen; Zahir Ahmad Zahir; Muhammad Uzair (Journal of Soil Science and Plant Nutrition, 2021)

New records of Meschia pugnax (Heteroptera: Meschiidae) and stethoconus praefectus (Heteroptera: Miridae): predatory deraeocorinae plant bug associated with tingidae bugs, Pakistan - Zuhaib Ahmad; Muhammad Naeem; Tariq Mahmood; Rashid Azad (International Journal of Tropical Insect Science, 2021)

Correction to: Inventory and Quantitative Valuation of Geological and Geomorphological Sites from Gilgit‑Baltistan, Northern Pakistan - Javed Akhter Qureshi; Muzammil Khan; Shehzad Sikandar; Garee Khan; Naeem Abbas; Asghar Khan; Muhammad Alam; Rehmat Karim; Sarah J. Halvorson (Geoheritage, 2021)

Inventory and Quantitative Valuation of Geological and Geomorphological Sites from Gilgit-Baltistan, Northern Pakistan - Javed Akhter Qureshi; Muzammil Khan; Shehzad Sikandar; Garee Khan; Naeem Abbas; Asghar Khan; Muhammad Alam; Rehmat Karim; Sarah J. Halvorson (Geoheritage, 2021)

Assessment of Hg accumulation in fish and scalp hair in fishing communities along river Swat, Pakistan - Muhammad Aamir Munir; Bushra Khan; Ishaq Ahmed Mian; Muhammad Rafiq; Samreen Shahzadi; Kashif Naeem; Iqbal Ahmad (Environmental Science and Pollution Research, 2021)

Hydrogeochemical and health risk investigation of potentially toxic elements in groundwater along River Sutlej floodplain in Punjab, Pakistan - Sajjad Ahmad; Muhammad Imran; Behzad Murtaza; Natasha; Muhammad Arshad; Rab Nawaz; Abdul Waheed; Hafiz Mohkum Hammad; Muhammad Asif Naeem; Muhammad Shahid; Nabeel Khan Niazi (Environmental Geochemistry and Health, 2021)

The potential of microbes and sulfate in reducing arsenic phytoaccumulation by maize (Zea mays L.) plants - Natasha; Irshad Bibi; Khalid Hussain; Rabia Amen; Israr Masood Ul Hasan; Muhammad Shahid; Safdar Bashir; Nabeel Khan Niazi; Tariq Mehmood; Hafiz Naeem Asghar; Muhammad Farrakh Nawaz; Muhammad Mahroz Hussain; et al. (Environmental Geochemistry and Health, 2021)

Economic assessment of prospective shale gas play in Pakistan using discounted cashflow model - Faizan Ali; Muhammad Arqam Khan; Naeem ul Hussain Dahraj; Musab Usman; Laiba Sajid Cheema (Arabian Journal of Geosciences, 2021)

Examining the role of gender diversity on ownership structure-sustainable performance nexus: fresh evidence from emerging markets - Sitara Karim; Muhammad Abubakr Naeem; Abdelrahman Ahmed Meero; Mustafa Raza Rabbani (Environmental Science and Pollution Research, 2021)

Expression studies of stress responsive genes in cotton Gossypium hirsutum L. - Muhammad Naeem; Muhammad Iqbal; Sami Ul-Allah; Hassan Javed Chaudhary; Wajad Nazeer; Javeria Ashraf; Faheem Shahzad Baloch (Molecular Biology Reports, 2021)

Heavy Metals Accumulation in Dragonflies (Odonata) and Their Habitats in District Swabi, Khyber Pakhtunkhwa, Pakistan: Assessing Dragonfly Bionomics in the Region - Hajra Noor-Ul-Islam; Khurshaid Khan; Syed Ahmed Zia; Muhammad Naeem; Waqas Ahmad Shams (Bulletin of Environmental Contamination and Toxicology, 2021)

Role of nanotechnology in animal production and veterinary medicine - Ahmad Ali; Muhammad Ijaz; Yasir Razzaq Khan; Hina Afzal Sajid; Kashif Hussain; Ameer Hamza Rabbani; Muhammad Shahid; Omer Naseer; Awais Ghaffar; Muhammad Anas Naeem; Muhammad Zeeshan Zafar; Amir Iftikhar Malik; et al. (Tropical Animal Health and Production, 2021)

Population structure and phylogenetic relationship of Peach [Prunus persica (L.) Batsch] and Nectarine [Prunus persica var. nucipersica (L.) C.K. Schneid.] based on retrotransposon markers - Hina Naeem; Faisal Saeed Awan; Peter Michael Dracatos; Muhammad Wasim Sajid; Shahzad Saleem; Qudsia Yousafi; Muhammad Saad Khan; Asim Mehmood; Bushra Zulfiqar (Genetic Resources and Crop Evolution, 2021)

Environmental impact and diversity of protease-producing bacteria in areas of leather tannery effluents of Sialkot, Pakistan - Muhammad Qasim Butt; Nadia Zeeshan; Naeem Mahmood Ashraf; Muhammad Aftab Akhtar; Hina Ashraf; Amber Afroz; Aqsa Shaheen; Shumaila Naz (Environmental Science and Pollution Research, 2021)

Exploring natural colorant behavior of husk of durum (Triticum durum Desf.) and bread (Triticum aestivum L.) wheat species for sustainable cotton fabric dyeing - Ali Ahmad Khan; Shahid Adeel; Muhammad Azeem; Naeem Iqbal (Environmental Science and Pollution Research, 2021)

Biochemical characterization of Aedes aegypti (Linnaeus) (Diptera: Culicidae) resistance to deltamethrin, fipronil, and imidacloprid - Muhammad Waqas Sumra; Shoaib Freed; Muhammad Sheraz Shah; Muhammad Zeeshan Nazar; Sikandar Hussain; Afifa Naeem (Environmental Monitoring and Assessment, 2021)

Nitrogen balance, production performance, and plasma metabolites of lactating buffaloes in response to varying dietary protein levels - Muhammad Uzair Akhtar; Hifzulrahman; Muhammad Imran; Talat Naseer Pasha; Anjum Khalique; Muhammad Saadullah; Muhammad Naeem Tahir; Muhammad Ikram-ul-Haq; Muhammad Naveed-ul-Haque (Tropical Animal Health and Production, 2021)

Weed flora composition of different barley‐based cropping systems under conventional and conservation tillage practices - Muhammad Naeem; Mubshar Hussain; Muhammad Farooq; Shahid Farooq (Phytoparasitica, 2021)

Zinc-Solubilizing Bacteria-Mediated Enzymatic and Physiological Regulations Confer Zinc Biofortification in Chickpea (Cicer arietinum L.) - Sadia Batool; Hafiz Naeem Asghar; Muhammad Asif Shehzad; Sanaullah Yasin; Muhammad Sohaib; Fahim Nawaz; Gulzar Akhtar; Khuram Mubeen; Zahir Ahmad Zahir; Muhammad Uzair (Journal of Soil Science and Plant Nutrition, 2021)

Assessing the physico-chemical parameters and some metals of underground water and associated soil in the arid and semiarid regions of Tank District, Khyber Pakhtunkhwa, Pakistan - Asif Khan; Muhammad Naeem; Muhammad Bilal; Abbas Khan; Fazle Subhan; Muhammad Ikram; Muhammad Ishaq Ali Shah; Saleem Ullah; Asmat Ullah; Atta Ullah (Environmental Monitoring and Assessment, 2021)

RETRACTED ARTICLE: Pharmacological support to anti-arthritic prospective of physostigmine: a new approach - Haseeb Ahsan; Ihtisham Haider; Muhammad Naveed Mushtaq; Muhammad Naeem Qaisar; Farwa Naqvi; Awais Asif (Inflammopharmacology, 2021)

Carrageenan oligomers and salicylic acid act in tandem to escalate artemisinin production by suppressing arsenic uptake and oxidative stress in Artemisia annua (sweet wormwood) cultivated in high arsenic soil - Muhammad Naeem; Tariq Aftab; Abid Ali Ansari; Mohammad Masroor Akhtar Khan (Environmental Science and Pollution Research, 2021)

RETRACTED ARTICLE: Inhibition of NF-κB signaling and HSP70/HSP90 proteins by newly synthesized hydrazide derivatives in arthritis model - Ashraf Ullah Khan; Amna Khan; Adnan Khan; Bushra Shal; Abdul Aziz; Muhammad Naeem Ahmed; Salman Ul Islam; Hussain Ali; Adeeb Shehzad; Salman Khan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Monitoring of field-evolved resistance to flonicamid, neonicotinoid, and conventional insecticides in the Oxycarenus hyalinipennis costa - Inam Ullah; Shabana Wazir; Naeem Abbas; Muhammad Naeem; Khalid Abdullah; Zahid Mahmood; Mamoon-ur Rashid; Abdulwahab M. Hafez (Environmental Monitoring and Assessment, 2021)

Mineralogy and geochemistry of calc-alkaline magmatic rocks from the Mansehra Granitic Complex, NW Himalaya, Pakistan: insights into petrogenesis and tectonic setting - Mustansar Naeem; Tehseen Zafar; Muhammad Nawaz Chaudhry; Jean-Pierre Burg; Nasir Ahmad; Hafiz Ur Rehman (Arabian Journal of Geosciences, 2021)

Mitigating Drought Stress in Sunflower (Helianthus annuus L.) Through Exogenous Application of β-Aminobutyric Acid - Allah Wasaya; Tanveer Abbas; Tauqeer Ahmad Yasir; Naeem Sarwar; Ahsan Aziz; Muhammad Mansoor Javaid; Sheeraz Akram (Journal of Soil Science and Plant Nutrition, 2021)

Dusky cotton bug Oxycarenus hyalinipennis Costa (Lygaeidae: Hemiptera) loss assessment in cotton - Faisal Hafeez; Muhammad Akram; Muhammad Farooq; Muhammad Saghir; Muhammad Arshad; Ayesha Iftikhar; Afifa Naeem; Unsar Naeem-Ullah (International Journal of Tropical Insect Science, 2021)

Removal of N-terminal methionine of human interferon α-2b by co‐producing with Pyrococcus furiosus methionine aminopeptidase in Escherichia coli - Amina Arif; Naeem Rashid; Muhammad Akhtar (Biologia, 2021)

Physiological insights into sulfate and selenium interaction to improve drought tolerance in mung bean - Muhammad Aqib; Fahim Nawaz; Sadia Majeed; Abdul Ghaffar; Khawaja Shafique Ahmad; Muhammad Asif Shehzad; Muhammad Naeem Tahir; Muhammad Aurangzaib; Hafiz Muhammad Rashad Javeed; Muhammad Habib-ur-Rahman; Muhammad Munir Usmani (Physiology and Molecular Biology of Plants, 2021)
The present study involved two pot experiments to investigate the response of mung bean to the individual or combined SO 4 2− and selenate application under drought stress. A marked increment in biomass and NPK accumulation was recorded in mung bean seedlings fertilized with various SO 4 2− sources, except for CuSO 4 . Compared to other SO 4 2− fertilizers, ZnSO 4 application resulted in the highest increase in growth attributes and shoot nutrient content. Further, the combined S and Se application (S + Se) significantly enhanced relative water content (16%), SPAD value (72%), photosynthetic rate (80%) and activities of catalase (79%), guaiacol peroxidase (53%) and superoxide dismutase (58%) in the leaves of water-stressed mung bean plants. Consequently, the grain yield of mung bean was markedly increased by 105% under water stress conditions. Furthermore, S + Se application considerably increased the concentrations of P (47%), K (75%), S (80%), Zn (160%), and Fe (15%) in mung bean seeds under drought stress conditions. These findings indicate that S + Se application potentially increases the nutritional quality of grain legumes by stimulating photosynthetic apparatus and antioxidative machinery under water deficit conditions. Our results could provide the basis for further experiments on cross-talk between S and Se regulatory pathways to improve the nutritional quality of food crops.

The effects of some heavy metals on some fish species - Saba Naeem; Muhammad Ashraf; Masroor Ellahi Babar; Sana Zahoor; Shaukat Ali (Environmental Science and Pollution Research, 2021)

A missense allele of PEX5 is responsible for the defective import of PTS2 cargo proteins into peroxisomes - Muhammad Ali; Shahid Y. Khan; Tony A. Rodrigues; Tânia Francisco; Xiaodong Jiao; Hang Qi; Firoz Kabir; Bushra Irum; Bushra Rauf; Asma A. Khan; Azra Mehmood; Muhammad Asif Naeem; et al. (Human Genetics, 2021)

Overcoming open defecation for healthier environment in case of Pakistan - Muhammad Irfan Malik; Shahzada Muhammad Naeem Nawaz; Muhammad Nadeem (Environmental Science and Pollution Research, 2021)

Empirical analysis of CO2 emissions and sustainable use of energy sources in Pakistan - Muhammad Khalid Naeem; Sofia Anwar; Samia Nasreen (Environmental Science and Pollution Research, 2021)

Investigating the effect of Aspergillus niger inoculated press mud (biofertilizer) on the potential of enhancing maize (Zea mays L.) yield, phosphorous use efficiency, and phosphorous agronomic efficiency - Urooj Naeem; Muhammad Afzaal; Irfan ul Haq; Akram Qazi; Abdullah Yasar; Amtul Bari Tabinda; Yusra Mahfooz; Asad Ullah Naz; Humera Aslam Awan; Ashfaq Ahmad (Arabian Journal of Geosciences, 2021)

Ovine haemonchosis: a review - Muhammad Naeem; Zahid Iqbal; Nabila Roohi (Tropical Animal Health and Production, 2021)

Foliage applied potassium improves stay green, photosynthesis and yield of maize (Zea mays L.) under rainfed condition - Allah Wasaya; Tauqeer Ahmad Yasir; Naeem Sarwar; Omer Farooq; Atique ur Rehman; Khuram Mubeen; Muqarrab Ali; Muhammad Affan; Ahsan Aziz (Plant Physiology Reports, 2021)

Demographic and morphometric features of pink bollworm, Pectinophora gossypiella (Saunder) (Lepidoptera: Gelechiidae) on four host plants - Muhammad Naeem Mushtaq; Muhammad Arshad; Shahid Majeed; Sajid Aleem Khan (International Journal of Tropical Insect Science, 2021)

Impact of Urbanization on Groundwater Levels in Rawalpindi City, Pakistan - Faraz ul Haq; Usman Ali Naeem; Hamza Farooq Gabriel; Noor Muhammad Khan; Ijaz Ahmad; Habib Ur Rehman; Muhammad Awais Zafar (Pure and Applied Geophysics, 2021)

Elucidating Cd-mediated distinct rhizospheric and in planta ionomic and physio-biochemical responses of two contrasting Zea mays L. cultivars - Saghir Abbas; Muhammad Tariq Javed; Qasim Ali; Muhammad Sohail Akram; Kashif Tanwir; Shafaqat Ali; Hassan Javed Chaudhary; Naeem Iqbal (Physiology and Molecular Biology of Plants, 2021)

Allelopathic hormesis and potent allelochemicals from multipurpose tree Moringa oleifera leaf extract - Shagufta Perveen; Muhammad Naeem Mushtaq; Muhammad Yousaf; Nighat Sarwar (Plant Biosystems, 2021)

Interaction of watermelon chlorotic stunt virus with satellites - Muhammad Shafiq; Muhammad Naeem Sattar; Muhammad Shafiq Shahid; Abdullah M. Al-Sadi; Rob W. Briddon (Australasian Plant Pathology, 2021)

Petrology and geochemistry of volcanic and volcanoclastic rocks from Zhob ophiolite, North-Western Pakistan - Abdul Naeem; Andrew C. Kerr; Muhammad Ishaq Kakar; Rehanul Haq Siddiqui; Muhammad Ayoub Khan; Nisar Ahmed (Arabian Journal of Geosciences, 2021)

Influence of Different Organic Manures and Their Combinations on Productivity and Quality of Bread Wheat - Nauman Ali; Muhammad Naeem Khan; Muhammad Saeed Ashraf; Sobia Ijaz; Hafiz Saeed-ur-Rehman; Muhammad Abdullah; Noor Ahmad; Hafiz Muhammad Akram; Muhammad Farooq (Journal of Soil Science and Plant Nutrition, 2020)

Quantification and risk assessment of heavy metal build-up in soil–plant system after irrigation with untreated city wastewater in Vehari, Pakistan - Tania Sarwar; Muhammad Shahid; Natasha; Sana Khalid; Ali Haidar Shah; Naveed Ahmad; Muhammad Asif Naeem; Zia ul Haq; Behzad Murtaza; Hafiz Faiq Bakhat (Environmental Geochemistry and Health, 2020)

Exogenous calcium mitigates heat stress effects in common bean: a coordinated impact of photoprotection of PSII, up-regulating antioxidants, and carbohydrate metabolism - Muhammad Naeem; Jesse Riaz Traub; Habib-ur-Rehman Athar; Wayne Loescher (Acta Physiologiae Plantarum, 2020)

Intraperitoneal injections of copper ferrite nanoparticles disturb blood, plasma, and antioxidant parameters of Wistar rats in a sex-specific manner - Hasna Riaz; Rimsha Hashmi; Shairyar Abid; Nisha Shareef; Abida Faqir; Aqsa Amir; Muhammad Saqib Shahzad; Muhammad Shakeel; Saeed Akhtar; Muhammad Naeem Ashiq; Ather Ibrahim; Furhan Iqbal (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

The potential of Allium sativum and Cannabis sativa extracts for anti-tick activities against Rhipicephalus (Boophilus) microplus - Nasreen Nasreen; Sadaf Niaz; Adil Khan; Muhammad Arfan Zaman; Sultan Ayaz; Huma Naeem; Nasrullah Khan; Abdallah M. Elgorban (Experimental and Applied Acarology, 2020)

Statistical Assessment of Toxic and Essential Metals in the Serum of Female Patients with Lung Carcinoma from Pakistan - Muhammad Abdul Qayyum; Zahid Farooq; Muhammad Yaseen; Mian HR Mahmood; Ahmad Irfan; Muhammad Nadeem Zafar; Muddassir Khawaja; Kashif Naeem; Dursun Kisa (Biological Trace Element Research, 2020)

Modulation of growth and key physiobiochemical attributes after foliar application of zinc sulphate (ZnSO4) on wheat (Triticum aestivum L.) under cadmium (Cd) stress - Shagufta Perveen; Muhammad Saeed; Abida Parveen; Muhammad Tariq Javed; Sara Zafar; Naeem Iqbal (Physiology and Molecular Biology of Plants, 2020)

Correction to: Sublethal effects of a juvenile hormone analog, Pyriproxyfen demographic parameters of non-target predator, Hippodamia convergens Guerin-Meneville (Coleoptera: Coccinellidae) - Ayesha Iftikhar; Faisal Hafeez; Muhammad Hafeez; Muhammad Farooq; Muhammad Asif Aziz; Muhammad Sohaib; Afifa Naeem; Yaobin Lu (Ecotoxicology, 2020)

Sublethal effects of a juvenile hormone analog, Pyriproxyfen on demographic parameters of non-target predator, Hippodamia convergens Guerin-Meneville (Coleoptera: Coccinellidae) - Ayesha Iftikhar; Faisal Hafeez; Muhammad Hafeez; Muhammad Farooq; Muhammad Asif Aziz; Muhammad Sohaib; Afifa Naeem; Yaobin Lu (Ecotoxicology, 2020)

Enhancement of salt tolerance in maize (Zea mays L.) using locally isolated Bacillus sp. SR-2-1/1 - Khadija Rafiq; Muhammad Sohail Akram; Muhammad Shahid; Uzma Qaisar; Naeem Rashid (Biologia, 2020)

Leading edges in bioremediation technologies for removal of petroleum hydrocarbons - Urooj Naeem; Muhammad Akram Qazi (Environmental Science and Pollution Research, 2020)

Compositional and health risk assessment of drinking water from health facilities of District Vehari, Pakistan - Behzad Murtaza; Natasha; Muhammad Amjad; Muhammad Shahid; Muhammad Imran; Noor Samad Shah; Ghulam Abbas; Muhammad Asif Naeem; Muhammad Amjad (Environmental Geochemistry and Health, 2020)

A new biochar from cotton stalks for As (V) removal from aqueous solutions: its improvement with H3PO4 and KOH - Munawar Hussain; Muhammad Imran; Ghulam Abbas; Muhammad Shahid; Muhammad Iqbal; Muhamamd Asif Naeem; Behzad Murtaza; Muhammad Amjad; Noor Samad Shah; Zia Ul Haq Khan; Azhar Ul Islam (Environmental Geochemistry and Health, 2020)

Biochar impact on microbial population and elemental composition of red soil - Zabih Ullah; Shafaqat Ali; Niaz Muhammad; Naeem Khan; Muhammad Rizwan; Muhammad Daud Khan; Niamat Khan; Baharullah Khattak; Haifa Abdulaziz S. Alhaithloul; Mona H. Soliman; Hamid Ullah; Dilnaz Begum; et al. (Arabian Journal of Geosciences, 2020)

Silybum marianum (milk thistle) improves vancomycin induced nephrotoxicity by downregulating apoptosis - Naila Malkani; Ammara Naeem; Farah Ijaz; Sidra Mumtaz; Saima Ashraf; Muhammad Imran Sohail (Molecular Biology Reports, 2020)

Vibration analysis of damaged and undamaged steel structure systems: cantilever column and frame - Muhammad Abuzar Khan; Kareem Akhtar; Naveed Ahmad; Feroz Shah; Naeem Khattak (Earthquake Engineering and Engineering Vibration, 2020)

Synthesis, characterization, and biocompatibility of lanthanum titanate nanoparticles in albino mice in a sex-specific manner - Irum Naz Akram; Sana Akhtar; Ghulam Khadija; Mian Muhammad Awais; Muhammad Latif; Aasia Noreen; Mehwish Mobeen; Fareeha Sajjad; Zahida Sardar; Shahid Iqbal; Muhammad Naeem Ashiq; Furhan Iqbal (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Yucasin and cinnamic acid inhibit IAA and flavonoids biosynthesis minimizing interaction between maize and endophyte Aspergillus nomius - Asif Mehmood; Anwar Hussain; Muhammad Irshad; Muhammad Hamayun; Amjad Iqbal; Abdul Tawab; Naeem Khan (Symbiosis, 2020)

Production analysis of broiler farming in central Punjab, Pakistan - Naeem Ur Rahman; Shahid Mehmood; Sohail Ahmad; Arshad Javid; Athar Mahmud; Jibran Hussain; Muhammad Shabir Shaheen; Muhammad Usman; Syed Ghulam Mohayud Din Hashmi (Tropical Animal Health and Production, 2020)

Synthesis and characterization of newly synthesized neodymium zirconate zinc sulfide nanocomposite and its effect on selected aspects of albino mice behavior - Tafheem Khosa; Aysha Faiz; Asia Hayder; Muhammad Naeem Ashiq; Furhan Iqbal (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Gene cloning and characterization of Tk1281, a flap endonuclease 1 from Thermococcus kodakarensis - Hira Muzzamal; Qurat ul Ain; Muhammad Sulaiman Saeed; Naeem Rashid (Folia Microbiologica, 2020)

Oxidative stress risk assessment through heavy metal and arsenic exposure in terrestrial and aquatic bird species of Pakistan - Shamsa Kanwal; Naeem Akhtar Abbasi; Muhammad Jamshed Iqbal Chaudhry; Sajid Rashid Ahmad; Riffat Naseem Malik (Environmental Science and Pollution Research, 2020)

Spatiotemporal variability in spate irrigation systems in Khirthar National Range, Sindh, Pakistan (case study) - Abdul Ghani Soomro; Muhammad Munir Babar; Muhammad Arshad; Anila Memon; Babar Naeem; Arshad Ashraf (Acta Geophysica, 2020)

Estimation of groundwater potential using GIS modeling in Kohistan region Jamshoro district, Southern Indus basin, Sindh, Pakistan (a case study) - Aneela Memon; Kamran Ansari; Abdul Ghani Soomro; Muhammad Afzal Jamali; Babar Naeem; Arshad Ashraf (Acta Geophysica, 2020)

Harnessing natural colorants from algal species for fabric dyeing: a sustainable eco-friendly approach for textile processing - Muhammad Azeem; Naeem Iqbal; Riffat Ayesha Mir; Shahid Adeel; Fatima Batool; Ali Ahmad Khan; Sadaf Gul (Journal of Applied Phycology, 2019)

First detection and molecular characterization of avian polyomavirus in young parrots in Pakistan - Aayesha Riaz; Arfan Yousaf; Muhammad Moaeen-ud-Din; Muhammad Ali Abdullah Shah; Tayyaba Zainab; Sadia Masood; Naeem Akhter; Adnan Ali (Veterinary Research Communications, 2019)

Comparative study of the genetic basis of nitrogen use efficiency in wild and cultivated barley - Jawad Munawar Shah; Sidra tul Muntaha; Essa Ali; Azhar Abbas Khan; Syed Hassan Raza Zaidi; Ahmad Naeem Shahzad; Zeshan Hassan; Ahmad Nawaz; Muhammad Rashid; Syed Asad Hussain Bukhari (Physiology and Molecular Biology of Plants, 2019)

Downscaling of CMIP5 Models Output by Using Statistical Models in a Data Scarce Mountain Environment (Mangla Dam Watershed), Northern Pakistan - Naeem Saddique; Christian Bernhofer; Rico Kronenberg; Muhammad Usman (Asia-Pacific Journal of Atmospheric Sciences, 2019)

Compatibility and interaction of begomoviruses and DNA-satellites causing leaf curl disease in Asia, Africa and Mediterranean Region - Muhammad Naeem Sattar; Maaike Ligthart; Anders Kvarnheden (European Journal of Plant Pathology, 2019)

Characterization of recombinant endo-1,4-β-xylanase of Bacillus halodurans C-125 and rational identification of hot spot amino acid residues responsible for enhancing thermostability by an in-silico approach - Malik Siddique Mahmood; Faiz Rasul; Mahjabeen Saleem; Amber Afroz; Muhammad Faheem Malik; Naeem Mehmood Ashraf; Umar Rashid; Shumaila Naz; Nadia Zeeshan (Molecular Biology Reports, 2019)

Green algae, Cladophora glomerata L.–based natural colorants: dyeing optimization and mordanting for textile processing - Riffat Ayesha Mir; Shahid Adeel; Muhammad Azeem; Fatima Batool; Ali Ahmad Khan; Sadaf Gul; Naeem Iqbal (Journal of Applied Phycology, 2019)

Acaricidal efficacy of Calotropis procera (Asclepiadaceae) and Taraxacum officinale (Asteraceae) against Rhipicephalus microplus from Mardan, Pakistan - Adil Khan; Nasreen Nasreen; Sadaf Niaz; Sultan Ayaz; Huma Naeem; Ijaz Muhammad; Fazal Said; Robert D. Mitchell; Adalberto A. Pérez de León; Snehil Gupta; Sachin Kumar (Experimental and Applied Acarology, 2019)

Synthesis of magnetite-based nanocomposites for effective removal of brilliant green dye from wastewater - Muhammad Imran; Azhar Ul Islam; Muhammad Adnan Tariq; Muhammad Hussnain Siddique; Noor Samad Shah; Zia Ul Haq Khan; Muhammad Amjad; Salah Ud Din; Ghulam Mustafa Shah; Muhammad Asif Naeem; Muhammad Nadeem; Muhammad Nawaz; et al. (Environmental Science and Pollution Research, 2019)

Recombinant Tk0522, a carbohydrate esterase homologue from Thermococcus kodakarensis, does not require a signal sequence for translocation to periplasmic space in Escherichia coli - Anam Tariq; Alina Gul; Majida A. Muhammad; Naeem Rashid; Masood A Siddiqui (Biologia, 2019)

N-Pyrazoloyl and N-thiopheneacetyl hydrazone of isatin exhibited potent anti-inflammatory and anti-nociceptive properties through suppression of NF-κB, MAPK and oxidative stress signaling in animal models of inflammation - Sara Zeeshan; Muhammad Naveed; Adnan Khan; Ayesha Atiq; Maryam Arif; Muhammad Naeem Ahmed; Yeong Shik Kim; Salman Khan (Inflammation Research, 2019)

Removal of pharmaceuticals and personal care products using constructed wetlands: effective plant-bacteria synergism may enhance degradation efficiency - Phuong Minh Nguyen; Muhammad Afzal; Inaam Ullah; Naeem Shahid; Mujtaba Baqar; Muhammad Arslan (Environmental Science and Pollution Research, 2019)

Haunch retrofitting technique for seismic upgrading deficient RC frames - Naveed Ahmad; Junaid Akbar; Muhammad Rizwan; Bashir Alam; Akhtar Naeem Khan; Abdul Lateef (Bulletin of Earthquake Engineering, 2019)

Technetium-99m labeled Ibuprofen: Development and biological evaluation using sterile inflammation induced animal models - Naeem-Ul-Haq Khan; Syed Ali Raza Naqvi; Hamza Sohail; Samina Roohi; Muhammad Asghar Jamal (Molecular Biology Reports, 2019)

Over 100 years of faults interaction, stress accumulation, and creeping implications, on Chaman Fault System, Pakistan - Muhammad Shahid Riaz; Shan Bin; Shahid Naeem; Wang Kai; Zujun Xie; Syed Mushhad M. Gilani; Umer Ashraf (International Journal of Earth Sciences, 2019)

Opportunities and challenges in the remediation of metal-contaminated soils by using tobacco (Nicotiana tabacum L.): a critical review - Muhammad Zia ur Rehman; Muhammad Rizwan; Muhammad Irfan Sohail; Shafaqat Ali; Aisha A. Waris; Hinnan Khalid; Asif Naeem; Hamaad Raza Ahmad; Arslan Rauf (Environmental Science and Pollution Research, 2019)

RETRACTED ARTICLE: Trends of electronic waste pollution and its impact on the global environment and ecosystem - Rida Akram; Natasha; Shah Fahad; Muhammad Zaffar Hashmi; Abdul Wahid; Muhammad Adnan; Muhammad Mubeen; Naeem Khan; Muhammad Ishaq Asif Rehmani; Muhammadd Awais; Mazhar Abbas; Khurram Shahzad; et al. (Environmental Science and Pollution Research, 2019)

Pcal_0970: an extremely thermostable l-asparaginase from Pyrobaculum calidifontis with no detectable glutaminase activity - Shahid Mahmood Chohan; Naeem Rashid; Muhammad Sajed; Tadayuki Imanaka (Folia Microbiologica, 2019)

Transcriptional Study Revealed That Boron Supplementation May Alter the Immune-Related Genes Through MAPK Signaling in Ostrich Chick Thymus - Ke Xiao; Keli Yang; Jing Wang; Pengpeng Sun; Haibo Huang; Haseeb Khaliq; Muhammad Ahsan Naeem; Juming Zhong; Kemei Peng (Biological Trace Element Research, 2019)

Biogeochemical behavior of nickel under different abiotic stresses: toxicity and detoxification mechanisms in plants - Nuzhat Ameen; Muhammad Amjad; Behzad Murtaza; Ghulam Abbas; Muhammad Shahid; Muhammad Imran; Muhammad Asif Naeem; Nabeel K. Niazi (Environmental Science and Pollution Research, 2019)

Hereditary brain tumor with a homozygous germline mutation in PMS2: pedigree analysis and prenatal screening in a family with constitutional mismatch repair deficiency (CMMRD) syndrome - Shahid Mahmood Baig; Ambrin Fatima; Muhammad Tariq; Tahir Naeem Khan; Zafar Ali; Mohammad Faheem; Humera Mahmood; Patrick Killela; Matthew Waitkus; Yiping He; Fangping Zhao; Sizhen Wang; et al. (Familial Cancer, 2019)

In vitro production of IAA by endophytic fungus Aspergillus awamori and its growth promoting activities in Zea mays - Asif Mehmood; Anwar Hussain; Muhammad Irshad; Muhammad Hamayun; Amjad Iqbal; Naeem Khan (Symbiosis, 2019)

Cysteine-induced alterations in physicochemical parameters of oat ( Avena sativa L. var. Scott and F-411) under drought stress - Shagufta Perveen; Muhammad Iqbal; Muhammad Saeed; Naeem Iqbal; Sara Zafar; Tehmina Mumtaz (Biologia Futura, 2019)

Modeling Sugar Beet Response to Different Combinations of On-Farm Water Management Practices Under Semi-arid Sub-tropical Environment - Abdul Malik; Abdul Sattar Shakir; Muhammad Jamal Khan; Muhammad Ajmal; Muhammad Shahzad Khattak; Taj Ali Khan; Zia Ul Haq; Mahmood Alam Khan; Naeem Ijaz (Sugar Tech, 2019)

Whole exome sequencing identified three ABCC6 variants in two Pakistani families with pseudoxanthoma elasticum phenotype - Fehmida Farid Khan; Muhammad Erfan; Nigar Kanwal; Muhammad Naeem (Molecular Biology Reports, 2019)

Characteristics of pipe corrosion scales in untreated water distribution system and effect on water quality in Peshawar, Pakistan - Dilawar Farhan Shams; Saeed Islam; Baoyou Shi; Waliullah Khan; Buddhika Gunawardana; Maryam Saad; Muhammad Qasim; Haider Ali Javed; Sahib Gul Afridi; Muhammad Naeem; Gul Shahzada Khan (Environmental Science and Pollution Research, 2019)

A multivariate analysis of physiological and antioxidant responses and health hazards of wheat under cadmium and lead stress - Behzad Murtaza; Faryal Naeem; Muhammad Shahid; Ghulam Abbas; Noor S. Shah; Muhammad Amjad; Hafiz Faiq Bakhat; Muhammad Imran; Nabeel Khan Niazi; Ghulam Murtaza (Environmental Science and Pollution Research, 2019)

Extremely stable indole-3-glycerol-phosphate synthase from hyperthermophilic archaeon Pyrococcus furiosus - Muhammad Arif; Naeem Rashid; Sumera Perveen; Qamar Bashir; Muhammad Akhtar (Extremophiles, 2019)

Carbon fiber paper@MgO films: in situ fabrication and high-performance removal capacity for phosphate anions - Saeed Ahmed; Muhammad Naeem Ashiq; Dianqing Li; Pinggui Tang; Yongjun Feng (Environmental Science and Pollution Research, 2018)

Role of foliar application of sulfur-containing compounds on maize (Zea mays L. var. Malka and hybrid DTC) under salt stress - Shagufta Perveen; Naeem Iqbal; Muhammad Saeed; Sara Zafar; Zunaira Arshad (Brazilian Journal of Botany, 2018)

Identification of a novel GLB1 mutation in a consanguineous Pakistani family affected by rare infantile GM1 gangliosidosis - Bibi Zubaida; Muhammad Almas Hashmi; Huma Arshad Cheema; Muhammad Naeem (Journal of Genetics, 2018)

Effect of exogenous nitric oxide on sulfur and nitrate assimilation pathway enzymes in maize (Zea mays L.) under drought stress - Sadia Majeed; Fahim Nawaz; Muhammad Naeem; Muhammad Yasin Ashraf (Acta Physiologiae Plantarum, 2018)

Interaction between PGPR and PGR for water conservation and plant growth attributes under drought condition - Naeem Khan; Asghari Bano; Muhammad Adnan Shahid; Wajid Nasim; MD Ali Babar (Biologia, 2018)

Oral supplementation of Lanthanum Zirconate nanoparticles moderately affected behavior but drastically disturbed leukocyte count, serum cholesterol levels and antioxidant parameters from vital organs of albino mice in a gender specific manner - Muhammad Nazar Aftab; Irum Naz Akram; Tafheem Khosa; Syeda Qandeel Zahra; Irum Bashir; Muhammad Naeem Ashiq; Furhan Iqbal (Metabolic Brain Disease, 2018)

Seismic fragility functions for code compliant and non-compliant RC SMRF structures in Pakistan - Naveed Ahmad; Asif Shahzad; Qaisar Ali; Muhammad Rizwan; Akhtar Naeem Khan (Bulletin of Earthquake Engineering, 2018)

A field study investigating the potential use of phosphorus combined with organic amendments on cadmium accumulation by wheat and subsequent rice - Muhammad Zia ur Rehman; Muhammad Rizwan; Shafaqat Ali; Asif Naeem; Balal Yousaf; Guijian Lui; Hinnan Khalid; Saifullah; Farhan Hafeez; Muhammad Azhar (Arabian Journal of Geosciences, 2018)

Screening wheat genotypes for better performance on reduced phosphorus supply by comparing glasshouse experiments with field trials - De-Yong Zhao; Shu-Song Zheng; Muhammad Kashif Naeem; Jian-Qing Niu; Ning Wang; Zhong-Jian Li; Hui-Lan Wu; Hong-Qing Ling (Plant and Soil, 2018)

Resistance in field populations of Amrasca devastans (Hemiptera: Cicadellidae) to new insecticides in Southern Punjab, Pakistan - Nasir Abbas; Naeem Abbas; Masood Ejaz; Sarfraz Ali Shad; Iqra Asghar; Aima Irum; Muhammad Binyameen (Phytoparasitica, 2018)

Phenanthrene Fluorescence Quenching in Aqueous Sodium Dodecyl Sulphate (SDS) and Determination of Important Metal Ions - Muhammad Idrees; Rafida Bibi; Muhammad Naeem Khan (Journal of Fluorescence, 2018)

Whole exome sequencing identified two novel homozygous missense variants in the same codon of CLCN7 underlying autosomal recessive infantile malignant osteopetrosis in a Pakistani family - Muhammad Aman Khan; Aman Ullah; Muhammad Naeem (Molecular Biology Reports, 2018)

Correction to: Anti-inflammatory, anti-rheumatic and analgesic activities of 2-(5-mercapto-1,3,4-oxadiazol-2-yl)-N-propylbenzenesulphonamide (MOPBS) in rodents - Hina Rasheed; Ruqayya Afridi; Ashraf Ullah Khan; Muhammad Zia Ullah; Sidra Khalid; Ayesha Atiq; Humaira Kashif; Muhammad Naeem Ahmed; Yeong Shik Kim; Salman Khan (Inflammopharmacology, 2018)

Anti-inflammatory, anti-rheumatic and analgesic activities of 2-(5-mercapto-1,3,4-oxadiazol-2-yl)-N-propylbenzenesulphonamide (MOPBS) in rodents - Hina Rasheed; Ruqayya Afridi; Ashraf Ullah Khan; Muhammad Zia Ullah; Sidra Khalid; Ayesha Atiq; Humaira Kashif; Muhammad Naeem Ahmed; Yeong Shik Kim; Salman Khan (Inflammopharmacology, 2018)

Performance evaluation of 1-D numerical model HEC-RAS towards modeling sediment depositions and sediment flushing operations for the reservoirs - Habib-ur-Rehman; Muhammad Asif Chaudhry; Usman Ali Naeem; Hashim Nisar Hashmi (Environmental Monitoring and Assessment, 2018)

Identification of phytotoxins in different plant parts of Brassica napus and their influence on mung bean - Azhar Mehmood; Muhammad Naeem; Farhan Khalid; Yousaf Saeed; Tasawer Abbas; Khawar Jabran; Muhammad Aqeel Sarwar; Asif Tanveer; Muhammad Mansoor Javaid (Environmental Science and Pollution Research, 2018)

RETRACTED ARTICLE: Evaluating toxicity of copper(II) oxide nanoparticles (CuO-NPs) through waterborne exposure to tilapia (Oreochromis mossambicus) by tissue accumulation, oxidative stress, histopathology, and genotoxicity - Khurram Shahzad; Muhammad Naeem Khan; Farhat Jabeen; Nasreen Kosour; Abdul Shakoor Chaudhry; Muhammad Sohail (Environmental Science and Pollution Research, 2018)

Effects of water shortage in Kabul River network on the plain areas of Khyber Pakhtunkhwa, Pakistan - Mohammad Nafees; Fawad Ahmad; Muhammad Naeem Butt; Mohammad Khurshed (Environmental Monitoring and Assessment, 2018)

Sugar beet extract acts as a natural bio-stimulant for physio-biochemical attributes in water stressed wheat (Triticum aestivum L.) - Ali Noman; Qasim Ali; Jazia Naseem; M. Tariq Javed; Hina Kanwal; Waqar Islam; Muhammad Aqeel; Noreen Khalid; Sara Zafar; Muhammad Tayyeb; Naeem Iqbal; Mahmooda Buriro; et al. (Acta Physiologiae Plantarum, 2018)

Enhancement of gene expression in Escherichia coli and characterization of highly stable ATP-dependent glucokinase from Pyrobaculum calidifontis - Tahira Bibi; Musadiq Ali; Naeem Rashid; Majida Atta Muhammad; Muhammad Akhtar (Extremophiles, 2018)

Deciphering the growth, organic acid exudations, and ionic homeostasis of Amaranthus viridis L. and Portulaca oleracea L. under lead chloride stress - Muhammad Tariq Javed; Muhammad Sohail Akram; Noman Habib; Kashif Tanwir; Qasim Ali; Nabeel Khan Niazi; Huma Gul; Naeem Iqbal (Environmental Science and Pollution Research, 2018)

Pcal_0632, a phosphorylating glyceraldehyde-3-phosphate dehydrogenase from Pyrobaculum calidifontis - Iram Aziz; Naeem Rashid; Raza Ashraf; Masood Ahmed Siddiqui; Tadayuki Imanaka; Muhammad Akhtar (Extremophiles, 2018)

A measles outbreak in Sindh, Pakistan caused by a genotype B3 virus - Syed Sohail Zahoor Zaidi; Abdul Hameed; Naeem Ali; Massab Umair; Muhammad Masroor Alam; Muhammad Suleman Rana; Salmaan Sharif; Uzma Bashir Aamir; Shahzad Shaukat; Mehar Angez; Adnan Khurshid; Ribqa Akhtar; et al. (Archives of Virology, 2017)

Detection of Verticillium species in Swedish soils using real-time PCR - Georgios Tzelepis; Sarosh Bejai; Muhammad Naeem Sattar; Arne Schwelm; Jonas Ilbäck; Johan Fogelqvist; Christina Dixelius (Archives of Microbiology, 2017)

Pcal_1311, an alcohol dehydrogenase homologue from Pyrobaculum calidifontis, displays NADH-dependent high aldehyde reductase activity - Raza Ashraf; Naeem Rashid; Tamotsu Kanai; Tadayuki Imanaka; Muhammad Akhtar (Extremophiles, 2017)

Understanding brassinosteroid-regulated mechanisms to improve stress tolerance in plants: a critical review - Fahim Nawaz; Muhammad Naeem; Bilal Zulfiqar; Asim Akram; Muhammad Yasin Ashraf; Muhammad Raheel; Rana Nauman Shabbir; Rai Altaf Hussain; Irfan Anwar; Muhammad Aurangzaib (Environmental Science and Pollution Research, 2017)

Response of cotton genotypes to water and heat stress: from field to genes - Muhammad Iqbal; Sami Ul-Allah; Muhammad Naeem; Muhammad Ijaz; Abdul Sattar; Ahmad Sher (Euphytica, 2017)

Biochar soil amendment on alleviation of drought and salt stress in plants: a critical review - Shafaqat Ali; Muhammad Rizwan; Muhammad Farooq Qayyum; Yong Sik Ok; Muhammad Ibrahim; Muhammad Riaz; Muhammad Saleem Arif; Farhan Hafeez; Mohammad I. Al-Wabel; Ahmad Naeem Shahzad (Environmental Science and Pollution Research, 2017)

Identification of a novel copper-activated and halide-tolerant laccase in Geobacillus thermopakistaniensis - Saadia Basheer; Naeem Rashid; Raza Ashraf; Muhammad Sohail Akram; Masood Ahmed Siddiqui; Tadayuki Imanaka; Muhammad Akhtar (Extremophiles, 2017)

Pcal_0111, a highly thermostable bifunctional fructose-1,6-bisphosphate aldolase/phosphatase from Pyrobaculum calidifontis - Iram Aziz; Naeem Rashid; Raza Ashraf; Qamar Bashir; Tadayuki Imanaka; Muhammad Akhtar (Extremophiles, 2017)

Arsenic uptake, accumulation and toxicity in rice plants: Possible remedies for its detoxification: A review - Hafiz Faiq Bakhat; Zahida Zia; Shah Fahad; Sunaina Abbas; Hafiz Mohkum Hammad; Ahmad Naeem Shahzad; Farhat Abbas; Hesham Alharby; Muhammad Shahid (Environmental Science and Pollution Research, 2017)

Seismic attributes’ application to evaluate the Goru clastics of Indus Basin, Pakistan - Muhammad Naseer Tayyab; Shazia Asim; Muhammad Mass Siddiqui; Muhammad Naeem; Sarfraz Hussain Solange; Farhan Khan Babar (Arabian Journal of Geosciences, 2017)

Photosynthesis and growth response of maize (Zea mays L.) hybrids exposed to cadmium stress - Tasneem Akhtar; Muhammad Zia-ur-Rehman; Asif Naeem; Rab Nawaz; Shafaqat Ali; Ghulam Murtaza; Muhammad Aamer Maqsood; Muhammad Azhar; Hinnan Khalid; Muhammad Rizwan (Environmental Science and Pollution Research, 2017)

Microwave-assisted enhancement of milkweed (Calotropis procera L.) leaves as an eco-friendly source of natural colorants for textile - Muhammad Hussaan; Naeem Iqbal; Shahid Adeel; Muhammad Azeem; M. Tariq Javed; Ali Raza (Environmental Science and Pollution Research, 2017)

Chitosan alleviates phytotoxicity caused by boron through augmented polyamine metabolism and antioxidant activities and reduced boron concentration in Cucumis sativus L. - Rashad Mukhtar Balal; Muhammad Adnan Shahid; Muhammad Mansoor Javaid; Zafar Iqbal; Guodong David Liu; Lincoln Zotarelli; Naeem Khan (Acta Physiologiae Plantarum, 2017)

Bioaccumulation of heavy metals and analysis of mineral element alongside proximate composition in foot, gills and mantle of freshwater mussels (Anodonta anatina) - Muhammad Sohail; Muhammad Naeem Khan; Abdul Shakoor Chaudhry; Naureen Aziz Qureshi (Rendiconti Lincei. Scienze Fisiche e Naturali, 2016)

Erratum to: An application of rock physics modeling to quantify the seismic response of gas hydrate-bearing sediments in Makran accretionary prism, offshore, Pakistan - Muhammad Irfan Ehsan; Nisar Ahmed; Perveiz Khalid; Liu Xue Wei; Mustansar Naeem (Geosciences Journal, 2016)

TK1656, an L-asparaginase from Thermococcus kodakarensis, a novel candidate for therapeutic applications - Shahid Mahmood Chohan; Muhammad Atif Nisar; Naeem Rashid; Ghazaleh Gharib; Qamar Bashir; Masood Ahmed Siddiqui (Biologia, 2016)

Pcal_1127, a highly stable and efficient ribose-5-phosphate pyrophosphokinase from Pyrobaculum calidifontis - Tahira Bibi; Sumera Perveen; Iram Aziz; Qamar Bashir; Naeem Rashid; Tadayuki Imanaka; Muhammad Akhtar (Extremophiles, 2016)

Longitudinal study of experimental induction of AA amyloidosis in mice seeded with homologous and heterologous AA fibrils - Naeem Muhammad; Tomoaki Murakami; Yasuo Inoshima; Naotaka Ishiguro (Inflammation Research, 2016)

Erratum to: Pcal_0768, a hyperactive 4-α-glucanotransferase from Pyrobaculum calidifontis - Sumaira Mehboob; Nasir Ahmad; Naeem Rashid; Tadayuki Imanaka; Muhammad Akhtar (Extremophiles, 2016)

Probiotic delivery systems: a brief overview - Jihyun Kim; Naeem Muhammad; Byung Hak Jhun; Jin-Wook Yoo (Journal of Pharmaceutical Investigation, 2016)

Pcal_0768, a hyperactive 4-α-glucanotransferase from Pyrobacculum calidifontis - Sumaira Mehboob; Nasir Ahmad; Naeem Rashid; Tadayuki Imanaka; Muhammad Akhtar (Extremophiles, 2016)

AM1 is a potential ABA substitute for drought tolerance as revealed by physiological and ultra-structural responses of oilseed rape - Muhammad Shahbaz Naeem; Lulu Dai; Farooq Ahmad; Ashfaq Ahmad; Jun Li; Chunlei Zhang (Acta Physiologiae Plantarum, 2016)

Differential Effects of Plant Growth-Promoting Rhizobacteria on Maize Growth and Cadmium Uptake - Iftikhar Ahmad; Muhammad Javed Akhtar; Hafiz Naeem Asghar; Umber Ghafoor; Muhammad Shahid (Journal of Plant Growth Regulation, 2016)

A New Broad-Spectrum Peptide Antibiotic Produced by Bacillus brevis Strain MH9 Isolated from Margalla Hills of Islamabad, Pakistan - Syed Aun Muhammad; Amjad Ali; Anam Naz; Afreenish Hassan; Naeem Riaz; Syed Saeed-ul-Hassan; Saadia Andleeb; Debmalya Barh (International Journal of Peptide Research and Therapeutics, 2016)

Accumulation of Residual Antibiotics in the Vegetables Irrigated by Pharmaceutical Wastewater - Shoaib Hussain; Muhammad Naeem; Muhammad Nawaz Chaudhry; Muhammad Adnan Iqbal (Exposure and Health, 2016)

Deltamethrin resistance in the cotton mealybug, Phenacoccus solenopsis Tinsley: Cross-resistance to other insecticides, fitness cost analysis and realized heritability - Bushra Saddiq; Naeem Abbas; Sarfraz Ali Shad; Muhammad Aslam; Muhammad Babar Shahzad Afzal (Phytoparasitica, 2016)

Seismic and well log driven structural and petrophysical analysis of the Lower Goru Formation in the Lower Indus Basin, Pakistan - Muhammad Naeem; Muhammad Kamran Jafri; Sayed S. R. Moustafa; Nassir S. AL-Arifi; Shazia Asim; Farhan Khan; Nisar Ahmed (Geosciences Journal, 2016)

Temporal Information of Directed Causal Connectivity in Multi-Trial ERP Data using Partial Granger Causality - Vahab Youssofzadeh; Girijesh Prasad; Muhammad Naeem; KongFatt Wong-Lin (Neuroinformatics, 2016)

Investigation of temporal change in glacial extent of Chitral watershed using Landsat data - Usman Ali Naeem; Muhammad Ali Shamim; Naeem Ejaz; Habib ur Rehman; Umer Mustafa; Hashim Nisar Hashmi; Abdul Razzaq Ghumman (Environmental Monitoring and Assessment, 2016)

Pcal_1699, an extremely thermostable malate dehydrogenase from hyperthermophilic archaeon Pyrobaculum calidifontis - Ghazaleh Gharib; Naeem Rashid; Qamar Bashir; Qura-tul Ann Afza Gardner; Muhammad Akhtar; Tadayuki Imanaka (Extremophiles, 2016)

Genetics, realized heritability and preliminary mechanism of spinosad resistance in Phenacoccus solenopsis Tinsley (Homoptera: Pseudococcidae): an invasive pest from Pakistan - Muhammad Babar Shahzad Afzal; Sarfraz Ali Shad; Naeem Abbas (Genetica, 2015)

Effect of inorganic amendments for in situ stabilization of cadmium in contaminated soils and its phyto-availability to wheat and rice under rotation - Muhammad Zia-ur Rehman; Muhammad Rizwan; Abdul Ghafoor; Asif Naeem; Shafaqat Ali; Muhammad Sabir; Muhammad Farooq Qayyum (Environmental Science and Pollution Research, 2015)

Reverse ion exchange as a major process controlling the groundwater chemistry in an arid environment: a case study from northwestern Saudi Arabia - Faisal K. Zaidi; Yousef Nazzal; Muhammad Kamran Jafri; Muhammad Naeem; Izrar Ahmed (Environmental Monitoring and Assessment, 2015)

Whole-exome sequencing identifies a novel LRAT mutation underlying retinitis punctata albescens in a consanguineous Pakistani family - Musharraf Jelani; Miyeon Jeon; Obaid Ur Rahman; Fazal Rahim; Muhammad Naeem; Changsoo Kang (Genes & Genomics, 2015)

Integrated study of seismic and well data for porosity estimation using multi-attribute transforms: a case study of Boonsville Field, Fort Worth Basin, Texas, USA - Muhammad Naeem; Hesham M. El-Araby; Mohammed Khalil Khalil; Muhammad Kamran Jafri; Farhan Khan (Arabian Journal of Geosciences, 2015)

Baseline susceptibility and resistance stability of Earias vittella fabricius (Lepidoptera: Noctuidae) to cypermethrin, deltamethrin and spinosad - Muhammad Tahir Jan; Naeem Abbas; Sarfraz Ali Shad; Muhammad Rafiq; Mushtaq Ahmad Saleem (Phytoparasitica, 2015)

Mutation of ATF6 causes autosomal recessive achromatopsia - Muhammad Ansar; Regie Lyn P. Santos-Cortez; Muhammad Arif Nadeem Saqib; Fareeha Zulfiqar; Kwanghyuk Lee; Naeem Mahmood Ashraf; Ehsan Ullah; Xin Wang; Sundus Sajid; Falak Sher Khan; Muhammad Amin-ud-Din; Joshua D. Smith; et al. (Human Genetics, 2015)

Efficacy of silicon priming and fertigation to modulate seedling’s vigor and ion homeostasis of wheat (Triticum aestivum L.) under saline environment - Muhammad Azeem; Naeem Iqbal; Shakila Kausar; M. Tariq Javed; M. Sohail Akram; M. Asim Sajid (Environmental Science and Pollution Research, 2015)

Gibberellic acid in combination with pressmud enhances the growth of sunflower and stabilizes chromium(VI)-contaminated soil - Muhammad Saleem; Hafiz Naeem Asghar; Muhammad Yahya Khan; Zahir Ahmad Zahir (Environmental Science and Pollution Research, 2015)

Production of human interferon alpha-2b in Escherichia coli and removal of N-terminal methionine utilizing archaeal methionine aminopeptidase - Amina Arif; Qura-Tul-Ann A. Gardner; Naeem Rashid; Muhammad Akhtar (Biologia, 2015)

Differential effects of cadmium and chromium on growth, photosynthetic activity, and metal uptake of Linum usitatissimum in association with Glomus intraradices - Amna; Naeem Ali; Sajid Masood; Tehmeena Mukhtar; Muhammad Aqeel Kamran; Mazhar Rafique; M. Farooq Hussain Munis; Hassan Javed Chaudhary (Environmental Monitoring and Assessment, 2015)

Predicting streamflows to a multipurpose reservoir using artificial neural networks and regression techniques - Muhammad Hassan; Muhammad Ali Shamim; Hashim Nisar Hashmi; Syed Zishan Ashiq; Imtiaz Ahmed; Ghufran Ahmed Pasha; Usman Ali Naeem; Abdul Razzaq Ghumman; Dawei Han (Earth Science Informatics, 2015)

Bioactive constituents from Croton sparsiflorus Morong - Durre Shahwar; Naeem Ahmad; Asma Yasmeen; Muhammad Akmal Khan; Sami Ullah; Rahman Atta-ur (Natural Product Research, 2015)

QTL mapping for economically important traits of common carp (Cyprinus carpio L.) - Muhammad Younis Laghari; Punhal Lashari; Xiaofeng Zhang; Peng Xu; Naeem Tariq Narejo; Baoping Xin; Yan Zhang; Xiaowen Sun (Journal of Applied Genetics, 2015)

Effects of steam-treated rice straw feeding on growth, digestibility, and plasma volatile fatty acids of goats under different housing systems - Naeem Muhammad; Rajput Nasir; Dong Li; Zhang Lili; Wang Tian (Tropical Animal Health and Production, 2014)

Mapping QTLs for Swimming Ability Related Traits in Cyprinus carpio L. - Muhammad Younis Laghari; Punhal Lashari; Xiaofeng Zhang; Peng Xu; Naeem Tariq Narejo; Yongxin Liu; Shahid Mehboob; K. Al-Ghanim; Yan Zhang; Xiaowen Sun (Marine Biotechnology, 2014)

Effect of emamectin benzoate on life history traits and relative fitness of Spodoptera litura (Lepidoptera: Noctuidae) - Syed Muhammad Zaka; Naeem Abbas; Sarfraz Ali Shad; Rizwan Mustafa Shah (Phytoparasitica, 2014)

Truncation of the E3 ubiquitin ligase component FBXO31 causes non-syndromic autosomal recessive intellectual disability in a Pakistani family - Asif Mir; Kumudesh Sritharan; Kirti Mittal; Nasim Vasli; Carolina Araujo; Talal Jamil; Muhammad Arshad Rafiq; Zubair Anwar; Anna Mikhailov; Sobiah Rauf; Huda Mahmood; Abdul Shakoor; et al. (Human Genetics, 2014)

Breeding approaches for bacterial leaf blight resistance in rice (Oryza sativa L.), current status and future directions - Mueen Alam Khan; Muhammad Naeem; Muhammad Iqbal (European Journal of Plant Pathology, 2014)

Assessment of human–leopard conflict in Machiara National Park, Azad Jammu and Kashmir, Pakistan - Muhammad Kabir; Arash Ghoddousi; Muhammad Sadique Awan; Muhammad Naeem Awan (European Journal of Wildlife Research, 2014)

Potential of Bacillus species against Meloidogyne javanica parasitizing eggplant (Solanum melongena L.) and induced biochemical changes - Muhammad Waseem Abbasi; Naeem Ahmed; Muhammad Javed Zaki; S. Shahid Shuakat; D. Khan (Plant and Soil, 2014)

Hydrogen sulfide ameliorates lead-induced morphological, photosynthetic, oxidative damages and biochemical changes in cotton - Saima Aslam Bharwana; Shafaqat Ali; Muhammad Ahsan Farooq; Basharat Ali; Naeem Iqbal; Farhat Abbas; Muhammad Sajid Aqeel Ahmad (Environmental Science and Pollution Research, 2014)

Tree species as a potential source of bio-herbicides for controlling Parthenium hysterophorus L. - Muhammad Ehsan Safdar; Asif Tanveer; Abdul Khaliq; Muhammad Shahbaz Naeem; Salman Ahmad (Natural Product Research, 2013)

Increased fitness and realized heritability in emamectin benzoate-resistant Chrysoperla carnea (Neuroptera: Chrysopidae) - Muhammad Mudassir Mansoor; Naeem Abbas; Sarfraz Ali Shad; Attaullah Khan Pathan; Muhammad Razaq (Ecotoxicology, 2013)

5-Aminolevulinic acid enhances photosynthetic gas exchange, chlorophyll fluorescence and antioxidant system in oilseed rape under drought stress - Dan Liu; Lingtong Wu; Muhammad Shahbaz Naeem; Hongbo Liu; Xiangqin Deng; Ling Xu; Fan Zhang; Weijun Zhou (Acta Physiologiae Plantarum, 2013)

Eggs Distribution Behaviour of Dubas Bug (Ommatissus Lybicus: Homoptera: Tropiduchidae) in Relation to Seasons and Some Physico- Morphic Characters of Date Palm Leaves - Arif Shah; Ata Ul Mohsin; Zahid Hafeez; Muhammad Naeem; Muhammad Irfan Ul Haq (Journal of Insect Behavior, 2013)

Ranging and foraging of Himalayan grey langurs (Semnopithecus ajax) in Machiara National Park, Pakistan - Riaz Aziz Minhas; Usman Ali; Muhammad Siddique Awan; Khawaja Basharat Ahmed; Muhammad Nasim Khan; Naeem Iftikhar Dar; Qamar Zaman Qamar; Hassan Ali; Cyril C. Grueter; Yamato Tsuji (Primates, 2013)

A Validated Spectrofluorimetric Method for the Determination of Citalopram in Bulk and Pharmaceutical Preparations Based on the Measurement of the Silver Nanoparticles-Enhanced Fluorescence of Citalopram/Terbium Complexes - Muhammad Naeem Khan; Jasmin Shah; Muhammad Rasul Jan; Sang Hak Lee (Journal of Fluorescence, 2013)

Cloning, characterization and molecular docking of a highly thermostable β-1,4-glucosidase from Thermotoga petrophila - Ikram Ul Haq; Mahmood Ali Khan; Bushra Muneer; Zahid Hussain; Sumra Afzal; Sana Majeed; Naeem Rashid; Muhammad Mohsin Javed; Ishtiaq Ahmad (Biotechnology Letters, 2012)

First cloning and characterization of aspartate aminotransferase from river buffalo (Bubalus bubalis) - Muhammad Shahid Nadeem; Naeem Rashid; Muzaffar Iqbal; Qurra-tul-Ann Afza Gardner; Muhammad Akhtar (Biologia, 2011)

Calcium invigorates the cadmium-stressed Brassica napus L. plants by strengthening their photosynthetic system - Guanglong Wan; Ullah Najeeb; Ghulam Jilani; Muhammad S. Naeem; Weijun Zhou (Environmental Science and Pollution Research, 2011)

Transgenic Brassica napus L. lines carrying a two gene construct demonstrate enhanced resistance against Plutella xylostella and Sclerotinia sclerotiorum - Hongbo Liu; Xiang Guo; Muhammad S. Naeem; Dan Liu; Ling Xu; Wenfang Zhang; Guixiang Tang; Weijun Zhou (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

Co-Ion Effect on Cr3+ Sorption by Amberlyst-15(H+) - Syed Mustafa; Khizar Hussain Shah; Abdul Naeem; Muhammad Waseem; Tauqeer Ahmad; Sadullah Khan (Water, Air, & Soil Pollution, 2011)

Ultraviolet-C mediated physiological and ultrastructural alterations in Juncus effusus L. shoots - Ullah Najeeb; Ling Xu; Zammurad I. Ahmed; Muhammad Rasheed; Ghulam Jilani; Muhammad S. Naeem; Weiqi Shen; Weijun Zhou (Acta Physiologiae Plantarum, 2011)

Gene cloning and characterization of glycine oxidase from newly isolated Bacillus subtilis strain R5 - Farrukh Jamil; Naeem Rashid; Qurra-tul-Ann Afza Gardner; Muhammad Akhtar (Biologia, 2011)

Kinetics of Chromium Ion Removal from Tannery Wastes Using Amberlite IRA-400 Cl− and its Hybrids - Syed Mustafa; Tauqeer Ahmad; Abdul Naeem; Khizar Hussain Shah; Muhammad Waseem (Water, Air, & Soil Pollution, 2010)

Surface properties and sub-surface aggregate assimilation of rhamnolipid surfactants in different aqueous systems - Zulfiqar Ali Raza; Zafar M. Khalid; Mohammad Saleem Khan; Ibrahim M. Banat; Asma Rehman; Abdul Naeem; Muhammad Tahir Saddique (Biotechnology Letters, 2010)

Production and Stability Evaluation of Modified-Release Microparticles for the Delivery of Drug Combinations - Muhammad Naeem Aamir; Mahmood Ahmad (AAPS PharmSciTech, 2010)

Insoluble but enzymatically active α-amylase from Bacillus licheniformis - Naeem Rashid; Alia Farooq; Ikram-ul-Haq; Muhammad Akhtar (Biologia, 2009)

Prevalence of hepatitis C virus (HCV) genotypes in Balochistan - Sarwat Afridi; Muhammad Naeem; Abid Hussain; Naseebullah Kakar; Masroor Ellahi Babar; Jamil Ahmad (Molecular Biology Reports, 2009)

Comparative effectiveness of Pseudomonas and Serratia sp. containing ACC-deaminase for improving growth and yield of wheat (Triticum aestivum L.) under salt-stressed conditions - Zahir Ahmad Zahir; Usman Ghani; Muhammad Naveed; Sajid Mahmood Nadeem; Hafiz Naeem Asghar (Archives of Microbiology, 2009)

Studies on the chemical constituents of Phyllanthus emblica - Habib-ur-Rehman; Khawaja Ansar Yasin; Muhammad Aziz Choudhary; Naeem Khaliq; Atta-ur-Rahman; Muhammad Iqbal Choudhary; Shahid Malik (Natural Product Research, 2007)

Piperidines: A new class of Urease inhibitors - Khalid Mohammed Khan; Zafar S. Saify; Muhammad Arif Lodhi; Naeem Butt; Shahnaz Perveen; Ghulam Murtaza Maharvi; Muhammad Iqbal Choudhary; Atta-ur-rahman (Natural Product Research, 2006)